Polyunsaturated fatty acid metabolism in the retinal pigment epithelium and its association with outer retinal disease - Naga Pradeep Rayana; Navdeep Gogna; Mark P. Krebs; Gayle B. Collin; Jürgen K. Naggert; Patsy M. Nishina (Mammalian Genome, 2026)
Polyunsaturated fatty acids (PUFAs) are essential for photoreceptor (PR) development, structure and function, and their availability in the outer retina is predominantly mediated by the retinal pigment epithelium (RPE), a cellular monolayer juxtaposed to the PR outer segments. Because PRs lack enzymatic machinery to generate critical PUFA intermediates from dietary precursors, they rely on the RPE to coordinate multiple steps of PUFA uptake, metabolism and export. Consequently, disruption in any of these steps perturbs PR homeostasis and compromises overall retinal health. In this review, we summarize current evidence about the genes, proteins, molecular pathways, and pathological alterations that govern the regulation of PUFA metabolism in the RPE. Data from human genetic disorders, mouse models and in vitro studies is discussed to illustrate how disruption of PUFA pathways in the RPE leads to lipid imbalance and retinal degeneration, and to highlight how these findings illuminate molecular mechanisms underlying PUFA biology. We also identify critical gaps in knowledge and unresolved questions surrounding RPE-PR PUFA metabolism and propose that addressing these gaps will be essential for advancing therapeutic strategies for retinal disease.

Trophic ecology and niche segregation among coexisting Macrourus species at South Georgia, Southern Ocean - José Abreu; Richard A. Phillips; Philip R. Hollyman; José P. Queirós; Paco Bustamante; Mark Belchier; Martin A. Collins; José C. Xavier (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Correction to: Assessment of extreme subsurface hydrologic conditions captured during atmospheric river storms in the San Francisco Bay area (California, USA) with applications to shallow landslide early warning - Brian D. Collins; Dianne L. Brien; Skye C. Corbett; Jonathan P. Perkins; Karimah H. Comstock (Landslides, 2026)

Assessment of extreme subsurface hydrologic conditions captured during atmospheric river storms in the San Francisco Bay area (California, USA) with applications to shallow landslide early warning - Brian D. Collins; Dianne L. Brien; Skye C. Corbett; Jonathan P. Perkins; Karimah H. Comstock (Landslides, 2026)
An increase in soil pore water pressure is the typical trigger for the majority of landslides caused by rainfall. Atmospheric river storms, common to the west coast of North America during the winter season, can deliver landslide triggering rainfall resulting in severe impacts to coastal communities. Using a network of hydrologic monitoring stations situated within landslide-prone terrain in the San Francisco Bay area of California (USA), we assess the meteorologic conditions and resulting hydrologic and landslide response resulting from eight consecutive storm events that caused thousands of shallow landslides during the winter of 2022–2023. We find disparate hydrological responses and resultant degrees of observed landsliding ranging from < 1 landslide/km 2 to 18 landslides/km 2 at the monitoring sites that reflect the interplay and differences between rainfall delivery, subsurface hydrological characteristics, and geotechnical properties at each site. Antecedent soil moisture from both early season rainfall and the first storm in the sequence played a critical role in setting up some hillslopes for failure. Subsequent storms then generated elevated pore water pressures for several hours with associated landsliding. However, we find that the occurrence of widespread landsliding required not only sufficient pore water pressure magnitude in susceptible hillslopes, but also full and prolonged effective soil saturation throughout hillslope profiles. Landslides may still occur at lower values and durations of effective saturation but are likely to be less extensive regionally. We present these findings within the context of research directions and improvements to landslide early warning systems first suggested by researchers 40 years ago.

A Review of 35 Years in Developing Constitutive Models for the Callovo-Oxfordian Claystone Behavior - M. N. Vu; G. Armand; J. Talandier; C. Plua; M. Souley; J. F. Shao; Z. Yu; J. B. Colliat; J. Vaunat; A. Gens; S. Olivella; F. Collin; et al. (Rock Mechanics and Rock Engineering, 2026)

Cumulative effects of forest fuel reduction and restoration treatment regimes on horizontal and vertical structure in the Sierra Nevada - Sean P. Reilly; Brandon M. Collins; John J. Battles; Rob A. York; Scott L. Stephens (Forest Ecology and Management, 2026)

Correction: Quantitative Mineral Resource Assessment of Lithium Pegmatite Deposits in the Northern Appalachian Orogen, USA - Niki E. Wintzer; Christopher S. Holm-Denoma; Jacob E. Poletti; Dalton M. McCaffrey; Stanley P. Mordensky; Erik R. Tharalson; Collin Cronkite-Ratcliff (Natural Resources Research, 2026)

Quantitative Mineral Resource Assessment of Lithium Pegmatite Deposits in the Northern Appalachian Orogen, USA - Niki E. Wintzer; Christopher S. Holm-Denoma; Jacob E. Poletti; Dalton M. McCaffrey; Stanley P. Mordensky; Erik R. Tharalson; Collin Cronkite-Ratcliff (Natural Resources Research, 2026)
Lithium demand is projected to increase more than 48 times by 2040 due to electric vehicle production and other energy storage needs. Most lithium production is outside of the USA, thereby increasing supply chain vulnerability. The combined end use importance and heightened supply risk of lithium make this lightest metallic element a critical commodity to the USA. To mitigate this supply risk, the US Geological Survey is actively assessing lithium deposits in the USA. Herein, we detail an assessment for lithium-mineralized pegmatites in the US northern Appalachian Mountains. Permissive tracts were generated by cross-referencing tectonic and geologic maps and mineral occurrence data with mappable criteria derived from generalized and region-specific lithium pegmatite ore deposit models; tracts were then ranked as having high, medium, or low permissibility. Available geophysical and geochemical data were found to be of minimal utility for this deposit type at the scale of the assessment. The number of undiscovered deposits were estimated and integrated into probabilistic simulations, which included an expanded and updated global grade and tonnage model of pegmatite-hosted lithium ore. The estimated total amount of undiscovered resources for the northern Appalachian Orogen has a median value of 1,410,000 metric tons of Li 2 O when considering moderate correlation across sub-regions. At a confidence level of 90%, a resource of at least 90,000 metric tons of Li 2 O remains undiscovered, and at a 10% confidence level, a resource of as much as 7,380,000 metric tons Li 2 O remains undiscovered. After applying an up-to-date economic filter to convert median contained lithium to recoverable material, a correlated total of 900,000 metric tons of Li 2 O may be economically extractable, equating to enough Li 2 O to provide the current annual US lithium supply deficit (presently obtained through net imports) for 127 years at 2025 rates of apparent consumption. This period of provision will inevitably shorten with projected increasing consumption rates, emphasizing that further research could be completed to better delineate regions of high lithium resource potential and support exploration and domestic production.

Timing of exposure impacts how organophosphorus pesticides affect the developing brain in the planarian Dugesia japonica - Rebecca T. Somach; Danielle Ireland; Hao P. Tran; Gustav Allotey; Eva-Maria S. Collins (Archives of Toxicology, 2026)
Exposure to organophosphorus pesticides (OPs) during pregnancy has been suggested to cause adverse outcomes on neural development of the fetus but the mechanisms underlying developmental neurotoxicity of OPs remain unclear. While OPs share acetylcholinesterase (AChE) as the primary molecular target, different OPs have been shown to induce different effects in laboratory studies. Previously, we found that OPs differentially affect regenerating planarians when applied on the first day of regeneration. To determine if the timing of OP exposure affects adverse outcomes, here, we performed a comparative study of 5 OPs—chlorpyrifos (17.8 μM), diazinon (16.2 μM), dichlorvos (1 μM), profenofos (10 μM), and malathion (56.2 μM)—in the planarian Dugesia japonica . We evaluated how effects on behavior and nervous system morphology changed with OP exposure starting on different days of regeneration/development. We found that some toxic effects were dependent on the developmental stage during exposure. For example, profenofos impaired brain development when exposure started on day 1 of development but caused lethality when exposure started during later stages. Inhibition of the enzymatic activity of AChE on day 12 of exposure was not affected by the different exposure paradigms, suggesting that the differential effects were either due to effects on the non-enzymatic functions of AChE or on other targets during neurodevelopment. This work provides insight into which neurodevelopmental key events are affected by OP exposure, enabling future mechanistic work to identify the targets underlying OP developmental neurotoxicity.

Nutrient Enrichment Increases Grassland Biomass Sensitivity to Interannual Precipitation Variation - Ingrid J. Slette; Eric W. Seabloom; Carlos Alberto Arnillas; Jonathan D. Bakker; Dana Blumenthal; Jane A. Catford; Scott L. Collins; Nico Eisenhauer; Philip A. Fay; Magda Garbowski; Sylvia Haider; W. Stanley Harpole; et al. (Global Change Biology, 2026)
Primary production underpins much of ecosystem functioning and is often limited by nutrient and water availability. Ongoing global increases in nutrient inputs and interannual precipitation variability are thus likely to impact primary production, with unclear consequences for interannual variability in plant biomass. We used data from 35 grasslands in the Nutrient Network coordinated fertilization experiment to test if nutrient addition alters the response of plant biomass to year‐to‐year variation in growing season precipitation, and whether the effects of nutrient addition vary with factors such as site aridity or plant community composition. Nutrient addition increased biomass (by an average of 46% across sites), rain‐use efficiency (by 48%), and the sensitivity of biomass to interannual variation in precipitation (i.e., larger increase in biomass in wet years; by 13%), but did not change the strength of the interannual precipitation‐biomass correlation. Both sensitivity and correlation strength were higher in more arid sites, regardless of nutrient addition. These results suggest that grassland ecosystem functioning may become more variable from year to year as nutrient enrichment increases biomass sensitivity to precipitation and precipitation becomes more variable.

Conservation implications of low contemporary connectivity along the Mid‐Atlantic Ridge in hydrothermal vent gastropods - E. Portanier; A. Tran Lu Y; F. Pradillon; C. Daguin‐Thiébaut; S. Ruault; P. Collins; E. Omnes; S. Fuchs; J. Carlsson; D. Jollivet; M. Matabos (Conservation Biology, 2026)
Polymetallic sulfide deposits produced at hydrothermal vent fields are targets for mining exploitation along the Mid‐Atlantic Ridge, threatening the functioning and resilience of vent ecosystems that provide multiple ecosystem services. Knowledge about connectivity between vents will inform conservation practices. The present‐day genetic structure and demographic history of the two vent‐dwelling gastropod species, Lepetodrilus atlanticus and Peltospira smaragdina , were investigated using more than 15,000 single‐nucleotide polymorphisms and mt Cox1 sequences. Each species comprised three genetic groups. Genetic breaks were stronger for L. atlanticus , separating three distinct operational taxonomic units (5°S, Broken Spur at 29°N, and the Azorean vent fields near 37°N). Peltospira smaragdina was also geographically separated into three groups: Broken Spur, TAG, and Snake Pit (23–29°N); Lucky Strike (37°N); and Moytirra (45°N). A semipermeable zone was detected south of Rainbow (35°N), similar to that of vent mussels in this area, suggesting the presence of a multispecies hybrid zone. Demographic inferences supported secondary contact between most pairs of metapopulations for both species, but the time since contact was insufficient for allele frequencies to rehomogenize. Gene flow between vent fields may be sporadic and rare or restricted by genetic barriers. The fragmentation of species into isolated metapopulations may reduce their resilience to disturbance and create the need for specific conservation measures. Isolated populations (e.g., Moytirra for P. smaragdina , 5°S and Broken Spur for L. atlanticus ), source populations (e.g., Lucky Strike for P. smaragdina ), admixture areas, and sites that may act as stepping stones within a metapopulation must be protected from deep‐sea mining. An average distance of

DNA barcoding reveals the presence of Whitson's grenadier, Macrourus whitsoni , in sub‐Antarctic waters of South Georgia, Southern Ocean - M. L. Romero Martínez; J. Abreu; J. P. Queirós; J. C. Xavier; P. R. Hollyman; E. Fitzcharles; M. A. Collins (Journal of Fish Biology, 2026)
Macrourid species constitute the main bycatch in Southern Ocean toothfish longline fisheries. We report the first confirmed record of Whitson's grenadier, Macrourus whitsoni , in the South Georgia toothfish fishery. Mitochondrial cox1 DNA barcoding confirmed its presence in bycatch samples collected around South Georgia and the northern South Sandwich Islands, with approximately 1% divergence from its congener, M. caml . Haplotype network analysis revealed a single dominant haplotype and two peripheral haplotypes, indicating a well‐connected Southern Ocean stock. These findings highlight the need for accurate species‐level identification to inform effective fisheries management.

No experimental evidence for the role of trait-mediated interactions in a marine tri-trophic cascade - Samuel D.G. Smith; Hansjoerg P. Kunc; Patrick C. Collins (Journal of Experimental Marine Biology and Ecology, 2026)

Clay mineralogy influence on cementitious phase development in calcined gravel wash fines cement blends - Prateek Kumar Sharma; Alastair J.N. MacLeod; Laurie P. Aldridge; Frank Collins; Will P. Gates (Applied Clay Science, 2026)

Individual Trees Respond to 40 Years of Climate Change Through Leaf Functional Trait Acclimation - Riley P. Fortier; Rodolfo Vásquez Martínez; Rocío Del Pilar Rojas Gonzalez; Rachel Collins; Luis Valenzuela Gamarra; Abel Montagudo Mendoza; Oliver L. Phillips; Timothy R. Baker; J. Sebastián Tello; Kenneth J. Feeley (Global Change Biology, 2026)
Forests are vital for regulating climate and sustaining biodiversity, but climate change threatens their ability to do so, especially in the tropics. Our knowledge of how tropical forests and their constituent trees will respond to changes in climate is largely based on functional trait studies; however, few previous studies have investigated trait changes within individual tropical trees across decades, limiting our ability to predict the future of these forests. In this study, we leveraged historical and contemporary botanical specimens collected from the same individual trees in the southern Peruvian Amazon, measured a suite of leaf traits to test for individual‐level trait changes over nearly 40 years, and then related these changes to concurrent changes in local climate. We hypothesized that trees have acclimated their functional traits in response to increasing air temperatures and drought intensification and that this acclimation should help to maintain stable leaf temperatures through time. In accord with our hypothesis, we found significant decreases in measured leaf traits, including size and shape metrics and stomatal traits, within individuals through time. We used these measured traits to model leaf temperatures through time, which increased faster than would be expected based on changes in air temperature alone. This accelerated warming of leaves was due to decreased stomatal conductance, a potential acclimation of trees to dry season intensification and rising [CO 2 ], thus limiting leaf transpirational cooling. In other words, trees have decreased abilities to cool their leaves, and consequently they may be approaching critical thermal thresholds faster than they would in the absence of water limitation. Our study provides evidence that while individual trees are acclimating to climate change, tropical forests are undergoing increasing thermal stress and that intensifying drought may be elevating this risk.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Exposure to chronic warming affects fitness components differently in two congener gastropods - Ahmed S. A. Abbas; Robert P. Ellis; Michael Collins; John I. Spicer; Manuela Truebano (Marine Biology, 2026)

Spatiotemporal variability in Antarctic krill (Euphausia superba) around South Georgia derived from Antarctic fur seal (Arctocephalus gazella) diets - J. Coleman; P. Hollyman; J. Ashburner; M. Jessopp; J. Forcada; K. Owen; I. J. Staniland; C. M. Waluda; M. A. Collins; P. N. Trathan (Marine Biology, 2026)

A sea-to-soil solution for the green tides threatening shellfish aquaculture: conceptual model and lessons learned from a pilot project - Sarah M. Collier; Emily Buckner; Nicole J. Capizzi; Meg Chadsey; Douglas P. Collins; Jonathan P. Davis; Erick Dowell; Alan Ismach; Brittany G. Johnson; Sergey Rabotyagov; Rob Smith; Katie R. Webb; et al. (Journal of Environmental Management, 2026)

Correction: Maximizing ENSO as a source of Western US hydroclimate predictability - Christina M. Patricola-DiRosario; John P. O’Brien; Mark D. Risser; Alan M. Rhoades; Travis A. O’Brien; Paul A. Ullrich; Dáithí A. Stone; William D. Collins (Climate Dynamics, 2026)

A Global Review of Bycatch Reduction Technology Assessments: Revealing Gaps in Fisher‐Focused Metrics - Cindy Vargas; James P. Collins; Jesse F. Senko (Fish and Fisheries, 2026)
Global fisheries support livelihoods, food security and economies, but the incidental capture of non‐target species—termed bycatch—remains a key conservation challenge. We compiled peer‐reviewed published studies to assess metrics used to evaluate the effectiveness of bycatch reduction technologies and gear modifications (BRTs) for reducing air‐breathing marine megafauna bycatch in global passive fisheries. We assessed 196 studies, including assessments in operational fisheries and controlled experiments, from 114 published articles between 1997 and 2024. These studies tested 28 types of BRTs across five fishing gears. Changes in bycatch and target catch were assessed in 94.4% and 73% of all studies, respectively. By contrast, only 6.6% of studies assessed catch value. We identified and evaluated seven fisher‐focused metrics that were divided into quantitative and anecdotal evidence describing how the application of BRTs affects fishers. Relative to quantitative assessments, 9.2% of all studies quantified effects on fishing gear, 8.7% quantified BRT cost, 4.1% quantified economic impact, 3.1% quantified fisher safety, 3.1% quantified BRT ease of use, 2% quantified operational efficiency and 1% quantified fisher perceptions of BRT efficacy. Relative to anecdotal evidence, 10.7% of all studies reported on ease of use, 7.1% on BRT cost, 6.6% on fisher perceptions of efficacy, 3.1% on effects on fishing gear, 1.5% on effects on fisher safety and 0.5% on both operational efficiency and economic impact. Across diverse regions and timeframes, our analysis highlights a persistent lack of fisher‐focused metrics in BRT research, emphasising the need for more holistic evaluations that consider fisher wellbeing.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Distribution and ecology of the four Macrourus species by‐caught in the longline fishery at South Georgia, Southern Ocean - José Abreu; Philip R. Hollyman; Jennifer J. Freer; M. L. Romero Martínez; José P. Queirós; Timothy Jones; Richard A. Phillips; José C. Xavier; Martin A. Collins (Journal of Fish Biology, 2026)
Although Macrourus species are the main by‐catch across Southern Ocean longline fisheries, including around South Georgia, the lack of species‐specific data has hindered effective management and ecological understanding. Aggregation of macrourids at genus level masks critical interspecific differences in life‐history strategies and vulnerabilities to fishing. Here, we provide the first comprehensive biological assessment of the four macrourid species caught in South Georgia waters: Macrourus caml , Macrourus carinatus , Macrourus holotrachys and Macrourus whitsoni . Using fishery and observer data collected in 2018–2022, we reveal pronounced female‐biased sex ratios in three species ( M. holotrachys , M. carinatus and M. caml ), strong depth‐based segregation by body length, distinct distributions and habitat preferences related to environmental features (bathymetric depth and slope, primary productivity and temperature). By‐catch rates were highest in the southern region of South Georgia and varied across species: M. holotrachys was the most frequently caught and had a wide spatial and bathymetric distribution (∼1000–1750 m); M. caml was the second most caught and appeared the most flexible in terms of habitat use; M. carinatus was mainly caught in the west, including at Shag Rocks; and M. whitsoni was caught less frequently and in deeper water (> 1500 m), mostly in the northeast and east, and had the most restricted distribution. These interspecific differences underscore the need for species‐level assessments of fisheries risk and improved data collection to fill knowledge gaps. Overall, this study provides a critical foundation for understanding the ecology of Macrourus species in sub‐Antarctic ecosystems and highlights that additional data are required for by‐caught species to aid species‐level management in toothfish longline fisheries in the CCAMLR area.

Novel sensory epithelial topography of the olfactory lamellae in southern bluefin tuna, Thunnus maccoyii (Scombridae) - Myoung-Hoon Ha; Travis Dutka; Julian Pepperell; Lucille Chapuis; Caroline C. Kerr; Shaun P. Collin (Ichthyological Research, 2026)
The arrangement of the sensory epithelium over the surface of the olfactory lamellae in teleosts is variable, with a diverse pattern ranging from large expanses of continuous epithelium to numerous discrete islets. As the olfactory epithelium is the location where water-borne odorants interact with olfactory receptors, its spatial distribution pattern serves as an important anatomical proxy for olfactory ability. However, nothing is known about the olfactory epithelial pattern in southern bluefin tuna, Thunnus maccoyii . Scanning electron microscopy was used to examine the spatial distribution pattern, area, and number of olfactory epithelial patches over the olfactory lamellar surface within the olfactory rosettes of both juvenile and mature T. maccoyii . Juvenile T. maccoyii exhibit a novel olfactory epithelial topography, where the lamellae in the caudal parts of the olfactory rosette display a combination of Type IV (olfactory epithelium arranged into numerous, small discrete islets) and Type III (olfactory epithelium irregularly intermingled with non-sensory epithelium) topographies. The lamellae in the rostral parts of the olfactory rosettes primarily have Type IV topography. In both arrangement patterns, the olfactory epithelia are smaller and more numerous rostrally. In mature T. maccoyii , the Type IV topography disappears, and lamellae in all parts of the olfactory rosette display exclusively Type III topography. The combined results of this study reveal a new and unique distribution pattern of olfactory sensory epithelia in T. maccoyii , with a striking change in distribution pattern associated with both lamellar location and growth, indicating adaptation to the different hydrodynamic conditions.

Incorporating fire severity mapping into fuel accumulation curves - Christopher E. Gordon; Luke Collins; Meaghan Jenkins; Brett P. Murphy; Trung H. Nguyen; Owen F. Price; Liubov Volkova; Christopher J. Weston; Rachael H. Nolan (Science of The Total Environment, 2026)

What’s inside the net? insights into fish bycatch diversity in the Antarctic krill fishery - María Lorena Romero Martínez; William D. K. Reid; Martin A. Collins; Katia Lizeth Treviño Cuellar; William P. Goodall-Copestake; James M. Clark; Benedict Viney; Susan Gregory; Kate Owen; Philip R. Hollyman (Polar Biology, 2026)
An ecosystem-based approach to fishery management requires, inter alia, knowledge of fishery impacts on both target and non-target species, as well as the wider ecosystem. To support management of the Antarctic krill fishery, we present a robust reference dataset for identifying fish species caught as bycatch. By combining morphological and molecular taxonomic identification, 53 fish species in 44 genera and 11 families were confidently identified. Our dataset extends the DNA barcode library of Sub-Antarctic and Antarctic fish species and provides a foundation for developing an enhanced identification guide for larval fish to be used by observers on board krill fishing vessels. Phylogenetic relationships were inferred from two commonly used barcode markers, the mitochondrial cox1 and the non-coding control region. We observed clear phylogenetic relationships, highlighting coherent placements of notothenioids, myctophids, Aulopiformes, Gadiformes and Zoarcoidei. The results suggest a discrepancy between observer-based and genetic identifications, with 20.6% of records representing misidentifications in the fishing seasons 2021/2022 and 2022/2023. Graphical Abstract Graphical abstract: illustrated by ©Louise Merquiol-Hatsya illustrations

Correction: A framework for detection and attribution of regional precipitation change: application to the United States historical record - Mark D. Risser; William D. Collins; Michael F. Wehner; Travis A. O’Brien; Christopher J. Paciorek; John P. O’Brien; Christina M. Patricola-DiRosario; Huanping Huang; Paul A. Ullrich; Burlen Loring (Climate Dynamics, 2026)

Correction: Quantifying the influence of natural climate variability on in situ measurements of seasonal total and extreme daily precipitation - Mark D. Risser; Michael F. Wehner; John P. O’Brien; Christina M. Patricola-DiRosario; Travis A. O’Brien; William D. Collins; Christopher J. Paciorek; Huanping Huang (Climate Dynamics, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Signal characteristics of potential airbursts in Titan’s atmosphere - Elisa Dong; Catherine D. Neish; John E. Moores; Shigeru Wakita; Gareth S. Collins; Peter G. Brown; Ralph D. Lorenz; Benjamin Fernando; Mark P. Panning (Icarus, 2026)

Resistance of shallow soil carbon to both short-term isolated and recurrent droughts in two semi-arid grasslands - Taofeek O. Muraina; Niwu Te; Saheed O. Jimoh; Robert Griffin-Nolan; Lin Song; Jiaqi Chen; Yuan Shi; Ahmed A. Amisu; Tilak Chaudhary; Qiang Yu; Melinda D. Smith; Alan K. Knapp; et al. (Oecologia, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Hydrodynamic flow in the peripheral olfactory system of pelagic fishes: A comparison between southern bluefin tuna, Thunnus maccoyii and black marlin, Istiompax indica - Myoung-Hoon Ha; Travis Dutka; Julian Pepperell; Lucille Chapuis; Caroline C. Kerr; Shaun P. Collin (Zoology, 2026)

HvABI5 is an important ABA-dependent regulator of drought stress response at heading time in barley - Anna Collin; Hubert Matkowski; Elvira Sari Dewi; Luiz Augusto Fornasier Milani; Daria Ponikwia; Issaka Abdulai; Beata Chmielewska; Kamlesh K. Sahu; Reimund P. Roetter; Miriam Schreiber; Robbie Waugh; Agata Daszkowska-Golec (Plant Science, 2026)

Superchilling storage reduces the growth and diversity of bacterial communities associated with Atlantic salmon (Salmo salar) fillets - P. Collin; M. Darsonval; O. Rué; F.T. Ndoye; G. Alvarez; F. Dubois-Brissonnet (Food Research International, 2026)

North Atlantic Oscillation modulates long-term ANPP dynamics via precipitation or temperature, depending on soil nutrient levels - JGN Irisarri; M Texeira; P Harris; PE Gundel; AL Collins (Agricultural and Forest Meteorology, 2026)

Soil property controls on plasticiser, antioxidant and UV absorber additive degradation across a global soil gradient - Michaela K. Reay; Martine Graf; Maddy Murphy; Charlie Monkley; Perrine J. Florent; Benjamin I. Collins; Nguyen Van Hien; Tran Minh Tien; Andreia Neves Fernandes; Tapan Adhikari; Samantha Viljoen; Mona Tolba; et al. (Environmental Science and Pollution Research, 2025)
Additives in agricultural plastics can leach into the surrounding soil during use or improper disposal. Their subsequent degradation rates directly regulate whether they persist and accumulate to levels with ecotoxicological effects or are rendered benign. However, which soil properties primarily regulate the degradation of additives remains unclear (e.g. soil carbon, pH, available nutrients, microbial biomass and community structure). We assessed the degradation of the common plastic additives with different functionalities (DEHP (di(2-ethylhexyl) phthalate; plasticiser), 2-hydroxy-4-n-octyloxybenzophenone (benzophenone-12; BP12; UV stabiliser) and AO168 (tris(2,4-di- tert -butylphenyl) phosphite; antioxidant)) in soils under controlled moisture and temperature conditions over 21 days across contrasting agricultural soils from six countries across a global transect (Australia, Brazil, Egypt, India, Vietnam and the UK). DEHP followed zero-order degradation kinetics, with negligible degradation in soils with low microbial biomass. BP12 degraded fastest via first-order degradation kinetics via ether cleavage and hydroxyl loss. The degradation of DEHP and BP12 was correlated with soil microbial biomass and nitrate concentration. BP12 degradation products detected included benzophenone and benzoic acid. DEHP is degraded via β-oxidation of alkyl groups to dibutyl phthalate and diethyl phthalate and through ester hydrolysis to phthalic acid. AO168 degraded via abiotic oxidation and phosphate ester hydrolysis to 2,4-di- tert -butyl-phenol, and degradation was not well correlated with any measured soil variable. Overall, these results show that the components of additive mixtures leached into soils will degrade at different rates due to varying mechanisms and controls exerted by the soil microbial biomass. Plastic additives have differing potentials to persist in agricultural soils globally, with some likely to accumulate to levels that may impact soil function and pose an ecotoxicological threat to soil biota.

Corrigendum to “Subchronic inhalation exposure to ultrafine particulate matter alters the intestinal microbiome in various mouse models” [Environ. Res. 248 (2024) 118242] - Candace Chang; Rajat Gupta; Farzaneh Sedighian; Allen Louie; David M. Gonzalez; Collin Le; Jae Min Cho; Seul-Ki Park; Jocelyn Castellanos; To-Wei Ting; Tien S. Dong; Nerea Arias-Jayo; et al. (Environmental Research, 2025)

Benthopelagic Deep-Sea Food Webs Along a Latitudinal Gradient in the Scotia Sea (Southern Ocean) - José P. Queirós; Mark Belchier; José Abreu; Paco Bustamante; Martin A. Collins; Ana M. M. Gonçalves; Irene Bermúdez-Gutiérrez; Gabriele Stowasser; Diana Vaz; Philip R. Hollyman; José C. Xavier (Ecosystems, 2025)
Understanding food-web structure is crucial to determine the functioning of ecosystems and sustainably manage resources. The Scotia Sea is an important area for Antarctic krill and toothfish fisheries, and one of the regions most impacted by climate change in the Southern Ocean. Whilst the pelagic Antarctic krill-centric food web has been investigated in reasonable detail, the structure of deep-sea food webs associated with toothfish fisheries remain largely unknown. Utilising stable isotopes and fatty acids as trophic proxies, we studied the deep-sea food-web structure in three locations of the Scotia Sea, from South Georgia (SG) to the South Sandwich Islands (SSI; divided into north and south). Our analyses indicate that all food webs were similar, presenting high trophic redundancy and similar vertical structure. All food webs had five trophic levels, with the 5th and 4th trophic levels mainly constituted of fish and the 3rd trophic level of cephalopods and crustaceans. However, some differences existed with the SG food web presenting larger diversity of producers and the bigeye grenadier Macrourus holotrachys in the highest trophic position, while Patagonian toothfish Dissostichus eleginoides and both Patagonian and Antarctic toothfish D. mawsoni were the top predators at SSI-North and SSI-South, respectively. Compared to coastal and pelagic food webs in the Southern Ocean, our results suggest that deep-sea food webs, including the benthic/demersal components, have a longer food-chain length. This study provides essential knowledge of the ecological variability of Southern Ocean deep-sea food webs while contributing to the management of resources within the SG and SSI Marine Protected Area.

Quantifying Benthic Flux of Mysis Biomass Through Diel Vertical Migration at the Ecosystem Scale - Brian P. O’Malley; Georgia W. Hoffman; Rosaura J. Chapina; Jason D. Stockwell; Collin J. Farrell (Ecosystems, 2025)
Mysis diluviana is a macroinvertebrate that couples benthic and pelagic habitats on a daily timescale through diel vertical migration (DVM). However, quantifying how much Mysis biomass is exchanged between benthic and pelagic habitats at an ecosystem scale is difficult because of sampling limitations and variability in Mysis DVM behavior related to light and depth. Although Mysis are benthic-pelagic migrators, a portion remains pelagic during the day offshore in Lake Ontario, partially contradicting the assumption of population-level DVM over deep areas. To estimate the amount of biomass transferred from benthic to pelagic habitat via DVM in Lake Ontario, we estimated the portion of pelagic biomass at night originating from benthic habitat as the difference between night and day pelagic estimates from net tows along a bathymetric depth gradient. We then modeled the portion as a function of depth, extrapolated these depth-dependent estimates to an existing lake wide night-pelagic dataset, and summed amounts across depth strata. We estimated more biomass was transferred from benthic to pelagic habitat at intermediate lake depths (100–160 m) despite greater offshore (> 180 m) night-pelagic biomass. Our results suggest ways to improve estimates of Mysis habitat coupling and how to account for important factors such as depth and light for modeling Mysis DVM behavior at the population- and ecosystem-levels.

What temperature is best for the offshore farming of the Australasian snapper, Chrysophrys auratus ? A collective examination of growth, FCR, O 2 consumption and welfare - Selwyn P. Collins; Leonardo J. Magnoni; Denham G. Cook; Suzanne E. Black; Neill A. Herbert (New Zealand Journal of Marine and Freshwater Research, 2025)
The Australasian snapper ( Chrysophrys auratus ) is a candidate for offshore aquaculture in New Zealand. The culture of snapper requires knowledge of the best locations for farms and a key variable is water temperature. The oxygen‐ and capacity‐limited thermal tolerance (OCLTT) hypothesis suggests fish performance is optimised at the temperature that maximises absolute aerobic scope (AAS), whereas the ‘multiple performances–multiple optima’ (MPMO) idea, suggests AAS and other performance measures can have different optimal temperatures. Therefore, the applicability of the OCLTT for snapper was tested by holding juveniles at 15, 18, 21, or 24°C for two months and constructing thermal performance curves (TPCs) for specific growth rate (SGR), feed conversion ratio (FCR) and AAS, and an assessment of welfare indicators. We hypothesised that the OCLTT would apply with all TPCs optimised at 21°C. However, AAS showed no discernible peak with temperature (although lower at 15 than 18°C); SGR and FCR improved non‐linearly with temperature; and welfare indicators varied little with temperature. This lack of aerobic limitation and evidence of MPMO suggests snapper are amenable to culture across a significant temperature range with warmer water likely providing the highest levels of productivity with maintained welfare.

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

Persistent Genomic Erosion in Whooping Cranes Despite Demographic Recovery - Claudia Fontsere; Samuel A. Speak; Andrew J. Caven; Juan Antonio Rodríguez; Xuejing Wang; Carolina Pacheco; Molly Cassatt‐Johnstone; Georgette Femerling; Brigid Maloney; Jennifer Balacco; Joanna Collins; Ying Sims; et al. (Molecular Ecology, 2025)
Integrating in‐situ (wild) and ex‐situ (captive) conservation efforts can mitigate genetic diversity loss and help prevent extinction of endangered wild populations. The whooping crane ( Grus americana ) experienced severe population declines in the 18th century, culminating in a collapse to ~20 individuals by 1944. Legal protections and conservation actions have since increased the census population from a stock of 16 individuals to approximately 840 individuals, yet the impact on genomic diversity remains unclear. We analysed the temporal dynamics of genomic erosion by sequencing a high‐quality reference genome, and re‐sequencing 16 historical (years 1867–1893) and 37 modern (2007–2020) genomes, including wild individuals and four generations of captive‐bred individuals. Genomic demographic reconstructions reveal a steady decline, accelerating over the past 300 years with the European settlement of North America. Temporal genomic analyses show that despite demographic recovery, the species has lost 70% of its historical genetic diversity and has increased its inbreeding. Although the modern population bottleneck reduced the ancestral genetic load, modern populations possess more realised load than masked load, possibly resulting in a chronic loss of fitness. Integrating pedigree and genomic data, we underscore the role of breeding management in reducing recent inbreeding. Yet ongoing heterozygosity loss, load accumulation, and persistent effects of historical inbreeding (i.e., background inbreeding) argue against the species' downlisting from its current Endangered status on the IUCN Red List and the Endangered Species Act. The presence of private genetic variation in wild and captive populations suggests that wild‐captive crosses could enhance genetic diversity and reduce the realised load. Our findings emphasise the role of genomics in informing conservation management and policy.

Deep-sea biotope classification using opportunistic sampling: insights for future management - Heidy Q. Dias; Kerstin Kröger; Andrew J. Wheeler; Riccardo Arosio; Audrey Recouvreur; Tim P. Le Bas; Isobel A. Yeo; Patrick C. Collins (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Factors predicting incidence of nontuberculous mycobacteria in an era of climate change and altered ecosystems in the United States - Samantha J. Bents; Collin Powell; Joshua P. French; D. Rebecca Prevots; Rachel A. Mercaldo (Science of The Total Environment, 2025)

A “hazard model” using risk-weighted surveillance for first detection of chronic wasting disease - Krysten L. Schuler; Nicholas A. Hollingshead; Steven Heerkens; James D. Kelly; Jeremy E. Hurst; Rachel C. Abbott; Brenda J. Hanley; Eireann Collins; Kevin P. Hynes (Preventive Veterinary Medicine, 2025)

The influence of biochar pyrolysis temperature on anaerobic digestion of chicken litter in a leach bed coupled to a biochar filter - Ben A. Collins; Cristian H. Birzer; Stephen P. Kidd; Tony Hall; Paul R. Medwell (Bioresource Technology Reports, 2025)

Enhancing Bone Scaffold Fabrication: A Comparative Study of Manual Casting and Automated 3D Bioprinting - Yasser Ahmed; Ali S. Alshami; Ashraf Al-Goraee; Collins P. Obeng; Rebecca Kennedy; Hesham Abdelaziz; Ryan Striker (Annals of Biomedical Engineering, 2025)
While fabrication of bone scaffolds is important for the development of tissue engineering, traditional techniques have typically been prone to either scaling or reproducibility issues. This paper highlights a strategy for automated 3D printing and bioprinting techniques that enhance precision and efficiency in the production of PLGA–HA scaffolds. We realized significant improvements in efficiency, reproducibility, and scalability through optimization of 3D printing parameters, improvement of material handling, and refinement of the fabrication process. Precise measurement consequently minimized material waste; the introduction of a mesh filter allowed for high-throughput experimentation without compromising the integrity of individual scaffolds, streamlining the workflow. Combining automated casting with state-of-the-art 3D bioprinting, our experimental methodology precisely applied the bioactive materials, reducing the processing time fivefold and enhancing precision. Besides, automated casting produced thicker, better-quality scaffolds averaging 0.02354 g, which is against 0.01169 g using the manual approach, effectively doubling the retention of the PLGA–HA coating on a PVA mold. Excellent cell viability and adhesion on automated scaffolds have been further underlined for application in tissue engineering during in vitro studies using multipotent mesenchymal stromal cells. Although conventional techniques, such as injection molding, are standard for large lots, 3D printing has advantages in scaffold fabrication regarding control over geometry and homogeneous material properties. Equally important, these characteristics are necessary to achieve repeatable and up-scaled experimental results.

Opportunities and Challenges for Assessing Critical Mineral Resources Potential Using Legacy Drilling Results, Cave Peak Porphyry Mo Deposit, Texas, USA - Collin P. Hoffman; J. Richard Kyle (Natural Resources Research, 2025)

The role of dominant species in community organization and aboveground production in semiarid grasslands - Timothy J. Ohlert; Alesia Hallmark; Jennifer A. Rudgers; Debra P. C. Peters; Scott L. Collins (Ecology, 2025)
Dominant species play a key role in plant communities, influencing the abundance and richness of subordinate species through competitive and facilitative interactions. However, generalizations about the effects of dominant plant species in grasslands can be difficult due to the many differences among communities, such as abiotic conditions and regional species pools. To overcome this issue, we conducted a dominant species removal experiment in two semiarid grassland communities at the Sevilleta National Wildlife Refuge in central New Mexico. These communities had different dominant species but similar abiotic conditions and regional species pools. We studied the effects of removing dominant species on community composition, diversity, and aboveground net primary production (ANPP) over a 23‐year period. Our results showed that dominant grasses suppressed both richness and abundance of subordinate species. In the Chihuahuan Desert grassland, the loss of Bouteloua eriopoda was only partially compensated for by subordinate species, while in the Great Plains grassland, the loss of Bouteloua gracilis was fully compensated for after 16 years. Despite increased species richness, removing dominant species reduced ANPP and resulted in a negative relationship between species richness and ANPP in both grasslands. These results have important implications for ecosystem management and conservation, highlighting the potential impact of losing dominant species on subordinate species and community dynamics.

Immune Response of Nile Tilapia ( Oreochromis niloticus ) Vaccinated With Diatom‐Based Oral Vaccines Against Piscine Francisellosis - Collin Meyer; Roshan P. Shrestha; Ruth Milston‐Clements; Sarah Gibson; Taylor I. Heckman; Zeinab Yazdi; Esteban Soto (Journal of Fish Diseases, 2025)
Piscine francisellosis is a highly infectious and economically significant disease caused by Francisella orientalis in tilapia ( Oreochromis spp.). There are currently no approved treatments or commercial vaccines for this disease in cultured fish. Injectable vaccines using diatoms as antigen expression vectors have demonstrated efficacy in tilapia models; however, no oral vaccine trials have been performed. We hypothesised that fusion proteins consisting of F. orientalis IglC and flagellin expressed in Thalassiosira pseudonana diatoms will act as self‐adjuvanting antigen delivery systems to confer a protective immune response against F. orientalis in tilapia when administered as top‐coated feed. Different treatments were immunised and subsequently provided with one or two boosters prior to challenge. Fish were challenged with virulent F. orientalis via immersion thirty days post initial immunisation. Tilapia immune response was assessed 24 h post‐challenge by quantifying il‐12, il‐10, ifn‐γ and tgf‐β gene expression in gills and internal organs. Morbidity and mortality were monitored for 21 days after challenge and bacterial load was assessed in survivors. Findings indicate significant changes in the expression of ifn‐γ and tgf‐β in immunised fish, but similar mortality rates and bacterial load across all exposed groups.

Effects of training paradigm on dogs’ (Canis familiaris) acquisition and generalization of odors when trained with multiple explosives classes - S.A. Kane; G.N. Cupp; B. Rogers; D. Copeland; C. Collins-Pisano; J. Davis-Miller; L. Lazarowski; P. Waggoner; E.O. Aviles-Rosa; J. Denapoli; P.A. Prada-Tiedemann; N.J. Hall (Applied Animal Behaviour Science, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

New Approach Methods (NAMs) for genotoxicity assessment of nano- and advanced materials; Advantages and challenges - Arno C. Gutleb; Sivakumar Murugadoss; Maciej Stępnik; Tanima SenGupta; Naouale El Yamani; Eleonora Marta Longhin; Ann-Karin Hardie Olsen; Ewelina Wyrzykowska; Karolina Jagiello; Beata Judzinska; Sebastien Cambier; Tatiana Honza; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Higher potential leaching of inorganic and organic additives from biodegradable compared to conventional agricultural plastic mulch film - Michaela K. Reay; Martine Graf; Madelyn Murphy; Gupeng Li; Changrong Yan; Mondira Bhattacharya; Henny Osbahr; Ji Ma; Wen Chengtao; Xiner Shi; Siyang Ren; Jixiao Cui; et al. (Journal of Hazardous Materials, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Extreme Drought Increases the Temporal Variability of Grassland Productivity by Suppressing Dominant Grasses - Wentao Luo; Naohiro I. Ishii; Taofeek O. Muraina; Lin Song; Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Samuel R. P. J. Ross; Takehiro Sasaki; Jennifer A. Rudgers; Melinda D. Smith; Alan K. Knapp; et al. (Ecology Letters, 2025)
Extreme droughts are intensifying, yet their impact on temporal variability of grassland functioning and its drivers remains poorly understood. We imposed a 6‐year extreme drought in two semiarid grasslands to explore how drought influences the temporal variability of ANPP and identify potential stabilising mechanisms. Drought decreased ANPP while increasing its temporal variability across grasslands. In the absence of drought, ANPP variability was strongly driven by the dominant plant species (i.e., mass‐ratio effects), as captured by community‐weighted traits and species stability. However, drought decreased the dominance of perennial grasses, providing opportunities for subordinate species to alter the stability of productivity through compensatory dynamics. Specifically, under drought, species asynchrony emerged as a more important correlate of ANPP variability than community‐weighted traits or species stability. Our findings suggest that in grasslands, prolonged, extreme droughts may decrease the relative contribution of mass‐ratio effects versus compensatory dynamics to productivity stability by reducing the influence of dominant species.

The effect of training paradigm on dogs’ (Canis familiaris) acquisition and generalization of smokeless powders - S.A. Kane; G.N. Cupp; M. Rangel; A. Medrano; J. Davis-Miller; C. Collins-Pisano; B. Rogers; D. Copeland; L. Lazarowski; P. Waggoner; E.O. Aviles-Rosa; P.A. Prada-Tiedemann; et al. (Applied Animal Behaviour Science, 2025)

Unveiling hidden connections using photogrammetry: Multi-scale relationships between benthic communities and rocky subtidal seascapes - Q. Ternon; F. Ysnel; A. Collin; P. Thiriet; M. Guillaume; V. Danet; E. Feunteun (Regional Studies in Marine Science, 2025)

Variations in stand structure, composition, and fuelbeds drive prescribed fire behavior during mountain longleaf pine restoration - Collin J. Anderson; Matthew P. Weand; Heather D. Alexander; Mario Bretfeld; Nicholas Green (Forest Ecology and Management, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Seagrass wasting disease prevalence and lesion area increase with invertebrate grazing across the northeastern Pacific - Lillian R. Aoki; Carmen J. Ritter; Deanna S. Beatty; Lia K. Domke; Ginny L. Eckert; Olivia J. Graham; Carla P. Gomes; Collin Gross; Timothy L. Hawthorne; Eliza Heery; Margot Hessing‐Lewis; Kevin Hovel; et al. (Ecology, 2025)
Disease is a key driver of community and ecosystem structure, especially when it strikes foundation species. In the widespread marine foundation species eelgrass ( Zostera marina ), outbreaks of wasting disease have caused large‐scale meadow collapse in the past, and the causative pathogen, Labyrinthula zosterae , is commonly found in meadows globally. Research to date has mainly focused on abiotic environmental drivers of seagrass wasting disease, but there is strong evidence from other systems that biotic interactions such as herbivory can facilitate plant diseases. How biotic interactions influence seagrass wasting disease in the field is unknown but is potentially important for understanding dynamics of this globally valuable and declining habitat. Here, we investigated links between epifaunal grazers and seagrass wasting disease using a latitudinal field study across 32 eelgrass meadows distributed from southeastern Alaska to southern California. From 2019 to 2021, we conducted annual surveys to assess eelgrass shoot density, morphology, epifauna community, and the prevalence and lesion area of wasting disease infections. We integrated field data with satellite measurements of sea surface temperature and used structural equation modeling to test the magnitude and direction of possible drivers of wasting disease. Our results show that grazing by small invertebrates was associated with a 29% increase in prevalence of wasting disease infections and that both the prevalence and lesion area of disease increased with total epifauna abundances. Furthermore, these relationships differed among taxa; disease levels increased with snail ( Lacuna spp.) and idoteid isopod abundances but were not related to abundance of ampithoid amphipods. This field study across 23° of latitude suggests a prominent role for invertebrate consumers in facilitating disease outbreaks with potentially large impacts on coastal seagrass ecosystems.

Dog swimming and ectoparasiticide water contamination in urban conservation areas: A case study on Hampstead Heath, London - Lauren E. Yoder; Melanie Egli; Alexandra K. Richardson; Adrian Brooker; Rosemary Perkins; C.M. Tilly Collins; Jacqueline M. Cardwell; Leon P. Barron; Jeff Waage (Science of The Total Environment, 2024)

A global systematic review of the cultural ecosystem services provided by wetlands - Kevin A. Wood; Lucy L. Jupe; Francisca C. Aguiar; Alexandra M. Collins; Scott J. Davidson; Will Freeman; Liam Kirkpatrick; Tatiana Lobato-de Magalhães; Emma McKinley; Ana Nuno; Jordi F. Pagès; Antonella Petruzzella; et al. (Ecosystem Services, 2024)

Diel movement patterns in nominally nocturnal coral reef fishes (Haemulidae and Lutjanidae): Intra vs. Interspecific variation - William P. Collins; David R. Bellwood; Renato A. Morais; Nathan J. Waltham; Alexandre C. Siqueira (Coral Reefs, 2024)
Movement of animals, habitat connectivity, and nutrient transport are key elements in the ecological functioning of coral reef ecosystems. However, most studies have focused on the diurnal component of these aspects; nocturnal patterns are less known. Our study aims to address this knowledge gap by assessing diel movement patterns in ecologically and commercially important nocturnal coral reef fishes. We evaluate 122-days of acoustic telemetry data from 4 nocturnal species in 2 coral reef fish families (Haemulidae and Lutjanidae) on the Great Barrier Reef. For all species, we found a clear division between daytime resting areas on the reef and a move towards off-reef areas at night. This was highlighted in the low number of detections at night and the high average transitions between receivers at twilight. Over our study period, average nocturnal space use area (minimum convex polygon) of Plectorhincus gibbosus was 328,089 m 2 , Plectorhincus lineatus 28,828 m 2 , and Lutjanus carponotatus 20,369 m 2 . However, results from a Principal Component Analysis revealed that space use, and movement, varied substantially within species; for 3 of the 4 species the main axis of variation correlated with individual-level behaviour. These large differences in individual space use patterns highlight the need for caution when using species averages when considering ecosystem functions. Overall, our preliminary observations provide a glimpse into the large spatial extent, potential habitat connectivity, and intra and interspecific variation in activity patterns among large nocturnal Indo-Pacific reef fishes. This highlights their potential importance in maintaining ecosystem links between coral reefs and adjacent habitats.

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

A Latitudinal Cline in the Taxonomic Structure of Eelgrass Epifaunal Communities is Associated With Plant Genetic Diversity - Collin P. Gross; J. Emmett Duffy; Kevin A. Hovel; Pamela L. Reynolds; Christoffer Boström; Katharyn E. Boyer; Mathieu Cusson; Johan Eklöf; Aschwin H. Engelen; Britas Klemens Eriksson; F. Joel Fodrie; John N. Griffin; et al. (Global Ecology and Biogeography, 2024)
Aim Biogenic structural complexity increases mobile animal richness and abundance at local, regional and global scales, yet animal taxa vary in their response to complexity. When these taxa also vary functionally, habitat structures favouring certain taxa may have consequences for ecosystem function. We characterised global patterns of epifaunal invertebrates in eelgrass ( Zostera marina ) beds that varied in structural and genetic composition. Location North America, Europe and Asia. Time Period 2014. Major Taxa Studied Peracarid crustaceans and gastropod molluscs. Methods We sampled epifaunal invertebrate communities in 49 eelgrass beds across 37° latitude in two ocean basins concurrently with measurements of eelgrass genetic diversity, structural complexity and other abiotic and biotic environmental variables. We examined how species richness, abundance and community composition varied with latitude and environmental predictors using a random forest approach. We also examined how functional trait composition varied along with community structure. Results Total species richness decreased with latitude, but this was accompanied by a taxonomic shift in dominance from peracarid crustaceans to gastropods, which exhibited different sets of functional traits. Greater eelgrass genetic diversity was strongly correlated with both richness and abundance of peracarids, but less so for gastropods. Main Conclusions Our results add to a growing body of literature that suggests genetic variation in plant traits influences their associated faunal assemblages via habitat structure. Because peracarids and gastropods exhibited distinct functional traits, our results suggest a tentative indirect link between broad‐scale variation in plant genetic diversity and ecosystem function.

A review of lithogeochemical dispersion haloes of LCT pegmatites, and their application to rare metal exploration, with special reference to lithium in an Australian context - M. T. Sweetapple; P. J. Vanstone; G. R. Lumpkin; P. L. F. Collins (Australian Journal of Earth Sciences, 2024)

Impacts of changing weather patterns on the dynamics of water pollutants in agricultural catchments: Insights from 11-year high temporal resolution data analysis - G. Ezzati; A.L. Collins; S. Pulley; J. Galloway; D. Hawtree; P. Mellander (Journal of Hydrology, 2024)

Using zircon and apatite chemistry to fingerprint porphyry Cu – Mo ± Au mineralization in the Delamerian Orogen, South Australia - Wei Hong; Adrian Fabris; Sarah Gilbert; Benjamin P. Wade; Alan S. Collins; Tom Wise; Anthony J. Reid (Mineralium Deposita, 2024)
To evaluate the fertility of porphyry mineralization in the Delamerian Orogen (South Australia), zircon and apatite from four prospects, including Anabama Hill, Netley Hill, Bendigo, and Colebatch, have been analyzed by LA-ICP-MS and electron microprobe. The zircon is characterized by heavy REEs enrichment relative to light REEs, high (Ce/Nd) N (1.3–45), and weak to moderate negative Eu/Eu* (0.2–0.78). The apatite has right-sloped REE patterns with variably negative to positive Eu anomalies. Low Mg (< 670 ppm) and Sr/Y ratios (< 5) in apatite likely illustrate fractional crystallization trends for the granitic melts in shallow crust. The Yb/Gb and Eu/Eu* in zircon reveal that intrusions at Anabama Hill, Netley Hill, and Bendigo underwent fractional crystallization controlled by amphibole (< 50–60%), garnet (< 15%), apatite (< 0.6%), and/or titanite (< 0.3%). These stocks have average f O 2 values reported relative to fayalite-magnetite-quartz buffer (ΔFMQ), from 0.7 ± 0.9 to 2.1 ± 0.4, ascribed to prolonged magmatic evolution or sulfur degassing during post-subduction processes. Our data imply that both Anabama and Bendigo complexes experienced prevalent (garnet-) amphibole crystallization from hydrous melts that have moderately high oxidation (ΔFMQ + 1 to + 3) and elevated sulfur-chlorine components (Anabama, 37 ± 9 to 134 ± 83 ppm S and 0.30 ± 0.24 to 0.64 ± 0.89 wt% Cl; Bendigo, 281 ± 178 to 909 ± 474 ppm S and 0.45 ± 0.47 to 3.01 ± 1.54 wt% Cl). These are crucial ingredients to form porphyry Cu–Mo ± Au ores with economic significance, which provides encouragement for mineral exploration in this orogen.

Using forty years of research to view Bahía Almirante on the Caribbean Coast of Panama as an integrated social-ecological system - Rachel Collin; Anne E. Adelson; Andrew H. Altieri; Kasey E. Clark; Kristen Davis; Sarah N. Giddings; Samuel Kastner; Leon Mach; Geno Pawlak; Sofie Sjögersten; Mark Torres; Cinda P. Scott (Estuarine, Coastal and Shelf Science, 2024)

Eight weeks of high-intensity interval training versus stretching do not change the psychoneuroendocrine response to a social stress test in emotionally impulsive humans - F. Javelle; W. Bloch; U. Borges; T. Burberg; B. Collins; N. Gunasekara; T. J. Hosang; T. Jacobsen; S. Laborde; A. Löw; A. Schenk; M. L. Schlagheck; et al. (European Journal of Applied Physiology, 2024)
Purpose Research supports physical activity as a method to heighten stress resistance and resilience through positive metabolic alterations mostly affecting the neuroendocrine system. High-intensity interval training (HIIT) has been proposed as a highly effective time-saving method to induce those changes. However, existing literature relies heavily on cross-sectional analyses, with few randomised controlled trials highlighting the necessity for more exercise interventions. Thus, this study aims to investigate the effects of HIIT versus an active control group on the stress response to an acute psychosocial stressor in emotionally impulsive humans (suggested as being strong stress responders). Methods The study protocol was registered online (DRKS00016589) before data collection. Sedentary, emotionally impulsive adults (30.69 ± 8.20 y) were recruited for a supervised intervention of 8 weeks and randomly allocated to either a HIIT ( n = 25) or a stretching group ( n = 19, acting as active controls). Participants were submitted to a test battery, including saliva samples, questionnaires (self-efficacy- and perceived stress-related), visual analogue scales (physical exercise- and stress-related), and resting electroencephalography and electrocardiography assessing their reaction to an acute psychological stressor (Trier Social Stress Test) before and after the exercise intervention. Results HIIT increased aerobic fitness in all participants, whereas stretching did not. Participants from the HIIT group reported perceiving exercising more intensively than those from the active control group ( ƞ p 2 = 0.108, p = 0.038). No further group differences were detected. Both interventions largely increased levels of joy post-TSST ( ƞ p 2 = 0.209, p = 0.003) whilst decreasing tension ( ƞ p 2 = 0.262, p < 0.001) and worries ( ƞ p 2 = 0.113, p = 0.037). Finally, both interventions largely increased perceived levels of general self-efficacy ( ƞ p 2 = 0.120, p = 0.029). Conclusion This study suggests that 8 weeks of HIIT does not change the psychoneuroendocrine response to an acute psychological stress test compared to an active control group in emotionally impulsive humans. Further replications of supervised exercise studies highly powered with active and passive controls are warranted.

Exchange experiments for chlorine and bromine partitioning in scapolite at variable fluid salinities, pressures, and temperatures: implications for tracing crustal fluid sources via Cl/Br ratios in scapolite - Johannes Hammerli; David M. Jenkins; David P. Collins (Contributions to Mineralogy and Petrology, 2024)

Comparison of Kinematics for Head Impacts Initiated by Helmets and Shoulder Pads Among High School American Football Athletes - Aaron M. Sinnott; Christy L. Collins; Adrian J. Boltz; Hannah J. Robison; Hari Pinapaka; Jason P. Mihalik (Annals of Biomedical Engineering, 2024)

Padded Helmet Shell Covers in American Football: A Comprehensive Laboratory Evaluation with Preliminary On-Field Findings - Nicholas J. Cecchi; Ashlyn A. Callan; Landon P. Watson; Yuzhe Liu; Xianghao Zhan; Ramanand V. Vegesna; Collin Pang; Enora Le Flao; Gerald A. Grant; Michael M. Zeineh; David B. Camarillo (Annals of Biomedical Engineering, 2024)

Long‐Term Alpine Plant Responses to Global Change Drivers Depend on Functional Traits - Jonathan J. Henn; Kurt E. Anderson; Laurel M. Brigham; Clifton P. Bueno de Mesquita; Courtney G. Collins; Sarah C. Elmendorf; Matthew D. Green; Jared D. Huxley; Nicole E. Rafferty; Annika Rose‐Person; Marko J. Spasojevic (Ecology Letters, 2024)
Forecasting plant responses under global change is a critical but challenging endeavour. Despite seemingly idiosyncratic responses of species to global change, greater generalisation of ‘winners’ and ‘losers’ may emerge from considering how species functional traits influence responses and how these responses scale to the community level. Here, we synthesised six long‐term global change experiments combined with locally measured functional traits. We quantified the change in abundance and probability of establishment through time for 70 alpine plant species and then assessed if leaf and stature traits were predictive of species and community responses across nitrogen addition, snow addition and warming treatments. Overall, we found that plants with more resource‐acquisitive trait strategies increased in abundance but each global change factor was related to different functional strategies. Nitrogen addition favoured species with lower leaf nitrogen, snow addition favoured species with cheaply constructed leaves and warming showed few consistent trends. Community‐weighted mean changes in trait values in response to nitrogen addition, snow addition and warming were often different from species‐specific trait effects on abundance and establishment, reflecting in part the responses and traits of dominant species. Together, these results highlight that the effects of traits can differ by scale and response of interest.

Beneficial ‘inefficiencies’ of western ranching: Flood-irrigated hay production sustains wetland systems by mimicking historic hydrologic processes - J. Patrick Donnelly; Kelsey Jensco; John S. Kimball; Johnnie N. Moore; David Ketchum; Daniel P. Collins; David E. Naugle (Agriculture, Ecosystems & Environment, 2024)

Population dynamics of the Lyme disease bacterium, Borrelia burgdorferi , during rapid range expansion in New York State - Zachary J. Oppler; Melissa A. Prusinski; Kayleigh R. O'Keeffe; Patrick Pearson; Stephen M. Rich; Richard C. Falco; Vanessa Vinci; Collin O'Connor; Jamie Haight; P. Bryon Backenson; Dustin Brisson (Molecular Ecology, 2024)
Recent changes in climate and human land‐use have resulted in alterations of the geographic range of many species, including human pathogens. Geographic range expansion and population growth of human pathogens increase human disease risk. Relatively little empirical work has investigated the impact of range changes on within‐population variability, a contributor to both colonization success and adaptive potential, during the precise time in which populations are colonized. This is likely due to the difficulties of collecting appropriate natural samples during the dynamic phase of migration and colonization. We systematically collected blacklegged ticks ( Ixodes scapularis ) across New York State (NY), USA, between 2006 and 2019, a time period coinciding with a rapid range expansion of ticks and their associated pathogens including Borrelia burgdorferi , the etiological agent of Lyme disease. These samples provide a unique opportunity to investigate the population dynamics of human pathogens as they expand into novel territory. We observed that founder effects were short‐lived, as gene flow from long‐established populations brought almost all B. burgdorferi lineages to newly colonized populations within just a few years of colonization. By 7 years post‐colonization, B. burgdorferi lineage frequency distributions were indistinguishable from long‐established sites, indicating that local B. burgdorferi populations experience similar selective pressures despite geographic separation. The B. burgdorferi lineage dynamics elucidate the processes underlying the range expansion and demonstrate that migration into, and selection within, newly colonized sites operate on different time scales.

Morphology and metabolic traits related to swimming performance in Australasian snapper ( Chrysophrys auratus ) selected for fast growth - Leonardo J. Magnoni; Selwyn P. Collins; Matthew J. Wylie; Suzanne E. Black; Maren Wellenreuther (Journal of Fish Biology, 2024)
Changes in body shape are linked to swimming performance and become relevant for selective breeding programmes in cultured finfish. We studied how the selection for fast growth could affect phenotypes by investigating the relationship between swimming performance and body shape. We also investigated how swimming might affect plasma metabolite concentrations. Critical swimming speed (U Crit ), body traits (e.g., BW, body weight; BL, body length; K, condition factor), and plasma lactate and glucose concentrations were evaluated in two cohorts of Australasian snapper ( Chrysophrys auratus ): one derived from wild broodstock (F 1 ), and the other selected for fast growth (F 4 ). U Crit tests ( n = 8) were applied in groups of 10 snapper of similar BW (71.7 g) and BL (14.6 cm). The absolute or relative U Crit values of both cohorts were similar (0.702 m⋅s −1 and 4.795 BL⋅s −1 , respectively), despite the F 4 cohort displaying a higher K. A positive correlation between K and absolute U Crit (Pearson's r = 0.414) was detected in the F 4 cohort, but not in the F 1 cohort, which may be linked to differences in body shape. A negative correlation between relative U Crit and body size (Pearson's r between −0.682 and −0.501), but no correlation between absolute U Crit and body size, was displayed in both cohorts. Plasma lactate and glucose concentrations were higher in the F 4 cohort at U Crit . Whether a longer selective breeding programme could result in more changes in body shape, potentially affecting swimming performance, should be explored, along with the potential outcomes of the differences in metabolic traits detected.

Extending trait dispersion across trophic levels: Predator assemblages act as top‐down filters on prey communities - Collin P. Gross; John J. Stachowicz (Ecology, 2024)
Studies of community assembly typically focus on the effects of abiotic environmental filters and stabilizing competition on functional trait dispersion within single trophic levels. Predation is a well‐known driver of community diversity and composition, yet the role of functionally diverse predator communities in filtering prey community traits has received less attention. We examined functionally diverse communities of predators (fishes) and prey (epifaunal crustaceans) in eelgrass ( Zostera marina ) beds in two northern California estuaries to evaluate the filtering effects of predator traits on community assembly and how filters acting on predators influence their ability to mediate prey community assembly. Fish traits related to bottom orientation were correlated with more clustered epifauna communities, and epifauna were generally overdispersed while fishes were clustered, suggesting prey may be pushed to disparate areas of trait space to avoid capture by benthic sit‐and‐wait predators. We also found correlations between the trait dispersions of predator and prey communities that strengthened after accounting for the effects of habitat filters on predator dispersion, suggesting that habitat filtering effects on predator species pools may hinder their ability to affect prey community assembly. Our results present compelling observational evidence that specific predator traits have measurable impacts on the community assembly of prey, inviting experimental tests of predator trait means on community assembly and explicit comparisons of how the relative effects of habitat filters and intraguild competition on predators impact their ability to affect prey community assembly. Integrating our understanding of traits at multiple trophic levels can help us better predict the impacts of community composition on food web dynamics as regional species pools shift with climate change and anthropogenic introductions.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Lunar Flashlight science ground and flight measurements and operations using a multi-band laser reflectometer - Barbara A. Cohen; Ryan R. Petersburg; Daniel R. Cremons; Patrick S. Russell; Paul O. Hayne; Benjamin T. Greenhagen; David A. Paige; Jose Martinez Camacho; Nathan Cheek; Mark T. Sullivan; Valeria Lopez Robles; Jessica Ban; et al. (Icarus, 2024)

Subchronic inhalation exposure to ultrafine particulate matter alters the intestinal microbiome in various mouse models - Candace Chang; Rajat Gupta; Farzaneh Sedighian; Allen Louie; David M. Gonzalez; Collin Le; Jae Min Cho; Seul-Ki Park; Jocelyn Castellanos; To-Wei Ting; Tien S. Dong; Nerea Arias-Jayo; et al. (Environmental Research, 2024)

Remote hideaways: first insights into the population sizes, habitat use and residency of manta rays at aggregation areas in Seychelles - Lauren R. Peel; Mark G. Meekan; Ryan Daly; Clare A. Keating; Shaun P. Collin; Josep Nogués; Guy M. W. Stevens (Marine Biology, 2024)
Understanding the aggregation and habitat use patterns of a species can aid the formulation and improved design of management strategies aiming to conserve vulnerable populations. We used photo-identification techniques and a novel remote underwater camera system to examine the population sizes, patterns of residency and habitat use of oceanic ( Mobula birostris ) and reef ( Mobula alfredi ) manta rays in Seychelles (5.42°S; 53.30°E) between July 2006 and December 2018. Sightings of M. birostris were infrequent ( n = 5), suggesting that if aggregation areas for this species exist, they occur outside of the boundary of our study. A total of 236 individual M. alfredi were identified across all surveys, 66.5% of which were sighted at D’Arros Island (Amirante Group) and 22.5% at St. François Atoll (Alphonse Group). Males and females were evenly represented within the identified population. M. alfredi visited a cleaning station at D’Arros Island less frequently during dawn and dusk than at midday, likely due to the adoption of a crepuscular foraging strategy. The remote and isolated nature of the Amirante and Alphonse Group aggregation areas, coupled with the lack of a targeted mobulid fishery in Seychelles, suggests that with appropriate regulations and monitoring, the marine protected areas gazetted within these two groups will benefit the conservation of M. alfredi in Seychelles.

Small coral reef fishes with large ecological footprints - William P. Collins; David R. Bellwood; Renato A. Morais (Coral Reefs, 2024)
Seascape connectivity can facilitate key ecosystem functions in complex ecosystems like coral reefs. Many reef fishes move across the seascape, bridging different ecosystems. However, their role in shaping important functions, such as biomass production and nutrient cycling, is still poorly understood. This study, therefore, assesses the extent of natural movements of cardinalfishes (Apogonidae), one of the major contributors to nocturnal fish biomass production with the potential for a major role in transferring energy and nutrients between sandy ecosystems and adjacent coral reefs. Consistent with previous work, showing their ability to move distances of 100 s to 1000 s of metres when displaced, we reveal that these small fishes undergo major voluntary nocturnal foraging forays extending up to at least 145 m from reef structures. Their estimated daily movement distances are at least 430 times greater than expected based solely on body size-home range expectations. Given their large travel distances and strong homing abilities, apogonids may provide a major conduit for material transfer between lagoonal soft sediment habitats and adjacent coral reefs. These results highlight the potential importance of apogonids in the cross-system or cross-habitat transport of energy and nutrients on coral reefs.

What inhabits the South Sandwich Islands deep-sea? Biodiversity and biogeography of bathyal communities using predators as biological samplers - José P. Queirós; José C. Xavier; José Abreu; Martin A. Collins; Mark Belchier; Philip R. Hollyman (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Habitat and dissolved organic carbon modulate variation in the biogeochemical drivers of mercury bioaccumulation in dragonfly larvae at the national scale - Sarah J. Nelson; James Willacker; Collin Eagles-Smith; Colleen Flanagan Pritz; Celia Y. Chen; Amanda Klemmer; David P. Krabbenhoft (Science of The Total Environment, 2024)

Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

Unburnt refugia support post-fire population recovery of a threatened arboreal marsupial, Leadbeater’s possum - Louise K. Durkin; Paul D. Moloney; Jemma K. Cripps; Jenny L. Nelson; Phoebe V. Macak; Michael P. Scroggie; Luke Collins; Luke D. Emerson; Jamie Molloy; Lindy F. Lumsden (Forest Ecology and Management, 2024)

Postfire hydrologic response along the Central California (USA) coast: insights for the emergency assessment of postfire debris-flow hazards - Matthew A. Thomas; Jason W. Kean; Scott W. McCoy; Donald N. Lindsay; Jaime Kostelnik; David B. Cavagnaro; Francis K. Rengers; Amy E. East; Jonathan Y. Schwartz; Douglas P. Smith; Brian D. Collins (Landslides, 2023)
The steep, tectonically active terrain along the Central California (USA) coast is well known to produce deadly and destructive debris flows. However, the extent to which fire affects debris-flow susceptibility in this region is an open question. We documented the occurrence of postfire debris floods and flows following the landfall of a storm that delivered intense rainfall across multiple burn areas. We used this inventory to evaluate the predictive performance of the US Geological Survey M1 likelihood model, a tool that presently underlies the emergency assessment of postfire debris-flow hazards in the western USA. To test model performance, we used the threat score skill statistic and found that the rainfall thresholds estimated by the M1 model for the Central California coast performed similarly to training (Southern California) and testing (Intermountain West) data associated with the original model calibration. Model performance decreased when differentiating between “minor” and “major” postfire hydrologic response types, which weigh effects on human life and infrastructure. Our results underscore that the problem of false positives is a major challenge for developing accurate rainfall thresholds for the occurrence of postfire debris flows. As wildfire activity increases throughout the western USA, so too will the demand for the assessment of postfire debris-flow hazards. We conclude that additional collection of field-verified inventories of postfire hydrologic response will be critical to prioritize which model variables may be suitable candidates for regional calibration or replacement.

Fly ash degree of reaction in hypersaline NaCl and CaCl2 brines: Effects of calcium-based additives - Marie Collin; Yu Song; Dale P. Prentice; Ross A. Arnold; Kirk Ellison; Dante A. Simonetti; Mathieu Bauchy; Gaurav N. Sant (Waste Management, 2023)

Bio-physical determinants of sediment accumulation on an offshore coral reef: A snapshot study - Sterling B. Tebbett; Jodie A. Schlaefer; Casey L. Bowden; William P. Collins; Christopher R. Hemingson; Scott D. Ling; Juliano Morais; Renato A. Morais; Alexandre C. Siqueira; Robert P. Streit; Sam Swan; David R. Bellwood (Science of The Total Environment, 2023)

The influence of biochar position in a leach bed system anaerobically digesting chicken litter - Ben A. Collins; Cristian H. Birzer; Stephen P. Kidd; Tony Hall; Paul R. Medwell (Journal of Environmental Management, 2023)

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Understanding drivers of mercury in lake trout (Salvelinus namaycush), a top-predator fish in southwest Alaska's parklands - Krista K. Bartz; Michael P. Hannam; Tammy L. Wilson; Ryan F. Lepak; Jacob M. Ogorek; Daniel B. Young; Collin A. Eagles-Smith; David P. Krabbenhoft (Environmental Pollution, 2023)

Characterisation of the trans-membrane nucleoporins GP210 and NDC1 in Arabidopsis thaliana - Patrick P. Collins; Ronan C. Broad; Krithika Yogeeswaran; Arvind Varsani; Anthony M. Poole; David A. Collings (Plant Science, 2023)

Corrigendum to “A home for all within planetary boundaries: Pathways for meeting England's housing needs without transgressing national climate and biodiversity goals” [Ecological Economics Vol 201 (2022) 107562] - Sophus O.S.E. zu Ermgassen; Michal P. Drewniok; Joseph W. Bull; Christine M. Corlet Walker; Mattia Mancini; Josh Ryan-Collins; André Cabrera Serrenho (Ecological Economics, 2023)

Comparison of Mann–Kendall and Şen’s innovative trend method for climatic parameters over Nigeria’s climatic zones - Emmanuel P. Agbo; Ugochukwu Nkajoe; Collins O. Edet (Climate Dynamics, 2023)

The influence of short-term temporal variability on the efficacy of dragonfly larvae as mercury biosentinels - James J. Willacker; Collin A. Eagles-Smith; Sarah J. Nelson; Colleen M. Flanagan Pritz; David P. Krabbenhoft (Science of The Total Environment, 2023)

A menu of measures to manage trade-related plant pest risks, and a review of methods for demonstrating measure efficacy - Rieks D. van Klinken; Lloyd Kingham; Matthew P. Hill; Kerry Collins (Biological Invasions, 2023)
Ever-increasing global trade is one of the most important introduction pathways for plant pests. A diverse range of risk-reducing measures can be applied depending on the pest, the commodity and the import requirements. We used a review of over 1,800 risk reduction measures to extend a risk framework and menu of measures, previously developed for horticulture, to be applied to any commodity. We also reviewed how the efficacy of risk reduction measures is demonstrated, and assessed the maturity of the supporting science. We identified 39 unique risk reduction measures that were classified according to how they reduce risk. These were grouped under ten measure categories and four risk reduction objectives (minimising exposure to pest, minimising vulnerability of the commodity, reducing infestation rate and reducing establishment risk). These could then be applied against one or more consignment stages (production, post-production and post-border). Measures covered both commercial activities that reduce risk and may contribute to pest risk assessment, and regulated measures mandated to address unrestricted risk. Almost 90% of citations included measures that minimised exposure to pests or reduced infestation. Some measures were rarely reported, and some commodity classes had few measures associated with them, suggesting that available measures are being underutilised. Clear guidance was apparent for demonstrating efficacy of some measures (e.g., kill treatments), but lacking for many others. Compiling a ‘menu of risk reduction measures’ according to how they reduce risk, accompanied by clear guidelines for demonstrating efficacy, provides a robust basis for agreement between jurisdictions, and the further development, refinement and communication of efforts to both assess and manage the risk of global, trade-related pest movement. Agreement on how efficacy can be demonstrated for less utilised measures identified in this study will contribute to the further development of risk-based trade.

Bibliometric investigation of the integration of animal personality in conservation contexts - Sydney M. Collins; Jack G. Hendrix; Quinn M. R. Webber; Sean P. Boyle; Katrien A. Kingdon; Robert J. Blackmore; Kyle J. N. d'Entremont; Jennifer Hogg; Juan P. Ibáñez; Joanie L. Kennah; Jessika Lamarre; Miguel Mejías; et al. (Conservation Biology, 2023)
Consistent individual differences in behavior, commonly termed animal personality , are a widespread phenomenon across taxa that have important consequences for fitness, natural selection, and trophic interactions. Animal personality research may prove useful in several conservation contexts, but which contexts remains to be determined. We conducted a structured literature review of 654 studies identified by combining search terms for animal personality and various conservation subfields. We scored the relevance of personality and conservation issues for each study to identify which studies meaningfully integrated the 2 fields as opposed to surface‐level connections or vague allusions. We found a taxonomic bias toward mammals (29% of all studies). Very few amphibian or reptile studies applied personality research to conservation issues (6% each). Climate change (21%), invasive species (15%), and captive breeding and reintroduction (13%) were the most abundant conservation subfields that occurred in our search, though a substantial proportion of these papers weakly integrated conservation and animal personality (climate change 54%, invasive species 51%, captive breeding and reintroduction 40%). Based on our results, we recommend that researchers strive for consistent and broadly applicable terminology when describing consistent behavioral differences to minimize confusion and improve the searchability of research. We identify several gaps in the literature that appear to be promising and fruitful avenues for future research, such as disease transmission as a function of sociability or exploration as a driver of space use in protected areas. Practitioners can begin informing future conservation efforts with knowledge gained from animal personality research.

Suitability of remediated heat-treated soil in concrete applications - Andras Fehervari; Alastair J.N. MacLeod; Chathuranga Gallage; Frank Collins; Damien Callahan; Will P. Gates (Journal of Environmental Management, 2023)

Recommendations for advancing test protocols examining the photo-induced toxicity of petroleum and polycyclic aromatic compounds - Matthew M. Alloy; Bryson E. Finch; Collin P. Ward; Aaron D. Redman; Adriana C. Bejarano; Mace G. Barron (Aquatic Toxicology, 2023)

Detection of SARS-CoV-2 RNA in wastewater and comparison to COVID-19 cases in two sewersheds, North Carolina, USA - Alyssa M. Grube; Collin K. Coleman; Connor D. LaMontagne; Megan E. Miller; Nikhil P. Kothegal; David A. Holcomb; A. Denene Blackwood; Thomas J. Clerkin; Marc L. Serre; Lawrence S. Engel; Virginia T. Guidry; Rachel T. Noble; et al. (Science of The Total Environment, 2023)

Long-term aircraft noise exposure and risk of hypertension in postmenopausal women - Daniel D. Nguyen; Eric A. Whitsel; Gregory A. Wellenius; Jonathan I. Levy; Jessica H. Leibler; Stephanie T. Grady; James D. Stewart; Matthew P. Fox; Jason M. Collins; Melissa N. Eliot; Andrew Malwitz; JoAnn E. Manson; et al. (Environmental Research, 2023)

Coupling a biochar filter to a leach bed reactor for anaerobic digestion of chicken litter - Ben A. Collins; Cristian H. Birzer; Stephen P. Kidd; Tony Hall; Paul R. Medwell (Bioresource Technology Reports, 2023)

Understanding heterogeneity of responses to, and optimizing clinical efficacy of, exercise training in older adults: NIH NIA Workshop summary - Melissa L. Erickson; Jacob M. Allen; Daniel P. Beavers; Linda M. Collins; Karina W. Davidson; Kirk I. Erickson; Karyn A. Esser; Matthijs K. C. Hesselink; Kerrie L. Moreau; Eric B. Laber; Charlotte A. Peterson; Courtney M. Peterson; et al. (GeroScience, 2023)
Exercise is a cornerstone of preventive medicine and a promising strategy to intervene on the biology of aging. Variation in the response to exercise is a widely accepted concept that dates back to the 1980s with classic genetic studies identifying sequence variations as modifiers of the VO 2 max response to training. Since that time, the literature of exercise response variance has been populated with retrospective analyses of existing datasets that are limited by a lack of statistical power from technical error of the measurements and small sample sizes, as well as diffuse outcomes, very few of which have included older adults. Prospective studies that are appropriately designed to interrogate exercise response variation in key outcomes identified a priori and inclusive of individuals over the age of 70 are long overdue. Understanding the underlying intrinsic (e.g., genetics and epigenetics) and extrinsic (e.g., medication use, diet, chronic disease) factors that determine robust versus poor responses to various exercise factors will be used to improve exercise prescription to target the pillars of aging and optimize the clinical efficacy of exercise training in older adults. This review summarizes the proceedings of the NIA-sponsored workshop entitled, “Understanding Heterogeneity of Responses to, and Optimizing Clinical Efficacy of, Exercise Training in Older Adults” and highlights the importance and current state of exercise response variation research, particularly in older adults, prevailing challenges, and future directions.

Crown Lifting of Low-Density Loblolly Pine ( Pinus taeda ) Plantations on Nonindustrial Private Forest Lands - Darcey Collins; Joshua J Granger; Stephen Dicke; Krishna P Poudel; Adam Polinko; John L Willis (Forest Science, 2023)
Pruning or the physical removal of lower branches, in combination with wider tree spacing, offers an alternative management scheme for small nonindustrial private forest landowners in areas lacking markets for small diameter wood. A 5-year-old loblolly pine (Pinus taeda) plantation was thinned to 495 trees/ha (200 trees/ac). Four crown-lifting treatments of 35%, 40%, 45%, and 50% live crown ratio (LCR) were then implemented. An additional unmanaged plot was established in an unthinned, unpruned area. Two replications were established for all pruning treatments. The target LCR was maintained throughout the study with the additional crown-lifting activities in 2003, 2004, and 2008. At age 8, the average diameter of the unmanaged plot was 13.5 cm (5.3 in), and the diameter of the 50% LCR treatment, which had the greatest diameter growth of all the treatments, was 20.8 cm (8.2 in). The highest mortality rate (22%) was observed in the unmanaged plot, but it was not significantly greater than the other treatments. Low density plantings maintained with pruning could allow small nonindustrial private landowners to obtain a high value sawtimber product while eliminating the need for thinning practices commonly used in traditional pine plantation management.

A framework for detection and attribution of regional precipitation change: Application to the United States historical record - Mark D. Risser; William D. Collins; Michael F. Wehner; Travis A. O’Brien; Christopher J. Paciorek; John P. O’Brien; Christina M. Patricola-DiRosario; Huanping Huang; Paul A. Ullrich; Burlen Loring (Climate Dynamics, 2023)
Despite the emerging influence of anthropogenic climate change on the global water cycle, at regional scales the combination of observational uncertainty, large internal variability, and modeling uncertainty undermine robust statements regarding the human influence on precipitation. Here, we use output from global climate models in a perfect-data sense to develop a framework for conducting regional detection and attribution (D&A) for precipitation, starting with the contiguous United States (CONUS) where observational uncertainty is lower than in other regions. Our unified approach can simultaneously detect systematic trends in mean and extreme precipitation, attribute trends to anthropogenic forcings, compute the effects of forcings as a function of time, and map the effects of individual forcings. Model output is used to conduct a set of tests that yield a parsimonious representation for characterizing seasonal precipitation over the CONUS for the historical record (1900 to present day), which ensures our D&A is insensitive to structural uncertainty. Our framework is developed using synthetic data in a Pearl-causal perspective wherein causality can be identified using intervention-based simulations. While the hypothesis-based framework and accompanying generalized D&A formula we develop should be widely applicable, we include a strong caution that the hypothesis-guided simplification of the formula for the historical climatic record of CONUS as described in this paper will likely fail to hold in other geographic regions and under future warming.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Plant defense synergies and antagonisms affect performance of specialist herbivores of common milkweed - Collin B. Edwards; Stephen P. Ellner; Anurag A. Agrawal (Ecology, 2023)
As a general rule, plants defend against herbivores with multiple traits. The defense synergy hypothesis posits that some traits are more effective when co‐expressed with others compared to their independent efficacy. However, this hypothesis has rarely been tested outside of phytochemical mixtures, and seldom under field conditions. We tested for synergies between multiple defense traits of common milkweed ( Asclepias syriaca ) by assaying the performance of two specialist chewing herbivores on plants in natural populations. We employed regression and a novel application of random forests to identify synergies and antagonisms between defense traits. We found the first direct empirical evidence for two previously hypothesized defense synergies in milkweed (latex by secondary metabolites, latex by trichomes) and identified numerous other potential synergies and antagonisms. Our strongest evidence for a defense synergy was between leaf mass per area and low nitrogen content; given that these “leaf economic” traits typically covary in milkweed, a defense synergy could reinforce their co‐expression. We report that each of the plant defense traits showed context‐dependent effects on herbivores, and increased trait expression could well be beneficial to herbivores for some ranges of observed expression. The novel methods and findings presented here complement more mechanistic approaches to the study of plant defense diversity and provide some of the best evidence to date that multiple classes of plant defense synergize in their impact on insects. Plant defense synergies against highly specialized herbivores, as shown here, are consistent with ongoing reciprocal evolution between these antagonists.

Daily roadkill monitoring and long-term population census reveal female-biased mortality for a small mammal along a wildland-urban interface - Katherine Burgstahler; Jessica Isidro; Dirk H. Van Vuren; Amy C. Collins; Jaclyn R. Aliperti; Caitlin P. Wells (Biological Conservation, 2023)

The impact of varying dextran oxidation levels on the inhibitory activity of a bacteriocin loaded injectable hydrogel - James Flynn; Mario Culebras; Maurice N. Collins; Sarah P. Hudson (Drug Delivery and Translational Research, 2023)
In the design of injectable antimicrobial dextran-alginate hydrogels, the impact of dextran oxidation and its subsequent changes in molecular weight and the incorporation of glycol chitosan on (i) gel mechanical strength and (ii) the inhibitory profile of an encapsulated bacteriocin, nisin A, are explored. As the degree of oxidation increases, the weight average molecular mass of the dextran decreases, resulting in a reduction in elastic modulus of the gels made. Upon encapsulation of the bacteriocin nisin into the gels, varying the dextran mass/oxidation level allowed the antimicrobial activity against S. aureus to be controlled. Gels made with a higher molecular weight (less oxidised) dextran show a higher initial degree of inhibition while those made with a lower molecular weight (more oxidised) dextran exhibit a more sustained inhibition. Incorporating glycol chitosan into gels composed of dextran with higher masses significantly increased their storage modulus and the gels’ initial degree of inhibition. Graphical abstract

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Meteorological analysis of the relationship between climatic parameters: understanding the dynamics of the troposphere - Emmanuel P. Agbo; Collins O. Edet (Theoretical and Applied Climatology, 2022)

Assessment of Cavitation Intensity in Accelerating Syringes of Spring-Driven Autoinjectors - Javad Eshraghi; Jean-Christophe Veilleux; Galen Shi; David Collins; Arezoo M. Ardekani; Pavlos P. Vlachos (Pharmaceutical Research, 2022)

The auditory system of cartilaginous fishes - Lucille Chapuis; Shaun P. Collin (Reviews in Fish Biology and Fisheries, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Projected changes in the n ear‐future mean climate and extreme climate events in northeast Thailand - Dibesh Khadka; Mukand S. Babel; Matthew Collins; Sangam Shrestha; Salvatore G. P. Virdis; Albert S. Chen (International Journal of Climatology, 2022)
This study provides an assessment of changes in mean and extreme climate in northeast Thailand, focusing on the near‐future period (2021–2050). Spatiotemporal changes in climate extremes and return values are investigated compared to 1981–2010. Climate model‐related uncertainties are quantified using 14 models from the Coupled Model Intercomparison Project phase 5 (CMIP5) and 8 models from phase 6 (CMIP6). CMIP6 models have a higher sensitivity to external forcings as the CMIP6 ensemble suggests an increase in maximum and minimum temperatures by 1.45°C (0.8–1.9°C) and 1.54°C (1.1–1.9°C) under the high emission scenario, which is greater than by CMIP5 ensemble: 1.10°C (0.5–1.7°C) and 1.13°C (0.7–1.6°C), respectively. No significant changes in annual rainfall are projected, although it will be temporally more uneven with decreases (6–11%) during the pre‐rainy season (March–May) and increases (2–8%) during the rainy season (June–October). The bootstrap analysis technique shows the inter‐model uncertainties for rainfall projections in CMIP6 have reduced by 40% compared to CMIP5. The annual number of hot days will increase more than twofold and warm nights, more than threefold. Near‐future will experience an increase in the rainfall intensity, a decrease in the number of rainy days, and an increase in the 20‐year return values of annual maximum 1‐day rainfall and consecutive 5‐days rainfall (>30%). In addition, the rainy season will be shortened in the future as onset and retreat are delayed, which may have implications in agricultural activities in the basin since cultivation is primarily rainfed. These findings suggest that anthropogenic activities will significantly amplify the climate extremes. The study results will be useful for managing climate‐related risks and developing adaptation measures to improve resilience towards potential climate hazards.

The Status of Marine Megafauna Research in Macaronesia: A Systematic Review - Ashlie J. McIvor; Collin T. Williams; Filipe Alves; Ana Dinis; Miguel P. Pais; João Canning-Clode (Frontiers in Marine Science, 2022)
Marine megafauna serve valuable ecological and economical roles globally, yet, many species have experienced precipitous population declines. The significance of marine megafauna is particularly evident in Macaronesia, a complex of oceanic archipelagos in the Northeast Atlantic Ocean. Macaronesian islands provide important habitats for marine megafauna species, in turn supporting considerable regional economic activity (e.g., ecotourism and fisheries). Despite this, concerted efforts to manage marine megafauna throughout Macaronesia have been limited. This systematic review provides the first description of the trends in marine megafauna research in this unique insular ecosystem, to provide a better understanding of taxa-specific research needs and future directions for conservation. We identified and validated 408 peer-reviewed publications until 2021 following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. Literature was dominated by marine mammal research conducted in the northern archipelagos (Azores, Madeira, and Canary Islands) and marine turtle research conducted in Cabo Verde. Much less research focused on large-bodied fish, especially in Madeira and Canary Islands, leaving some of the most vulnerable species regionally data deficient. Research across scientific disciplines focused more on biological studies than management and policy, and anthropogenic impacts were quantified more frequently on mammals or turtles and less on fishes. By identifying gaps in our knowledge of megafauna in relation to threats faced by these organisms, we offer taxa-specific recommendations for future research direction. Although, overall our results indicate that determining population level connectivity should be a major research priority among many marine megafauna species as this information is vital to numerous management strategies, including marine protected areas. In this review, we present a basis of understanding of the current work in Macaronesia, highlighting critical data gaps that are urgently needed to guide the next steps toward establishing conservation priorities for marine megafauna in the region.

Natural and anthropogenic impacts on the geochemical composition and metal speciation of fine sediment in a glacier-fed Canadian river basin - M. Stone; A. L. Collins; J. P. Laceby (Journal of Soils and Sediments, 2022)

Stratigraphic relationship between Rimrock Lake and Hay Lake playa sediments, Harney Basin, eastern Oregon, USA - Joe D. Collins; Mark W. Bowen; Thomas E. Gill; Richard P. Langford (Journal of Paleolimnology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Biogeochemical status of the Paleo-Pacific Ocean: clues from the early Cambrian of South Australia - P. A. Hall; D. M. McKirdy; G. P. Halverson; J. B. Jago; A. S. Collins (Australian Journal of Earth Sciences, 2021)

Changes in extreme events over Asia for present and future climate conditions based on a modelling analysis of atmospheric circulation anomalies - Ranjeet S. Sokhi; P. R. Tiwari; Joanna S. N. de Medeiros; Gerd A. Folberth; William J. Collins (Theoretical and Applied Climatology, 2021)

Pyrosilviculture Needed for Landscape Resilience of Dry Western United States Forests - M P North; R A York; B M Collins; M D Hurteau; G M Jones; E E Knapp; L Kobziar; H McCann; M D Meyer; S L Stephens; R E Tompkins; C L Tubbesing (Journal of Forestry, 2021)
A significant increase in treatment pace and scale is needed to restore dry western US forest resilience owing to increasingly frequent and severe wildfire and drought. We propose a pyrosilviculture approach to directly increase large-scale fire use and modify current thinning treatments to optimize future fire incorporation. Recommendations include leveraging wildfire’s “treatment” in areas burned at low and moderate severity with subsequent pyrosilviculture management, identifying managed wildfire zones, and facilitating and financing prescribed fire with “anchor,” “ecosystem asset,” and “revenue” focused thinning treatments. Pyrosilviculture would also expand prescribed-burn and managed-wildfire objectives to include reducing stand density, increasing forest heterogeneity, and selecting for tree species and phenotypes better adapted to changing climate and disturbance regimes. The potential benefits and limitations of this approach are discussed. Fire is inevitable in dry western US forests and pyrosilviculture focuses on proactively shifting more of that fire into managed large-scale burns needed to restore ecosystem resilience.

Biodiversity and biogeography of hydroids across marine ecoregions and provinces of southern South America and Antarctica - Thaís P. Miranda; Marina O. Fernandez; Gabriel N. Genzano; Álvaro L. Peña Cantero; Allen G. Collins; Antonio C. Marques (Polar Biology, 2021)

Letter in response to: circulating von Willebrand factor and high molecular weight multimers as markers of endothelial injury predict COVID-19 in-hospital mortality - P. Bhogal; G. Paul; G. Collins; O. Jaffer (Angiogenesis, 2021)

Novel ferrocenyl chalcone derivatives as antibacterial agents: is there a solution to the problem? - Elecia J. Henry; Charles Thomas Bennett; Michael Collins; John P. Cassella (Medicinal Chemistry Research, 2021)

Timing and order of different insecticide classes drive control of Drosophila suzukii; a modeling approach - Serhan Mermer; Ferdinand Pfab; Gabriella Tait; Rufus Isaacs; Philip D. Fanning; Steven Van Timmeren; Gregory M. Loeb; Stephen P. Hesler; Ashfaq A. Sial; Jamal H. Hunter; Harit Kaur Bal; Francis Drummond; et al. (Journal of Pest Science, 2021)

Understanding Persistent Non-compliance in a Remote, Large-Scale Marine Protected Area - Claire Collins; Ana Nuno; Annette Broderick; David J. Curnick; Asha de Vos; Thomas Franklin; David M. P. Jacoby; Chris Mees; James Moir-Clark; John Pearce; Tom B. Letessier (Frontiers in Marine Science, 2021)
Area coverage of large-scale marine protected areas (MPAs) (LSMPAs, > 100,000 km 2 ) is rapidly increasing globally. Their effectiveness largely depends on successful detection and management of non-compliance. However, for LSMPAs this can be difficult due to their large size, often remote locations and a lack of understanding of the social drivers of non-compliance. Taking a case-study approach, we review current knowledge of illegal fishing within the British Indian Ocean Territory (BIOT) LSMPA. Data stemming from enforcement reports (2010–20), and from fieldwork in fishing communities (2018–19) were combined to explore and characterise drivers of non-compliance. Enforcement data included vessel investigation reports ( n = 188), transcripts of arrests (20) and catch seizures (58). Fieldwork data included fisher interviews (95) and focus groups (12), conducted in two communities in Sri Lanka previously associated with non-compliance in BIOT LSMPA. From 2010 to 2020, there were 126 vessels suspected of non-compliance, 76% of which were Sri Lankan. The majority of non-compliant vessels targeted sharks (97%), catching an estimated 14,340 individuals during the study period. Sri Lankan vessels were primarily registered to one district (77%) and 85% operated from just two ports within the fieldwork sites. Social Network Analysis (SNA) showed that 66% of non-compliant vessels were linked by social ties, including sharing crew members, compared with only 34% of compliant vessels. Thematic analysis of qualitative data suggested that perceptions of higher populations of sharks and social ties between vessels may both be important drivers. We discuss our findings within a global context to identify potential solutions for LSMPA management.

Quantifying the influence of natural climate variability on in situ measurements of seasonal total and extreme daily precipitation - Mark D. Risser; Michael F. Wehner; John P. O’Brien; Christina M. Patricola-DiRosario; Travis A. O’Brien; William D. Collins; Christopher J. Paciorek; Huanping Huang (Climate Dynamics, 2021)
While various studies explore the relationship between individual sources of climate variability and extreme precipitation, there is a need for improved understanding of how these physical phenomena simultaneously influence precipitation in the observational record across the contiguous United States. In this work, we introduce a single framework for characterizing the historical signal (anthropogenic forcing) and noise (natural variability) in seasonal mean and extreme precipitation. An important aspect of our analysis is that we simultaneously isolate the individual effects of seven modes of variability while explicitly controlling for joint inter-mode relationships. Our method utilizes a spatial statistical component that uses in situ measurements to resolve relationships to their native scales; furthermore, we use a data-driven procedure to robustly determine statistical significance. In Part I of this work we focus on natural climate variability: detection is mostly limited to DJF and SON for the modes of variability considered, with the El Niño/Southern Oscillation, the Pacific–North American pattern, and the North Atlantic Oscillation exhibiting the largest influence. Across all climate indices considered, the signals are larger and can be detected more clearly for seasonal total versus extreme precipitation. We are able to detect at least some significant relationships in all seasons in spite of extremely large (> 95%) background variability in both mean and extreme precipitation. Furthermore, we specifically quantify how the spatial aspect of our analysis reduces uncertainty and increases detection of statistical significance while also discovering results that quantify the complex interconnected relationships between climate drivers and seasonal precipitation.

Effects of Chlorpyrifos Over Reproductive Traits of Three Sympatric Freshwater Crustaceans - C. L. Negro; J. F. Estrubia; F. Rivera; P. Collins (Bulletin of Environmental Contamination and Toxicology, 2021)

The taxonomic identity and distribution of the eel cod Muraenolepis (Gadiformes: Muraenolepididae) around South Georgia and the South Sandwich Islands - E. Fitzcharles; P. R. Hollyman; W. P. Goodall-Copestake; J. S. Maclaine; M. A. Collins (Polar Biology, 2021)

Does cattle and sheep grazing under best management significantly elevate sediment losses? Evidence from the North Wyke Farm Platform, UK - S. Pulley; L. M. Cardenas; P. Grau; S. Mullan; M. J. Rivero; A. L. Collins (Journal of Soils and Sediments, 2021)
Purpose Intensive livestock grazing has been associated with an increased risk of soil erosion and concomitant negative impacts on the ecological status of watercourses. Whilst various mitigation options are promoted for reducing livestock impacts, there is a paucity of data on the relationship between stocking rates and quantified sediment losses. This evidence gap means there is uncertainty regarding the cost–benefit of policy preferred best management. Methods Sediment yields from 15 hydrologically isolated field scale catchments on a heavily instrumented ruminant livestock farm in the south west UK were investigated over ~ 26 months spread across 6 years. Sediment yields were compared to cattle and sheep stocking rates on long-term, winter (November–April), and monthly timescales. The impacts of livestock on soil vegetation cover and bulk density were also examined. Cattle were tracked using GPS collars to determine how grazing related to soil damage. Results No observable impact of livestock stocking rates of 0.15–1.00 UK livestock units (LU) ha −1 for sheep, and 0–0.77 LU ha −1 for cattle on sediment yields was observed at any of the three timescales. Cattle preferentially spent time close to specific fences where soils were visually damaged. However, there was no indication that livestock have a significant effect on soil bulk density on a field scale. Livestock were housed indoors during winters when most rainfall occurs, and best management practices were used which when combined with low erodibility clayey soils likely limited sediment losses. Conclusion A combination of clayey soils and soil trampling in only a small proportion of the field areas lead to little impact from grazing livestock. Within similar landscapes with best practice livestock grazing management, additional targeted measures to reduce erosion are unlikely to yield a significant cost-benefit.

Correction to: Assessing the Contribution of Sli to Self-Compatibility in North American Diploid Potato Germplasm Using KASP™ Markers - N. R. Kaiser; S. Jansky; J. J. Coombs; P. Collins; M. Alsahlany; D. S. Douches (American Journal of Potato Research, 2021)

Assessing the Contribution of Sli to Self-Compatibility in North American Diploid Potato Germplasm Using KASP™ Markers - N. R. Kaiser; S. Jansky; J. J. Coombs; P. Collins; M. Alsahlany; D. S. Douches (American Journal of Potato Research, 2021)

Whole Community Metatranscriptomes and Lipidomes Reveal Diverse Responses Among Antarctic Phytoplankton to Changing Ice Conditions - Jeff S. Bowman; Benjamin A. S. Van Mooy; Daniel P. Lowenstein; Helen F. Fredricks; Colleen M. Hansel; Rebecca Gast; James R. Collins; Nicole Couto; Hugh W. Ducklow (Frontiers in Marine Science, 2021)
The transition from winter to spring represents a major shift in the basal energy source for the Antarctic marine ecosystem from lipids and other sources of stored energy to sunlight. Because sea ice imposes a strong control on the transmission of sunlight into the water column during the polar spring, we hypothesized that the timing of the sea ice retreat influences the timing of the transition from stored energy to photosynthesis. To test the influence of sea ice on water column microbial energy utilization we took advantage of unique sea ice conditions in Arthur Harbor, an embayment near Palmer Station on the western Antarctic Peninsula, during the 2015 spring–summer seasonal transition. Over a 5-week period we sampled water from below land-fast sea ice, in the marginal ice zone at nearby Palmer Station B, and conducted an ice removal experiment with incubations of water collected below the land-fast ice. Whole-community metatranscriptomes were paired with lipidomics to better understand how lipid production and utilization was influenced by light conditions. We identified several different phytoplankton taxa that responded similarly to light by the number of genes up-regulated, and in the transcriptional complexity of this response. We applied a principal components analysis to these data to reduce their dimensionality, revealing that each of these taxa exhibited a strikingly different pattern of gene up-regulation. By correlating the changes in lipid concentration to the first principal component of log fold-change for each taxa we could make predictions about which taxa were associated with different changes in the community lipidome. We found that genes coding for the catabolism of triacylglycerol storage lipids were expressed early on in phytoplankton associated with a Fragilariopsis kerguelensis reference transcriptome. Phytoplankton associated with a Corethron pennatum reference transcriptome occupied an adjacent niche, responding favorably to higher light conditions than F. kerguelensis . Other diatom and dinoflagellate taxa had distinct transcriptional profiles and correlations to lipids, suggesting diverse ecological strategies during the polar winter–spring transition.

Analysis of the effects of meteorological parameters on radio refractivity, equivalent potential temperature and field strength via Mann-Kendall test - Emmanuel P. Agbo; Chris M. Ekpo; Collins O. Edet (Theoretical and Applied Climatology, 2021)

The Interface Motion and Hydrodynamic Shear of the Liquid Slosh in Syringes - Yuchen Zhang; Dingding Han; Zhongwang Dou; Jean-Christophe Veilleux; Galen H. Shi; David S. Collins; Pavlos P. Vlachos; Arezoo M. Ardekani (Pharmaceutical Research, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Volumetric analysis and morphological assessment of the ascending olfactory pathway in an elasmobranch and a teleost using diceCT - Victoria Camilieri-Asch; Jeremy A. Shaw; Kara E. Yopak; Lucille Chapuis; Julian C. Partridge; Shaun P. Collin (Brain Structure and Function, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Experimental metatranscriptomics reveals the costs and benefits of dissolved organic matter photo‐alteration for freshwater microbes - Sarah G. Nalven; Collin P. Ward; Jérôme P. Payet; Rose M. Cory; George W. Kling; Thomas J. Sharpton; Christopher M. Sullivan; Byron C. Crump (Environmental Microbiology, 2020)
Summary Microbes and sunlight convert terrigenous dissolved organic matter (DOM) in surface waters to greenhouse gases. Prior studies show contrasting results about how biological and photochemical processes interact to contribute to the degradation of DOM. In this study, DOM leached from the organic layer of tundra soil was exposed to natural sunlight or kept in the dark, incubated in the dark with the natural microbial community, and analysed for gene expression and DOM chemical composition. Microbial gene expression (metatranscriptomics) in light and dark treatments diverged substantially after 4 h. Gene expression suggested that sunlight exposure of DOM initially stimulated microbial growth by (i) replacing the function of enzymes that degrade higher molecular weight DOM such as enzymes for aromatic carbon degradation, oxygenation, and decarboxylation, and (ii) releasing low molecular weight compounds and inorganic nutrients from DOM. However, growth stimulation following sunlight exposure of DOM came at a cost. Sunlight depleted the pool of aromatic compounds that supported microbial growth in the dark treatment, ultimately causing slower growth in the light treatment over 5 days. These first measurements of microbial metatranscriptomic responses to photo‐alteration of DOM provide a mechanistic explanation for how sunlight exposure of terrigenous DOM alters microbial processing and respiration of DOM.

Regional Movements of Reef Manta Rays (Mobula alfredi) in Seychelles Waters - Lauren R. Peel; Guy M. W. Stevens; Ryan Daly; Clare A. Keating Daly; Shaun P. Collin; Josep Nogués; Mark G. Meekan (Frontiers in Marine Science, 2020)

Efficacy of VERYL® in the treatment of cattle naturally infected with gastro-intestinal nematodes in Kenya - M. W. Maichomo; J. M. Nginyi; A. Caruso-Varès; E. O. Mungube; G. Pagny; C. Chevtzoff; J. C. Njanja; P. A. Lumumba; J. F. Collin; N. Isaka (Tropical Animal Health and Production, 2020)

Protection of wetlands as a strategy for reducing the spread of avian influenza from migratory waterfowl - Tong Wu; Charles Perrings; Chenwei Shang; James P. Collins; Peter Daszak; Ann Kinzig; Ben A. Minteer (Ambio, 2020)

Climate and human water use diminish wetland networks supporting continental waterbird migration - J. Patrick Donnelly; Sammy L. King; Nicholas L. Silverman; Daniel P. Collins; Eduardo M. Carrera‐Gonzalez; Alberto Lafón‐Terrazas; Johnnie N. Moore (Global Change Biology, 2020)
Migrating waterbirds moving between upper and lower latitudinal breeding and wintering grounds rely on a limited network of endorheic lakes and wetlands when crossing arid continental interiors. Recent drying of global endorheic water stores raises concerns over deteriorating migratory pathways, yet few studies have considered these effects at the scale of continental flyways. Here, we investigate the resiliency of waterbird migration networks across western North America by reconstructing long‐term patterns (1984–2018) of terminal lake and wetland surface water area in 26 endorheic watersheds. Findings were partitioned regionally by snowmelt‐ and monsoon‐driven hydrologies and combined with climate and human water‐use data to determine their importance in predicting surface water trends. Nonlinear patterns of lake and wetland drying were apparent along latitudinal flyway gradients. Pervasive surface water declines were prevalent in northern snowmelt watersheds (lakes −27%, wetlands −47%) while largely stable in monsoonal watersheds to the south (lakes −13%, wetlands +8%). Monsoonal watersheds represented a smaller proportion of total lake and wetland area, but their distribution and frequency of change within highly arid regions of the continental flyway increased their value to migratory waterbirds. Irrigated agriculture and increasing evaporative demands were the most important drivers of surface water declines. Underlying agricultural and wetland relationships however were more complex. Approximately 7% of irrigated lands linked to flood irrigation and water storage practices supported 61% of all wetland inundation in snowmelt watersheds. In monsoonal watersheds, small earthen dams, meant to capture surface runoff for livestock watering, were a major component of wetland resources (67%) that supported networks of isolated wetlands surrounding endorheic lakes. Ecological trends and human impacts identified herein underscore the importance of assessing flyway‐scale change as our model depictions likely reflect new and emerging bottlenecks to continental migration.

Rapid recovery of ecosystem function following extreme drought in a South African savanna grassland - Kevin R. Wilcox; Sally E. Koerner; David L. Hoover; Andrea K. Borkenhagen; Deron E. Burkepile; Scott L. Collins; Ava M. Hoffman; Kevin P. Kirkman; Alan K. Knapp; Tercia Strydom; Dave I. Thompson; Melinda D. Smith (Ecology, 2020)
Climatic extremes, such as severe drought, are expected to increase in frequency and magnitude with climate change. Thus, identifying mechanisms of resilience is critical to predicting the vulnerability of ecosystems. An exceptional drought (

Age and growth of Brauer's lanternfish Gymnoscopelus braueri and rhombic lanternfish Krefftichthys anderssoni (Family Myctophidae) in the Scotia Sea, Southern Ocean - Ryan A. Saunders; Silvia Lourenço; Rui P. Vieira; Martin A. Collins; Carlos A. Assis; Jose C. Xavier (Journal of Fish Biology, 2020)
This study examines age and growth of Brauer's lanternfish Gymnoscopelus braueri and rhombic lanternfish Krefftichthys anderssoni from the Scotia Sea in the Southern Ocean, through the analysis of annual growth increments deposited on sagittal otoliths. Otolith pairs from 177 G. braueri and 118 K. anderssoni were collected in different seasons from the region between 2004 and 2009. Otolith‐edge analysis suggested a seasonal change in opaque and hyaline depositions, indicative of an annual growth pattern, although variation within the populations of both species was apparent. Age estimates varied from 1 to 6 years for G. braueri (40 to 139 mm standard length; L S ) and from 0 to 2 years for K. anderssoni (26 to 70 mm L S ). Length‐at‐age data were broadly consistent with population cohort parameters identified in concurrent length‐frequency data from the region for both species. The estimated values of von Bertalanffy growth curves for G. braueri were L ∞ = 133.22 mm, k = 0.29 year −1 and t 0 = − 0.21 year and the values for K. anderssoni were L ∞ = 68.60 mm, k = 0.71 year −1 and t 0 = − 0.49 year. There were no significant ( P > 0.05) differences in growth between sexes for either species, suggesting that males and females have similar growth and development trajectories in the Scotia Sea. A positive allometric relationship between L S and wet mass was found for each species, as well as a significant ( P L S . Growth performance ( Ф ′) was similar between the two species and congruent with other myctophid species across the Southern Ocean. This study provides important parameters for future Southern Ocean ecosystem studies in a resource management context.

The response of stomatal conductance to seasonal drought in tropical forests - Jin Wu; Shawn P. Serbin; Kim S. Ely; Brett T. Wolfe; L. Turin Dickman; Charlotte Grossiord; Sean T. Michaletz; Adam D. Collins; Matteo Detto; Nate G. McDowell; S. Joseph Wright; Alistair Rogers (Global Change Biology, 2020)
Stomata regulate CO 2 uptake for photosynthesis and water loss through transpiration. The approaches used to represent stomatal conductance ( g s ) in models vary. In particular, current understanding of drivers of the variation in a key parameter in those models, the slope parameter (i.e. a measure of intrinsic plant water‐use‐efficiency), is still limited, particularly in the tropics. Here we collected diurnal measurements of leaf gas exchange and leaf water potential (Ψ leaf ), and a suite of plant traits from the upper canopy of 15 tropical trees in two contrasting Panamanian forests throughout the dry season of the 2016 El Niño. The plant traits included wood density, leaf‐mass‐per‐area (LMA), leaf carboxylation capacity ( V c,max ), leaf water content, the degree of isohydry, and predawn Ψ leaf . We first investigated how the choice of four commonly used leaf‐level g s models with and without the inclusion of Ψ leaf as an additional predictor variable influence the ability to predict g s , and then explored the abiotic (i.e. month, site‐month interaction) and biotic (i.e. tree‐species‐specific characteristics) drivers of slope parameter variation. Our results show that the inclusion of Ψ leaf did not improve model performance and that the models that represent the response of g s to vapor pressure deficit performed better than corresponding models that respond to relative humidity. Within each g s model, we found large variation in the slope parameter, and this variation was attributable to the biotic driver, rather than abiotic drivers. We further investigated potential relationships between the slope parameter and the six available plant traits mentioned above, and found that only one trait, LMA, had a significant correlation with the slope parameter ( R 2 = 0.66, n = 15), highlighting a potential path towards improved model parameterization. This study advances understanding of g s dynamics over seasonal drought, and identifies a practical, trait‐based approach to improve modeling of carbon and water exchange in tropical forests.

Maximizing ENSO as a source of western US hydroclimate predictability - Christina M. Patricola; John P. O’Brien; Mark D. Risser; Alan M. Rhoades; Travis A. O’Brien; Paul A. Ullrich; Dáithí A. Stone; William D. Collins (Climate Dynamics, 2020)
Until recently, the El Niño–Southern Oscillation (ENSO) was considered a reliable source of winter precipitation predictability in the western US, with a historically strong link between extreme El Niño events and extremely wet seasons. However, the 2015–2016 El Niño challenged our understanding of the ENSO-precipitation relationship. California precipitation was near-average during the 2015–2016 El Niño, which was characterized by warm sea surface temperature (SST) anomalies of similar magnitude compared to the extreme 1997–1998 and 1982–1983 El Niño events. We demonstrate that this precipitation response can be explained by El Niño’s spatial pattern, rather than internal atmospheric variability. In addition, observations and large-ensembles of regional and global climate model simulations indicate that extremes in seasonal and daily precipitation during strong El Niño events are better explained using the ENSO Longitude Index (ELI), which captures the diversity of ENSO’s spatial patterns in a single metric, compared to the traditional Niño3.4 index, which measures SST anomalies in a fixed region and therefore fails to capture ENSO diversity. The physically-based ELI better explains western US precipitation variability because it tracks the zonal shifts in tropical Pacific deep convection that drive teleconnections through the response in the extratropical wave-train, integrated vapor transport, and atmospheric rivers. This research provides evidence that ELI improves the value of ENSO as a predictor of California’s seasonal hydroclimate extremes compared to traditional ENSO indices, especially during strong El Niño events.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Self-administration of the synthetic cathinones 3,4-methylenedioxypyrovalerone (MDPV) and α-pyrrolidinopentiophenone (α-PVP) in rhesus monkeys - Gregory T. Collins; Agnieszka Sulima; Kenner C. Rice; Charles P. France (Psychopharmacology, 2019)

Are Oxidative Stress Biomarkers Sensitive to Environmental Concentrations of Chlorpyrifos Exposed to the Freshwater Crab, Zilchiopsis collastinensis (Decapoda; Trichodactylidae)? - C. L. Negro; F. G. Iturburu; J. Mendieta; M. L. Menone; P. Collins (Bulletin of Environmental Contamination and Toxicology, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Linking Use of Ship Channels by West Indian Manatees (Trichechus manatus) to Seasonal Migration and Habitat Use - Carl S. Cloyed; Elizabeth E. Hieb; Merri K. Collins; Kayla P. DaCosta; Ruth H. Carmichael (Frontiers in Marine Science, 2019)

New shock microstructures in titanite (CaTiSiO5) from the peak ring of the Chicxulub impact structure, Mexico - Nicholas E. Timms; Mark A. Pearce; Timmons M. Erickson; Aaron J. Cavosie; Auriol S. P. Rae; John Wheeler; Axel Wittmann; Ludovic Ferrière; Michael H. Poelchau; Naotaka Tomioka; Gareth S. Collins; Sean P. S. Gulick; et al. (Contributions to Mineralogy and Petrology, 2019)

From shallow to deep divergences: mixed messages from Amazon Basin cichlids - Ana Paula C. Carvalho; Rupert A. Collins; José Gregório Martínez; Izeni P. Farias; Tomas Hrbek (Hydrobiologia, 2019)

Behavioral economic analysis of the reinforcing effects of “bath salts” mixtures: studies with MDPV, methylone, and caffeine in male Sprague-Dawley rats - Brenda M. Gannon; Melson P. Mesmin; Agnieszka Sulima; Kenner C. Rice; Gregory T. Collins (Psychopharmacology, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Does fish herding enhance catch rates and detection of invasive bigheaded carp? - Steven E. Butler; Anthony P. Porreca; Scott F. Collins; Jonathan A. Freedman; Joseph J. Parkos; Matthew J. Diana; David H. Wahl (Biological Invasions, 2019)

Shark depredation in commercial and recreational fisheries - J. D. Mitchell; D. L. McLean; S. P. Collin; T. J. Langlois (Reviews in Fish Biology and Fisheries, 2018)

Bed and suspended sediment-associated rare earth element concentrations and fluxes in a polluted Brazilian river system - Yuri Jacques Agra Bezerra da Silva; Clístenes Williams Araújo do Nascimento; Ygor Jacques Agra Bezerra da Silva; Fábio Farias Amorim; José Ramon Barros Cantalice; Vijay P. Singh; Adrian L. Collins (Environmental Science and Pollution Research, 2018)

Depositional age and provenance of the Cobar Supergroup - M. D. Parrish; W. J. Collins; R. A. Hegarty; P. J. Gilmore; H.-Q. Huang (Australian Journal of Earth Sciences, 2018)

Flood resilience: consolidating knowledge between and within critical infrastructure sectors - Jonathan Pearson; G. Punzo; M. Mayfield; G. Brighty; A. Parsons; P. Collins; S. Jeavons; A. Tagg (Environment Systems and Decisions, 2018)

Inter-Annual Precipitation Variability Decreases Switchgrass Productivity from Arid to Mesic Environments - Lara G. Reichmann; Harold P. Collins; Virginia L. Jin; Mari-Vaughn V. Johnson; Jim R. Kiniry; Robert B. Mitchell; H. Wayne Polley; Philip A. Fay (BioEnergy Research, 2018)

Evidence for exposure to selenium by breeding interior snowy plovers (Charadrius nivosus) in saline systems of the Southern Great Plains - H. M. Ashbaugh; W. C. Conway; D. A. Haukos; D. P. Collins; C. E. Comer; A. D. French (Ecotoxicology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Habitat disruption and the identification and management of functional trait changes - Jennifer L Kelley; Pauline F Grierson; Shaun P Collin; Peter M Davies (Fish and Fisheries, 2018)
Aquatic ecosystems are facing escalating threats from urbanization, habitat loss and projected impacts of climate change, which both individually and in combination have the potential to fundamentally alter ecosystem functioning. While it is well established that habitat disturbances can affect the composition and diversity of aquatic communities, only recently have studies considered whether such impacts result in changes in species’ functional traits. We consider how functional traits of freshwater and marine fishes respond to environmental change, and how shifts in the expression of these traits can impact community dynamics and key ecological processes, including trophic interactions and nutrient transfer. We find that a multitude of functional traits, including behavioural and sensory traits, is sensitive to habitat disturbances. We demonstrate how these trait changes can be used to reveal hidden “ecological diversity” as well as serving as early indicators of environmental perturbation. We conclude that management strategies that consider the fundamental biological responses of fishes to habitat disturbance will be particularly effective in determining causal relationships within the ecological network. While detailed information on trait function is often lacking, even some general understanding of trait function and importance will facilitate targeted and efficient ecosystem management. We urge fisheries biologists and aquatic ecosystem managers to consider the role of functional traits in facilitating effective habitat restoration and management.

Estimated Brain Tissue Response Following Impacts Associated With and Without Diagnosed Concussion - Jonathan G. Beckwith; Wei Zhao; Songbai Ji; Amaris G. Ajamil; Richard P. Bolander; Jeffrey J. Chu; Thomas W. McAllister; Joseph J. Crisco; Stefan M. Duma; Steven Rowson; Steven P. Broglio; Kevin M. Guskiewicz; et al. (Annals of Biomedical Engineering, 2018)

Using biological–physical modelling for informing sea lice dispersal in Loch Linnhe, Scotland - N K G Salama; A C Dale; V V Ivanov; P F Cook; C C Pert; C M Collins; B Rabe (Journal of Fish Diseases, 2018)
Sea lice are a constraint on the sustainable growth of Scottish marine salmonid aquaculture. As part of an integrated pest management approach, farms coordinate procedures within spatial units. We present observations of copepodids being at relatively greater density than nauplii in upper waters, which informs the development of surface layer sea lice transmission modelling of Loch Linnhe, Scotland, for informing farm parasite management. A hydrodynamic model is coupled with a biological particle‐tracking model, with characteristics of plankton sea lice. Simulations are undertaken for May and October 2011–2013, forced by local wind data collected for those periods. Particles are continually released from positions representing farm locations, weighted by relative farm counts, over a 2‐week period and tracked for a further 5 days. A comparison is made between modelled relative concentrations against physical and biological surveys to provide confidence in model outputs. Connectivity between farm locations is determined in order to propose potential coordination areas. Generally, connectivity depends on flow patterns in the loch and decreases with increased farm separation. The connectivity indices are used to estimate the origins of the sea lice population composition at each site, which may influence medicinal regimens to avoid loss of efficacy.

Improving reliability of species identification and logbook catch reporting by commercial fishers in an Australian demersal shark longline fishery - W. G. Macbeth; P. A. Butcher; D. Collins; S. P. McGrath; S. C. Provost; A. C. Bowling; P. T. Geraghty; V. M. Peddemors (Fisheries Management and Ecology, 2018)
Large adult carcharhinid and sphyrnid sharks have been targeted in coastal waters off New South Wales, eastern Australia, by commercial fishers using demersal longlines since 2005. Inaccurate fisher reporting of the composition of catches led in 2008 to a range of complementary management measures to help improve reliability, including a redesigned catch logbook, species identification guide and at‐sea education via an observer programme. This study provides results from assessments of the effectiveness of those measures. A questionnaire yielded overwhelmingly positive feedback from fishers regarding the usefulness of the species identification guide. Comparison of observer‐recorded data and corresponding fisher‐reported logbook data via weighted linear mixed‐effects modelling found that since 2008, misreporting of catches has varied considerably among species and, for some species, among fishers. With some species commonly under‐reported and others frequently over‐reported, it is apparent that certain species were likely mistaken for other morphologically similar species. Such systematic error inherently undermines stock assessments of these vulnerable species. Management strategies designed to include education and extension will ensure greater reliability of fisher reporting of shark catches in the future.

Regional grassland productivity responses to precipitation during multiyear above‐ and below‐average rainfall periods - Matthew D. Petrie; Debra P. C. Peters; Jin Yao; John M. Blair; Nathan D. Burruss; Scott L. Collins; Justin D. Derner; Laureano A. Gherardi; John R. Hendrickson; Osvaldo E. Sala; Patrick J. Starks; Jean L. Steiner (Global Change Biology, 2018)
There is considerable uncertainty in the magnitude and direction of changes in precipitation associated with climate change, and ecosystem responses are also uncertain. Multiyear periods of above‐ and below‐average rainfall may foretell consequences of changes in rainfall regime. We compiled long‐term aboveground net primary productivity ( ANPP ) and precipitation ( PPT ) data for eight North American grasslands, and quantified relationships between ANPP and PPT at each site, and in 1–3 year periods of above‐ and below‐average rainfall for mesic, semiarid cool, and semiarid warm grassland types. Our objective was to improve understanding of ANPP dynamics associated with changing climatic conditions by contrasting PPT – ANPP relationships in above‐ and below‐average PPT years to those that occurred during sequences of multiple above‐ and below‐average years. We found differences in PPT – ANPP relationships in above‐ and below‐average years compared to long‐term site averages, and variation in ANPP not explained by PPT totals that likely are attributed to legacy effects. The correlation between ANPP and current‐ and prior‐year conditions changed from year to year throughout multiyear periods, with some legacy effects declining, and new responses emerging. Thus, ANPP in a given year was influenced by sequences of conditions that varied across grassland types and climates. Most importantly, the influence of prior‐year ANPP often increased with the length of multiyear periods, whereas the influence of the amount of current‐year PPT declined. Although the mechanisms by which a directional change in the frequency of above‐ and below‐average years imposes a persistent change in grassland ANPP require further investigation, our results emphasize the importance of legacy effects on productivity for sequences of above‐ vs. below‐average years, and illustrate the utility of long‐term data to examine these patterns.

Flowering in grassland predicted by CO 2 and resource effects on species aboveground biomass - Philip A. Fay; Michael J. Aspinwall; Harold P. Collins; Anne E. Gibson; Richard H. Gill; Robert B. Jackson; Virginia L. Jin; Albina R. Khasanova; Lara G. Reichmann; H. Wayne Polley (Global Change Biology, 2018)
Continuing enrichment of atmospheric CO 2 may change plant community composition, in part by altering the availability of other limiting resources including soil water, nutrients, or light. The combined effects of CO 2 enrichment and altered resource availability on species flowering remain poorly understood. We quantified flowering culm and ramet production and biomass allocation to flowering culms/ramets for 10 years in C 4 ‐dominated grassland communities on contrasting soils along a CO 2 concentration gradient spanning pre‐industrial to expected mid‐21st century levels (250–500 μl/L). CO 2 enrichment explained up to 77% of the variation in flowering culm count across soils for three of the five species, and was correlated with flowering culm count on at least one soil for four of five species. In contrast, allocation to flowering culms was only weakly correlated with CO 2 enrichment for two species. Flowering culm counts were strongly correlated with species aboveground biomass (AGB; R 2 = .34–.74), a measure of species abundance. CO 2 enrichment also increased soil moisture and decreased light levels within the canopy but did not affect soil inorganic nitrogen availability. Structural equation models fit across the soils suggested species‐specific controls on flowering in two general forms: (1) CO 2 effects on flowering culm count mediated by canopy light level and relative species AGB (species AGB/total AGB) or by soil moisture effects on flowering culm count; (2) effects of canopy light level or soil inorganic nitrogen on flowering and/or relative species AGB, but with no significant CO 2 effect. Understanding the heterogeneity in species responses to CO 2 enrichment in plant communities across soils in edaphically variable landscapes is critical to predict CO 2 effects on flowering and other plant fitness components, and species potential to adapt to future environmental changes.

The Effect of Vine Kill Method on Vine Kill, Tuber Skinning Injury, Tuber Yield and Size Distribution, and Tuber Nutrients and Phytonutrients in Two Potato Cultivars Grown for Early Potato Production - R. A. Boydston; D. A. Navarre; H. P. Collins; B. Chaves-Cordoba (American Journal of Potato Research, 2018)

Effects of auditory and visual stimuli on shark feeding behaviour: the disco effect - Laura A. Ryan; Lucille Chapuis; Jan M. Hemmi; Shaun P. Collin; Robert D. McCauley; Kara E. Yopak; Enrico Gennari; Charlie Huveneers; Ryan M. Kempster; Caroline C. Kerr; Carl Schmidt; Channing A. Egeberg; et al. (Marine Biology, 2018)

Evaluation of Filtration and DNA Extraction Methods for Environmental DNA Biodiversity Assessments across Multiple Trophic Levels - Anni Djurhuus; Jesse Port; Collin J. Closek; Kevan M. Yamahara; Ofelia Romero-Maraccini; Kristine R. Walz; Dawn B. Goldsmith; Reiko Michisaki; Mya Breitbart; Alexandria B. Boehm; Francisco P. Chavez (Frontiers in Marine Science, 2017)

Fatigability, oxygen uptake kinetics and muscle deoxygenation in incomplete spinal cord injury during treadmill walking - Jared M. Gollie; Jeffrey E. Herrick; Randall E. Keyser; Lisa M. K. Chin; John P. Collins; Richard K. Shields; Gino S. Panza; Andrew A. Guccione (European Journal of Applied Physiology, 2017)

Use of anthropogenic material affects bird nest arthropod community structure: influence of urbanisation, and consequences for ectoparasites and fledging success - Hugh J. Hanmer; Rebecca L. Thomas; Gareth J. F. Beswick; Bradley P. Collins; Mark D. E. Fellowes (Journal of Ornithology, 2017)

Asymmetric responses of primary productivity to precipitation extremes: A synthesis of grassland precipitation manipulation experiments - Kevin R. Wilcox; Zheng Shi; Laureano A. Gherardi; Nathan P. Lemoine; Sally E. Koerner; David L. Hoover; Edward Bork; Kerry M. Byrne; James Cahill; Scott L. Collins; Sarah Evans; Anna K. Gilgen; et al. (Global Change Biology, 2017)
Climatic changes are altering Earth's hydrological cycle, resulting in altered precipitation amounts, increased interannual variability of precipitation, and more frequent extreme precipitation events. These trends will likely continue into the future, having substantial impacts on net primary productivity ( NPP ) and associated ecosystem services such as food production and carbon sequestration. Frequently, experimental manipulations of precipitation have linked altered precipitation regimes to changes in NPP . Yet, findings have been diverse and substantial uncertainty still surrounds generalities describing patterns of ecosystem sensitivity to altered precipitation. Additionally, we do not know whether previously observed correlations between NPP and precipitation remain accurate when precipitation changes become extreme. We synthesized results from 83 case studies of experimental precipitation manipulations in grasslands worldwide. We used meta‐analytical techniques to search for generalities and asymmetries of aboveground NPP ( ANPP ) and belowground NPP ( BNPP ) responses to both the direction and magnitude of precipitation change. Sensitivity (i.e., productivity response standardized by the amount of precipitation change) of BNPP was similar under precipitation additions and reductions, but ANPP was more sensitive to precipitation additions than reductions; this was especially evident in drier ecosystems. Additionally, overall relationships between the magnitude of productivity responses and the magnitude of precipitation change were saturating in form. The saturating form of this relationship was likely driven by ANPP responses to very extreme precipitation increases, although there were limited studies imposing extreme precipitation change, and there was considerable variation among experiments. This highlights the importance of incorporating gradients of manipulations, ranging from extreme drought to extreme precipitation increases into future climate change experiments. Additionally, policy and land management decisions related to global change scenarios should consider how ANPP and BNPP responses may differ, and that ecosystem responses to extreme events might not be predicted from relationships found under moderate environmental changes.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

The Effect of Nitrogen Rate on Vine Kill, Tuber Skinning Injury, Tuber Yield and Size Distribution, and Tuber Nutrients and Phytonutrients in Two Potato Cultivars Grown for Early Potato Production - R. A. Boydston; D. A. Navarre; H. P. Collins; B. Chaves-Cordoba (American Journal of Potato Research, 2017)

Genetic Analysis of Norovirus Strains that Caused Gastroenteritis Outbreaks Among River Rafters in the Grand Canyon, Arizona - Masaaki Kitajima; Brandon C. Iker; Anne Magill-Collins; Marlene Gaither; James D. Stoehr; Charles P. Gerba (Food and Environmental Virology, 2017)

Adapting astronomical source detection software to help detect animals in thermal images obtained by unmanned aerial systems - S. N. Longmore; R. P. Collins; S. Pfeifer; S. E. Fox; M. Mulero-Pázmány; F. Bezombes; A. Goodwin; M. De Juan Ovelar; J. H. Knapen; S. A. Wich (International Journal of Remote Sensing, 2017)

Molecular detection of kobuviruses in livestock in Northern Ireland and the Republic of Ireland - P. J. Collins; Michael J. McMenamy; Julie McClintock; Paula Lagan-Tregaskis; Lorna McCabe; Simon Doherty; Helen O’Shea; Michael Welsh; John McKillen (Archives of Virology, 2017)

Pushing precipitation to the extremes in distributed experiments: recommendations for simulating wet and dry years - Alan K. Knapp; Meghan L. Avolio; Claus Beier; Charles J. W. Carroll; Scott L. Collins; Jeffrey S. Dukes; Lauchlan H. Fraser; Robert J. Griffin‐Nolan; David L. Hoover; Anke Jentsch; Michael E. Loik; Richard P. Phillips; et al. (Global Change Biology, 2017)
Intensification of the global hydrological cycle, ranging from larger individual precipitation events to more extreme multiyear droughts, has the potential to cause widespread alterations in ecosystem structure and function. With evidence that the incidence of extreme precipitation years (defined statistically from historical precipitation records) is increasing, there is a clear need to identify ecosystems that are most vulnerable to these changes and understand why some ecosystems are more sensitive to extremes than others. To date, opportunistic studies of naturally occurring extreme precipitation years, combined with results from a relatively small number of experiments, have provided limited mechanistic understanding of differences in ecosystem sensitivity, suggesting that new approaches are needed. Coordinated distributed experiments ( CDE s) arrayed across multiple ecosystem types and focused on water can enhance our understanding of differential ecosystem sensitivity to precipitation extremes, but there are many design challenges to overcome (e.g., cost, comparability, standardization). Here, we evaluate contemporary experimental approaches for manipulating precipitation under field conditions to inform the design of ‘Drought‐Net’, a relatively low‐cost CDE that simulates extreme precipitation years. A common method for imposing both dry and wet years is to alter each ambient precipitation event. We endorse this approach for imposing extreme precipitation years because it simultaneously alters other precipitation characteristics (i.e., event size) consistent with natural precipitation patterns. However, we do not advocate applying identical treatment levels at all sites – a common approach to standardization in CDE s. This is because precipitation variability varies >fivefold globally resulting in a wide range of ecosystem‐specific thresholds for defining extreme precipitation years. For CDE s focused on precipitation extremes, treatments should be based on each site's past climatic characteristics. This approach, though not often used by ecologists, allows ecological responses to be directly compared across disparate ecosystems and climates, facilitating process‐level understanding of ecosystem sensitivity to precipitation extremes.

A kinematic investigation into the feeding behavior of the Goliath grouper Epinephelus itajara - A. B. Collins; P. J. Motta (Environmental Biology of Fishes, 2017)

Reply to the comments on “Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust” - Rui Wang; William J. Collins; Roberto F. Weinberg; Jeremy P. Richards; Wen-yan He (Contributions to Mineralogy and Petrology, 2017)

Electrophysiological measures of temporal resolution, contrast sensitivity and spatial resolving power in sharks - Laura A. Ryan; Jan M. Hemmi; Shaun P. Collin; Nathan S. Hart (Journal of Comparative Physiology A, 2017)

Independent evolution of sexual dimorphism and female‐limited mimicry in swallowtail butterflies ( Papilio dardanus and Papilio phorcas ) - M. J. T. N. Timmermans; M. J. Thompson; S. Collins; A. P. Vogler (Molecular Ecology, 2017)
Several species of swallowtail butterflies (genus Papilio ) are Batesian mimics that express multiple mimetic female forms, while the males are monomorphic and nonmimetic. The evolution of such sex‐limited mimicry may involve sexual dimorphism arising first and mimicry subsequently. Such a stepwise scenario through a nonmimetic, sexually dimorphic stage has been proposed for two closely related sexually dimorphic species: Papilio phorcas, a nonmimetic species with two female forms, and Papilio dardanus , a female‐limited polymorphic mimetic species. Their close relationship indicates that female‐limited polymorphism could be a shared derived character of the two species. Here, we present a phylogenomic analysis of the dardanus group using 3964 nuclear loci and whole mitochondrial genomes, showing that they are not sister species and thus that the sexually dimorphic state has arisen independently in the two species. Nonhomology of the female polymorphism in both species is supported by population genetic analysis of engrailed , the presumed mimicry switch locus in P. dardanus . McDonald–Kreitman tests performed on SNP s in engrailed showed the signature of balancing selection in a polymorphic population of P. dardanus , but not in monomorphic populations , nor in the nonmimetic P. phorcas . Hence, the wing polymorphism does not balance polymorphisms in engrailed in P. phorcas . Equally, unlike in P. dardanus , none of the SNP s in P. phorcas engrailed were associated with either female morph. We conclude that sexual dimorphism due to female polymorphism evolved independently in both species from monomorphic, nonmimetic states. While sexual selection may drive male–female dimorphism in nonmimetic species, in mimetic Papilios, natural selection for protection from predators in females is an alternative route to sexual dimorphism.

Use of artificially-induced freezing temperatures to identify freeze tolerance in above-ground buds of Saccharum and Erianthus accessions - Anna L. Hale; Ryan P. Viator; Collins Kimbeng; John C. Veremis (Euphytica, 2017)

Economic growth, urbanization, globalization, and the risks of emerging infectious diseases in China: A review - Tong Wu; Charles Perrings; Ann Kinzig; James P. Collins; Ben A. Minteer; Peter Daszak (Ambio, 2017)

Multiple processes drive genetic structure of humpback whale ( Megaptera novaeangliae ) populations across spatial scales - Francine Kershaw; Inês Carvalho; Jacqueline Loo; Cristina Pomilla; Peter B. Best; Ken P. Findlay; Salvatore Cerchio; Tim Collins; Marcia H. Engel; Gianna Minton; Peter Ersts; Jaco Barendse; et al. (Molecular Ecology, 2017)
Elucidating patterns of population structure for species with complex life histories, and disentangling the processes driving such patterns, remains a significant analytical challenge. Humpback whale ( Megaptera novaeangliae ) populations display complex genetic structures that have not been fully resolved at all spatial scales. We generated a data set of nuclear markers for 3575 samples spanning the seven breeding stocks and substocks found in the South Atlantic and western and northern Indian Oceans. For the total sample, and males and females separately, we assessed genetic diversity, tested for genetic differentiation between putative populations and isolation by distance, estimated the number of genetic clusters without a priori population information and estimated rates of gene flow using maximum‐likelihood and Bayesian approaches. At the ocean basin scale, structure is governed by geographical distance ( IBD P F ST 0.034–0.161; P

Genetic and Manual Survey Methods Yield Different and Complementary Views of an Ecosystem - Ryan P. Kelly; Collin J. Closek; James L. O'Donnell; James E. Kralj; Andrew O. Shelton; Jameal F. Samhouri (Frontiers in Marine Science, 2017)

CO2 and soil water potential as regulators of the growth and N fraction derived from fixation of a legume in tallgrass prairie communities - H. Wayne Polley; Harold P. Collins; Lara G. Reichmann; Philip A. Fay (Plant and Soil, 2016)

Modelling and genetic dissection of staygreen under heat stress - R. Suzuky Pinto; Marta S. Lopes; Nicholas C. Collins; Matthew P. Reynolds (Theoretical and Applied Genetics, 2016)

Early Disruption of Extracellular Pleiotrophin Distribution Alters Cerebellar Neuronal Circuit Development and Function - M. M. Hamza; S. A. Rey; P. Hilber; A. Arabo; T. Collin; D. Vaudry; D. Burel (Molecular Neurobiology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

A comparative approach to assess drivers of success in mammalian conservation recovery programs - Jennifer J. Crees; Amy C. Collins; P. J. Stephenson; Helen M. R. Meredith; Richard P. Young; Caroline Howe; Mark R. Stanley Price; Samuel T. Turvey (Conservation Biology, 2016)
The outcomes of species recovery programs have been mixed; high‐profile population recoveries contrast with species‐level extinctions. Each conservation intervention has its own challenges, but to inform more effective management it is imperative to assess whether correlates of wider recovery program success or failure can be identified. To contribute to evidence‐based improvement of future conservation strategies, we conducted a global quantitative analysis of 48 mammalian recovery programs. We reviewed available scientific literature and conducted semistructured interviews with conservation professionals involved in different recovery programs to investigate ecological, management, and political factors associated with population recoveries or declines. Identifying and removing threats was significantly associated with increasing population trend and decreasing conservation dependence, emphasizing that populations are likely to continue to be compromised in the absence of effective threat mitigation and supporting the need for threat monitoring and adaptive management in response to new and potential threats. Lack of habitat and small population size were cited as limiting factors in 56% and 42% of recovery programs, respectively, and both were statistically associated with increased longer term dependence on conservation intervention, demonstrating the importance of increasing population numbers quickly and restoring and protecting habitat. Poor stakeholder coordination and management were also regularly cited by respondents as key weaknesses in recovery programs, indicating the importance of effective leadership and shared goals and management plans. Project outcomes were not influenced by biological or ecological variables such as body mass or habitat, which suggests that these insights into correlates of conservation success and failure are likely to be generalizable across mammals.

Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust - Rui Wang; William J. Collins; Roberto F. Weinberg; Jin-xiang Li; Qiu-yun Li; Wen-yan He; Jeremy P. Richards; Zengqian Hou; Li-min Zhou; Richard A. Stern (Contributions to Mineralogy and Petrology, 2016)

Preliminary evidence of reduced brain network activation in patients with post-traumatic migraine following concussion - Anthony P. Kontos; Amit Reches; R. J. Elbin; Dalia Dickman; Ilan Laufer; Amir B. Geva; Galit Shacham; Ryan DeWolf; Michael W. Collins (Brain Imaging and Behavior, 2016)

It’s what’s inside that counts: egg contaminant concentrations are influenced by estimates of egg density, egg volume, and fresh egg mass - Mark P. Herzog; Joshua T. Ackerman; Collin A. Eagles-Smith; C. Alex Hartman (Ecotoxicology, 2016)

Antarctica on foot: the energy expended to walk, ski and man-haul - L. G. Halsey; R. Lambert; P. Collins; A. Newnham; A. Kumar; C. O’Driscoll; M. A. Stroud (Polar Biology, 2016)

Increased Light Availability Reduces the Importance of Bacterial Carbon in Headwater Stream Food Webs - Sarah M. Collins; Jed P. Sparks; Steven A. Thomas; Sarah A. Wheatley; Alexander S. Flecker (Ecosystems, 2016)

Development of a rapid, low-cost protoplast transfection system for switchgrass (Panicum virgatum L.) - Kellie P. Burris; Elizabeth M. Dlugosz; A. Grace Collins; C. Neal Stewart; Scott C. Lenaghan (Plant Cell Reports, 2016)

Reactions to cadmium stress in a cadmium-tolerant variety of cabbage (Brassica oleracea L.): is cadmium tolerance necessarily desirable in food crops? - Neel Jinadasa; Damian Collins; Paul Holford; Paul J. Milham; Jann P. Conroy (Environmental Science and Pollution Research, 2016)

Making literature reviews more reliable through application of lessons from systematic reviews - N.R. Haddaway; P. Woodcock; B. Macura; A. Collins (Conservation Biology, 2015)
Review articles can provide valuable summaries of the ever‐increasing volume of primary research in conservation biology. Where findings may influence important resource‐allocation decisions in policy or practice, there is a need for a high degree of reliability when reviewing evidence. However, traditional literature reviews are susceptible to a number of biases during the identification, selection, and synthesis of included studies (e.g., publication bias, selection bias, and vote counting). Systematic reviews, pioneered in medicine and translated into conservation in 2006, address these issues through a strict methodology that aims to maximize transparency, objectivity, and repeatability. Systematic reviews will always be the gold standard for reliable synthesis of evidence. However, traditional literature reviews remain popular and will continue to be valuable where systematic reviews are not feasible. Where traditional reviews are used, lessons can be taken from systematic reviews and applied to traditional reviews in order to increase their reliability. Certain key aspects of systematic review methods that can be used in a context‐specific manner in traditional reviews include focusing on mitigating bias; increasing transparency, consistency, and objectivity, and critically appraising the evidence and avoiding vote counting. In situations where conducting a full systematic review is not feasible, the proposed approach to reviewing evidence in a more systematic way can substantially improve the reliability of review findings, providing a time‐ and resource‐efficient means of maximizing the value of traditional reviews. These methods are aimed particularly at those conducting literature reviews where systematic review is not feasible, for example, for graduate students, single reviewers, or small organizations.

An eDNA assay for Irish Petromyzon marinus and Salmo trutta and field validation in running water - M. S. Gustavson; P. C. Collins; J. A. Finarelli; D. Egan; R. Ó. Conchúir; G. D. Wightman; J. J. King; D. T. Gauthier; K. Whelan; J. E. L. Carlsson; J. Carlsson (Journal of Fish Biology, 2015)
This pilot study presents an environmental DNA ( eDNA ) assay for sea lamprey Petromyzon marinus and brown trout Salmo trutta , two species of economic and conservation importance in the Republic of Ireland. The results demonstrate the effectiveness of eDNA for assessing presence of low‐abundance taxa (here, P. marinus ) for environmental managers, and they highlight the potential for assessing relative abundance of rare or invasive freshwater species.

Experimental drought and heat can delay phenological development and reduce foliar and shoot growth in semiarid trees - Henry D. Adams; Adam D. Collins; Samuel P. Briggs; Michel Vennetier; L. Turin Dickman; Sanna A. Sevanto; Núria Garcia‐Forner; Heath H. Powers; Nate G. McDowell (Global Change Biology, 2015)
Higher temperatures associated with climate change are anticipated to trigger an earlier start to the growing season, which could increase the terrestrial C sink strength. Greater variability in the amount and timing of precipitation is also expected with higher temperatures, bringing increased drought stress to many ecosystems. We experimentally assessed the effects of higher temperature and drought on the foliar phenology and shoot growth of mature trees of two semiarid conifer species. We exposed field‐grown trees to a ~45% reduction in precipitation with a rain‐out structure (‘drought’), a ~4.8 °C temperature increase with open‐top chambers (‘heat’), and a combination of both simultaneously (‘drought + heat’). Over the 2013 growing season, drought, heat, and drought + heat treatments reduced shoot and needle growth in piñon pine ( Pinus edulis ) by ≥39%, while juniper ( Juniperus monosperma ) had low growth and little response to these treatments. Needle emergence on primary axis branches of piñon pine was delayed in heat, drought, and drought + heat treatments by 19–57 days, while secondary axis branches were less likely to produce needles in the heat treatment, and produced no needles at all in the drought + heat treatment. Growth of shoots and needles, and the timing of needle emergence correlated inversely with xylem water tension and positively with nonstructural carbohydrate concentrations. Our findings demonstrate the potential for delayed phenological development and reduced growth with higher temperatures and drought in tree species that are vulnerable to drought and reveal potential mechanistic links to physiological stress responses. Climate change projections of an earlier and longer growing season with higher temperatures, and consequent increases in terrestrial C sink strength, may be incorrect for regions where plants will face increased drought stress with climate change.

Trophodynamics of Protomyctophum (Myctophidae) in the Scotia Sea (Southern Ocean) - R. A. Saunders; M. A. Collins; P. Ward; G. Stowasser; R. Shreeve; G. A. Tarling (Journal of Fish Biology, 2015)
This study investigated spatial and temporal patterns in distribution, population structure and diet of Bolin's lanternfish Protomyctophum bolini , Tenison's lanternfish Protomyctophum tenisoni and gaptooth lanternfish Protomyctophum choriodon in the Scotia Sea using data collected by midwater trawl during spring, summer and autumn. Protomyctophum bolini was the most abundant species of the genus encountered throughout the Scotia Sea with the greatest concentrations occurring around the Antarctic Polar Front ( APF ). This species had a life cycle of 2+ years, but spatial differences in population structure were apparent as the I‐group was absent from all regions south of the APF , suggesting that the species does not recruit in the Scotia Sea. Protomyctophum tenisoni occurred mostly in waters characteristic of the APF and was absent from the southern Scotia Sea. It had a limited size range, but there was clear size‐related sexual dimorphism with males significantly larger than females. The species had a life cycle of c. 2 years, but the I‐group ( c. 1 year old, 1 November to 31 October the next year) occurred only in regions close to the APF suggesting that recruitment is restricted to these waters. A seasonal southward migration for P. choriodon is likely as the species occurred mostly to the south‐west of South Georgia in summer, but extended to the sea‐ice sectors in autumn. Protomyctophum choriodon had a life cycle of 4+ years in the Scotia Sea and the population was dominated by age classes >3 years old. Larval stages were absent during the surveys for all species. Diurnal variations in vertical distribution were apparent for all three species. Interspecific variations in diet were evident, but all species were primarily copepod feeders, with Metridia spp., Rhincalanus gigas and Calanus simillimus generally dominating their diet. Small euphausiids, principally Thysanoessa spp., were also an important component of their diets, particularly for P. choriodon which had the largest body size. The spatial and temporal variations in diet for both P. bolini and P. tenisoni were broadly consistent with underlying abundance patterns within the mesozooplankton community.

It is not just size that matters: shark cruising speeds are species-specific - Laura A. Ryan; Jessica J. Meeuwig; Jan M. Hemmi; Shaun P. Collin; Nathan S. Hart (Marine Biology, 2015)

Geochemistry of post-extinction microbialites as a powerful tool to assess the oxygenation of shallow marine water in the immediate aftermath of the end-Permian mass extinction - P. Y. Collin; S. Kershaw; N. Tribovillard; M. B. Forel; S. Crasquin (International Journal of Earth Sciences, 2015)

Songbirds as sentinels of mercury in terrestrial habitats of eastern North America - Allyson K. Jackson; David C. Evers; Evan M. Adams; Daniel A. Cristol; Collin Eagles-Smith; Samuel T. Edmonds; Carrie E. Gray; Bart Hoskins; Oksana P. Lane; Amy Sauer; Timothy Tear (Ecotoxicology, 2015)

Seismic site characterization of the Kastelli (Kissamos) Basin in northwest Crete (Greece): assessments using ambient noise recordings - M. Moisidi; F. Vallianatos; S. Kershaw; P. Collins (Bulletin of Earthquake Engineering, 2015)

Not all sharks are “swimming noses”: variation in olfactory bulb size in cartilaginous fishes - Kara E. Yopak; Thomas J. Lisney; Shaun P. Collin (Brain Structure and Function, 2015)

Grassland to shrubland state transitions enhance carbon sequestration in the northern Chihuahuan Desert - M. D. Petrie; S. L. Collins; A. M. Swann; P. L. Ford; M.E. Litvak (Global Change Biology, 2015)
The replacement of native C 4 ‐dominated grassland by C 3 ‐dominated shrubland is considered an ecological state transition where different ecological communities can exist under similar environmental conditions. These state transitions are occurring globally, and may be exacerbated by climate change. One consequence of the global increase in woody vegetation may be enhanced ecosystem carbon sequestration, although the responses of arid and semiarid ecosystems may be highly variable. During a drier than average period from 2007 to 2011 in the northern Chihuahuan Desert, we found established shrubland to sequester 49 g C m −2 yr −1 on average, while nearby native C 4 grassland was a net source of 31 g C m −2 yr −1 over this same period. Differences in C exchange between these ecosystems were pronounced – grassland had similar productivity compared to shrubland but experienced higher C efflux via ecosystem respiration, while shrubland was a consistent C sink because of a longer growing season and lower ecosystem respiration. At daily timescales, rates of carbon exchange were more sensitive to soil moisture variation in grassland than shrubland, such that grassland had a net uptake of C when wet but lost C when dry. Thus, even under unfavorable, drier than average climate conditions, the state transition from grassland to shrubland resulted in a substantial increase in terrestrial C sequestration. These results illustrate the inherent tradeoffs in quantifying ecosystem services that result from ecological state transitions, such as shrub encroachment. In this case, the deleterious changes to ecosystem services often linked to grassland to shrubland state transitions may at least be partially offset by increased ecosystem carbon sequestration.

Enhanced characterization of the zebrafish brain as revealed by super-resolution track-density imaging - Jeremy F. P. Ullmann; Fernando Calamante; Shaun P. Collin; David C. Reutens; Nyoman D. Kurniawan (Brain Structure and Function, 2015)

Evidence for the existence of powder sub-populations in micronized materials: Aerodynamic size-fractions of aerosolized powders possess distinct physicochemical properties. - Sara Jaffari; Ben Forbes; Elizabeth Collins; Jiyi Khoo; Gary P Martin; Darragh Murnane (Pharmaceutical Research, 2014)

Brain activation during neurocognitive testing using functional near-infrared spectroscopy in patients following concussion compared to healthy controls - A. P. Kontos; T. J. Huppert; N. H. Beluk; R. J. Elbin; L. C. Henry; J. French; S. M. Dakan; M. W. Collins (Brain Imaging and Behavior, 2014)

Locating Noctiluca miliaris in the Arabian Sea: An optical proxy approach - Patricia S. Thibodeau; Collin S. Roesler; Susan L. Drapeau; S. G. Prabhu Matondkar; Joaquim I. Goes; P. Jeremy Werdell (Limnology and Oceanography, 2014)
Coincident with shifting monsoon weather patterns over India, the phytoplankter Noctiluca miliaris has recently been observed to be dominating phytoplankton blooms in the northeastern Arabian Sea during the winter monsoons. Identifying the exact environmental and/or ecological conditions that favor this species has been hampered by the lack of concurrent environmental and biological observations on time and space scales relevant to ecologic and physiologic processes. We present a bio‐optical proxy for N. miliaris measured on highly resolved depth scales coincident with hydrographic observations with the goal to identify conducive hydrographic conditions for the bloom. The proxy is derived from multichannel excitation chlorophyll a fluorescence and is validated with microscopy, pigment composition, and spectral absorption. Phytoplankton populations dominated by either diatoms or other dinoflagellates were additionally discerned. N. miliaris populations in full bloom were identified offshore in low‐nutrient and low–N : P ratio surface waters within a narrow temperature and salinity range. These populations transitioned to high‐biomass diatom‐dominated coastal upwelling populations. A week later, the N. miliaris blooms were observed in declining phase, transitioning to very‐low‐biomass populations of non– N. miliaris dinoflagellates. There were no clear hydrographic conditions uniquely associated with the N. miliaris populations, although N. miliaris was not found in the upwelling or extremely oligotrophic waters. Taxonomic transitions were not discernible in the spatial structure of the bloom as identified by the ocean color Chl imagery, indicating that in situ observations may be necessary to resolve community structure, particularly for populations below the surface.

Identification and validation of genes with expression patterns inverse to multiple metastasis suppressor genes in breast cancer cell lines - Natascia Marino; Joshua W. Collins; Changyu Shen; Natasha J. Caplen; Anand S. Merchant; Yesim Gökmen-Polar; Chirayu P. Goswami; Takashi Hoshino; Yongzhen Qian; George W. Sledge; Patricia S. Steeg (Clinical & Experimental Metastasis, 2014)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Hydroclimatic flood trends in the northeastern United States and linkages with large-scale atmospheric circulation patterns - William H. Armstrong; Mathias J. Collins; Noah P. Snyder (Hydrological Sciences Journal, 2014)

Quantifying the impact of environmental variables upon catch per unit effort of the blue shark Prionace glauca in the western English Channel - J. D. Mitchell; K. J. Collins; P. I. Miller; L. A. Suberg (Journal of Fish Biology, 2014)
The effect of environmental variables on blue shark Prionace glauca catch per unit effort ( CPUE ) in a recreational fishery in the western English Channel, between June and September 1998–2011, was quantified using generalized additive models ( GAMs ). Sea surface temperature ( SST ) explained 1·4% of GAM deviance, and highest CPUE occurred at 16·7° C, reflecting the optimal thermal preferences of this species. Surface chlorophyll a concentration ( CHL ) significantly affected CPUE and caused 27·5% of GAM deviance. Additionally, increasing CHL led to rising CPUE , probably due to higher productivity supporting greater prey biomass. The density of shelf‐sea tidal mixing fronts explained 5% of GAM deviance, but was non‐significant, with increasing front density negatively affecting CPUE. Time‐lagged frontal density significantly affected CPUE, however, causing 12·6% of the deviance in a second GAM and displayed a positive correlation. This outcome suggested a delay between the evolution of frontal features and the subsequent accumulation of productivity and attraction of higher trophic level predators, such as P. glauca .

A comparison of the efficiency of ELISA and selected primer sets to detect Norovirus isolates in southern Ireland over a four-year period (2002-2006): variation in detection rates and evidence for continuing predominance of NoV GII.4 genotype - G. Lennon; N. Reidy; P. J. Collins; L. Gunn; P. V. Coyle; B. Cryan; S. Fanning; H. O’Shea (Archives of Virology, 2014)

Effects of Chlorpyrifos and Endosulfan on Different Life Stages of the Freshwater Burrowing Crab Zilchiopsis collastinensis P.: Protective Role of Chorion - C. L. Negro; L. E. Senkman; F. Marino; E. Lorenzatti; P. Collins (Bulletin of Environmental Contamination and Toxicology, 2014)

Loss of a large grazer impacts savanna grassland plant communities similarly in North America and South Africa - Stephanie Eby; Deron E. Burkepile; Richard W. S. Fynn; Catherine E. Burns; Navashni Govender; Nicole Hagenah; Sally E. Koerner; Katherine J. Matchett; Dave I. Thompson; Kevin R. Wilcox; Scott L. Collins; Kevin P. Kirkman; et al. (Oecologia, 2014)

Plant community response to loss of large herbivores differs between North American and South African savanna grasslands - Sally E. Koerner; Deron E. Burkepile; Richard W. S. Fynn; Catherine E. Burns; Stephanie Eby; Navashni Govender; Nicole Hagenah; Katherine J. Matchett; Dave I. Thompson; Kevin R. Wilcox; Scott L. Collins; Kevin P. Kirkman; et al. (Ecology, 2014)
Herbivory and fire shape plant community structure in grass‐dominated ecosystems, but these disturbance regimes are being altered around the world. To assess the consequences of such alterations, we excluded large herbivores for seven years from mesic savanna grasslands sites burned at different frequencies in North America (Konza Prairie Biological Station, Kansas, USA) and South Africa (Kruger National Park). We hypothesized that the removal of a single grass‐feeding herbivore from Konza would decrease plant community richness and shift community composition due to increased dominance by grasses. Similarly, we expected grass dominance to increase at Kruger when removing large herbivores, but because large herbivores are more diverse, targeting both grasses and forbs, at this study site, the changes due to herbivore removal would be muted. After seven years of large‐herbivore exclusion, richness strongly decreased and community composition changed at Konza, whereas little change was evident at Kruger. We found that this divergence in response was largely due to differences in the traits and numbers of dominant grasses between the study sites rather than the predicted differences in herbivore assemblages. Thus, the diversity of large herbivores lost may be less important in determining plant community dynamics than the functional traits of the grasses that dominate mesic, disturbance‐maintained savanna grasslands.

Health of white sucker within the St. Louis River area of concern associated with habitat usage as assessed using stable isotopes - V. S. Blazer; J. Hoffman; H. L. Walsh; R. P. Braham; C. Hahn; P. Collins; Z. Jorgenson; T. Ledder (Ecotoxicology, 2014)

Seed bank potential of moist-soil managed wetlands in east-central Texas - Daniel P. Collins; Warren C. Conway; Corey D. Mason; Jeffrey W. Gunnels (Wetlands Ecology and Management, 2013)

Chemistry and Microbial Functional Diversity Differences in Biofuel Crop and Grassland Soils in Multiple Geographies - Lidia S. Watrud; Jay R. Reichman; Michael A. Bollman; Bonnie M. Smith; E. Henry Lee; Julie D. Jastrow; Michael D. Casler; Harold P. Collins; Steven Fransen; Robert B. Mitchell; Vance N. Owens; Brent Bean; et al. (BioEnergy Research, 2013)

Faster scaling of visual neurons in cortical areas relative to subcortical structures in non-human primate brains - C. E. Collins; D. B. Leitch; P. Wong; J. H. Kaas; Suzana Herculano-Houzel (Brain Structure and Function, 2013)

Footprints of selection in wild populations of B icyclus anynana along a latitudinal cline - M. A. de Jong; S. Collins; P. Beldade; P. M. Brakefield; B. J. Zwaan (Molecular Ecology, 2013)
One of the major questions in ecology and evolutionary biology is how variation in the genome enables species to adapt to divergent environments. Here, we study footprints of thermal selection in candidate genes in six wild populations of the afrotropical butterfly Bicyclus anynana sampled along a c . 3000 km latitudinal cline. We sequenced coding regions of 31 selected genes with known functions in metabolism, pigment production, development and heat shock responses. These include genes for which we expect a priori a role in thermal adaptation and, thus, varying selection pressures along a latitudinal cline, and genes we do not expect to vary clinally and can be used as controls. We identified amino acid substitution polymorphisms in 13 genes and tested these for clinal variation by correlation analysis of allele frequencies with latitude. In addition, we used two F ST ‐based outlier methods to identify loci with higher population differentiation than expected under neutral evolution, while accounting for potentially confounding effects of population structure and demographic history. Two metabolic enzymes of the glycolytic pathway, UGP and Treh, showed clinal variation. The same loci showed elevated population differentiation and were identified as significant outliers. We found no evidence of clines in the pigmentation genes, heat shock proteins and developmental genes. However, we identified outlier loci in more localized parts of the range in the pigmentation genes yellow and black . We discuss that the observed clinal variation and elevated population divergence in UGP and Treh may reflect adaptation to a geographic thermal gradient.

Impact of altitude and latitude on changes in temperature extremes over South Asia during 1971–2000 - J. V. Revadekar; S. Hameed; D. Collins; M. Manton; M. Sheikh; H. P. Borgaonkar; D. R. Kothawale; M. Adnan; A. U. Ahmed; J. Ashraf; S. Baidya; N. Islam; et al. (International Journal of Climatology, 2013)
South Asia covers more than 30° of latitude with weather observation stations situated from 6°N at Galle, Sri Lanka, to 36°N at Chitral in Pakistan. Moreover, the South Asian station network ranges in altitude from sea level to nearly 4000 m above sea level. This paper uses time series of 11 objectively defined indices of daily temperature extremes at 197 stations in Bangladesh, India, Nepal, Pakistan and Sri Lanka to examine the possible impacts of elevation and latitude on changes in temperature extremes over the period of 1971–2000. Trends in extreme indices are consistent with general warming only at low altitudes and latitudes. Stations at high altitudes and latitudes show both positive and negative trends in extreme temperature indices. As a notable example, the Diurnal Temperature Range (DTR), which has been known to decrease in most parts of the globe, has increasing trends over many high altitude stations in South Asia. Trends in extreme temperature indices at stations in South Asia higher than 2000 m above sea level are mostly in disagreement with those reported over the Tibetan Plateau. Observed trends at low altitude locations in South Asia suggest that these sites can generally expect future changes in temperature extremes that are consistent with broad‐scale warming. High‐elevation sites appear to be more influenced by local factors and, hence, future changes in temperature extremes may be less predictable for these locations. Copyright © 2012 Royal Meteorological Society

The mechanosensory lateral line system in two species of wobbegong shark (Orectolobidae) - Susan M. Theiss; Shaun P. Collin; Nathan S. Hart (Zoomorphology, 2012)

Corneal microprojections in coleoid cephalopods - Christopher Talbot; Thomas M. Jordan; Nicholas W. Roberts; Shaun P. Collin; N. Justin Marshall; Shelby E. Temple (Journal of Comparative Physiology A, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Impact of ocean model resolution on CCSM climate simulations - Ben P. Kirtman; Cecilia Bitz; Frank Bryan; William Collins; John Dennis; Nathan Hearn; James L. Kinter; Richard Loft; Clement Rousset; Leo Siqueira; Cristiana Stan; Robert Tomas; et al. (Climate Dynamics, 2012)

Molecular ecology and adaptation of visual photopigments in craniates - WAYNE I. L. DAVIES; SHAUN P. COLLIN; DAVID M. HUNT (Molecular Ecology, 2012)
In craniates, opsin‐based photopigments expressed in the eye encode molecular ‘light sensors’ that constitute the initial protein in photoreception and the activation of the phototransduction cascade. Since the cloning and sequencing of the first vertebrate opsin gene (bovine rod opsin) nearly 30 years ago (Ovchinnikov Yu 1982, FEBS Letters , 148, 179–191; Hargrave et al. 1983, Biophysics of Structure & Mechanism , 9, 235–244; Nathans & Hogness 1983, Cell , 34, 807–814), it is now well established that variation in the subtypes and spectral properties of the visual pigments that mediate colour and dim‐light vision is a prevalent mechanism for the molecular adaptation to diverse light environments. In this review, we discuss the origins and spectral tuning of photopigments that first arose in the agnathans to sample light within the ancient aquatic landscape of the Early Cambrian, detailing the molecular changes that subsequently occurred in each of the opsin classes independently within the main branches of extant jawed gnathostomes. Specifically, we discuss the adaptive changes that have occurred in the photoreceptors of craniates as they met the ecological challenges to survive in quite differing photic niches, including brightly lit aquatic surroundings; the deep sea; the transition to and from land; diurnal, crepuscular and nocturnal environments; and light‐restricted fossorial settings. The review ends with a discussion of the limitations inherent to the ‘nocturnal‐bottleneck’ hypothesis relevant to the evolution of the mammalian visual system and a proposition that transition through a ‘mesopic‐bottleneck’ may be a more appropriate model.

Vision in elasmobranchs and their relatives: 21st century advances - T. J. Lisney; S. M. Theiss; S. P. Collin; N. S. Hart (Journal of Fish Biology, 2012)
This review identifies a number of exciting new developments in the understanding of vision in cartilaginous fishes that have been made since the turn of the century. These include the results of studies on various aspects of the visual system including eye size, visual fields, eye design and the optical system, retinal topography and spatial resolving power, visual pigments, spectral sensitivity and the potential for colour vision. A number of these studies have covered a broad range of species, thereby providing valuable information on how the visual systems of these fishes are adapted to different environmental conditions. For example, oceanic and deep‐sea sharks have the largest eyes amongst elasmobranchs and presumably rely more heavily on vision than coastal and benthic species, while interspecific variation in the ratio of rod and cone photoreceptors, the topographic distribution of the photoreceptors and retinal ganglion cells in the retina and the spatial resolving power of the eye all appear to be closely related to differences in habitat and lifestyle. Multiple, spectrally distinct cone photoreceptor visual pigments have been found in some batoid species, raising the possibility that at least some elasmobranchs are capable of seeing colour, and there is some evidence that multiple cone visual pigments may also be present in holocephalans. In contrast, sharks appear to have only one cone visual pigment. There is evidence that ontogenetic changes in the visual system, such as changes in the spectral transmission properties of the lens, lens shape, focal ratio, visual pigments and spatial resolving power, allow elasmobranchs to adapt to environmental changes imposed by habitat shifts and niche expansion. There are, however, many aspects of vision in these fishes that are not well understood, particularly in the holocephalans. Therefore, this review also serves to highlight and stimulate new research in areas that still require significant attention.

Assessing the potential for post‐copulatory sexual selection in elasmobranchs - J. L. Fitzpatrick; R. M. Kempster; T. S. Daly‐Engel; S. P. Collin; J. P. Evans (Journal of Fish Biology, 2012)
This review highlights the potential role that post‐copulatory sexual selection plays in elasmobranch reproductive systems and the utility of this group to further understanding of evolutionary responses to the post‐copulatory processes of sperm competition and cryptic female choice. The growing genetic evidence for female multiple mating (polyandry) in elasmobranchs is summarized. While polyandry appears to be common in this group, rates of multiple paternity are highly variable between species suggesting that there is large variance in the strength of post‐copulatory sexual selection among elasmobranchs. Possible adaptations of traits important for post‐copulatory sexual selection are then considered. Particular emphasis is devoted to explore the potential for sperm competition and cryptic female choice to influence the evolution of testes size, sperm morphology, genital morphology and sperm storage organs. Finally, it is argued that future work should take advantage of the wealth of information on these reproductive traits already available in elasmobranchs to gain a better understanding of how post‐copulatory sexual selection operates in this group.

Phylogenetic and ecological factors influencing the number and distribution of electroreceptors in elasmobranchs - R. M. Kempster; I. D. McCarthy; S. P. Collin (Journal of Fish Biology, 2012)
Electroreception is found throughout the animal kingdom from invertebrates to mammals and has been shown to play an important role in prey detection, facilitating social behaviours, the detection of predators and orientation to the earth's magnetic field for navigation. Electroreceptors in elasmobranchs, the ampullae of Lorenzini, detect minute electric fields and independently process these stimuli, thereby providing spatial information to the central nervous system on the location of a source, often potential prey. The ampullae of Lorenzini are individually connected to a single somatic pore on the surface of the skin, with the spatial separation of each pore directly influencing how electrical stimuli are detected and processed. Pore abundance varies across taxonomic groups resulting in unique species‐specific differences. The intricate distribution patterns created by the specific positioning of somatic pores on the head are, however, consistent within families, resulting in patterns that are identifiable at higher taxonomic levels. As elasmobranchs evolved, the electrosensory system became more complex and highly specialized, which is evident by a general trend of increasing pore abundance over time. The elasmobranch electrosensory system has evolved to operate efficiently under the environmental conditions of the particular habitat in which a species lives. For example, reduced pore abundance is evident in oceanic pelagic elasmobranchs, for whom visual cues are thought to be of great importance. Pore abundance and spatial distribution may be influenced by multiple factors including head morphology, phylogeny, feeding behaviour and habitat.

Phylogeography and bindin evolution in Arbacia , a sea urchin genus with an unusual distribution - H. A. LESSIOS; S. LOCKHART; R. COLLIN; G. SOTIL; P. SANCHEZ‐JEREZ; K. S. ZIGLER; A. F. PEREZ; M. J. GARRIDO; L. B. GEYER; G. BERNARDI; V. D. VACQUIER; R. HAROUN; et al. (Molecular Ecology, 2012)
Among shallow water sea urchin genera, Arbacia is the only genus that contains species found in both high and low latitudes. In order to determine the geographical origin of the genus and its history of speciation events, we constructed phylogenies based on cytochrome oxidase I and sperm bindin from all its species. Both the mitochondrial and the nuclear gene genealogies show that Arbacia originated in the temperate zone of the Southern Hemisphere and gave rise to three species in the eastern Pacific, which were then isolated from the Atlantic by the Isthmus of Panama. The mid‐Atlantic barrier separated two additional species. The bindin data suggest that selection against hybridization is not important in the evolution of this molecule in this genus. Metz et al. in a previous publication found no evidence of selection on bindin of Arbacia and suggested that this might be due to allopatry between species, which obviated the need for species recognition. This suggestion formed the basis of the conclusion, widely spread in the literature, that the source of selection on sea urchin bindin (where it does occur) was reinforcement. However, the range of Arbacia spatuligera overlaps with that of two other species of Arbacia , and our data show that it is hybridizing with one of them. We found that even in the species that overlap geographically, there are no deviations from selective neutrality in the evolution of bindin.

Morphology and distribution of the ampullary electroreceptors in wobbegong sharks: implications for feeding behaviour - Susan M. Theiss; Shaun P. Collin; Nathan S. Hart (Marine Biology, 2011)

Detection and genetic characterization of canine parvoviruses and coronaviruses in southern Ireland - Susan McElligott; P. J. Collins; Roy D. Sleator; Vito Martella; Nicola Decaro; Canio Buonavoglia; Helen O’Shea (Archives of Virology, 2011)

Predator-dependent diel migration by Halocaridina rubra shrimp (Malacostraca: Atyidae) in Hawaiian anchialine pools - Cayelan C. Carey; Moana P. Ching; Sarah M. Collins; Angela M. Early; William W. Fetzer; David Chai; Nelson G. Hairston (Aquatic Ecology, 2011)

The potential for paleolimnology to determine historic sediment delivery to rivers - I. D. L. Foster; A. L. Collins; P. S. Naden; D. A. Sear; J. I. Jones; Y. Zhang (Journal of Paleolimnology, 2011)

The relation between adiposity throughout the life course and variation in IGFs and IGFBPs: evidence from the ProtecT (Prostate testing for cancer and Treatment) study - Mari-Anne Rowlands; Jeff M. P. Holly; David Gunnell; Rebecca Gilbert; Jenny Donovan; J. Athene Lane; Gemma Marsden; Simon M. Collin; Freddie Hamdy; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2010)

Prey life‐history and bioenergetic responses across a predation gradient - M. D. Rennie; C. F. Purchase; B. J. Shuter; N. C. Collins; P. A. Abrams; G. E. Morgan (Journal of Fish Biology, 2010)
To evaluate the importance of non‐consumptive effects of predators on prey life histories under natural conditions, an index of predator abundance was developed for naturally occurring populations of a common prey fish, the yellow perch Perca flavescens , and compared to life‐history variables and rates of prey energy acquisition and allocation as estimated from mass balance models. The predation index was positively related to maximum size and size at maturity in both male and female P. flavescens , but not with life span or reproductive investment. The predation index was positively related to size‐adjusted specific growth rates and growth efficiencies but negatively related to model estimates of size‐adjusted specific consumption and activity rates in both vulnerable (small) and invulnerable (large) size classes of P. flavescens . These observations suggest a trade‐off between growth and activity rates, mediated by reduced activity in response to increasing predator densities. Lower growth rates and growth efficiencies in populations with fewer predators, despite increased consumption suggests either 1) a reduction in prey resources at lower predator densities or 2) an intrinsic cost of rapid prey growth that makes it unfavourable unless offset by a perceived threat of predation. This study provides evidence of trade‐offs between growth and activity rates induced by predation risk in natural prey fish populations and illustrates how behavioural modification induced through predation can shape the life histories of prey fish species.

Detection and characterisation of group A rotavirus in asymptomatic piglets in southern Ireland - P. J. Collins; V. Martella; R. D. Sleator; S. Fanning; H. O’Shea (Archives of Virology, 2010)

Potential for mountaintop boulder fields to buffer species against extreme heat stress under climate change - Luke P. Shoo; Collin Storlie; Yvette M. Williams; Stephen E. Williams (International Journal of Biometeorology, 2010)

Characterisation of bacteria in ascites—reporting the potential of culture-independent, molecular analysis - G. B. Rogers; L. E. Russell; P. G. Preston; P. Marsh; J. E. Collins; J. Saunders; J. Sutton; D. Fine; K. D. Bruce; M. Wright (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

A multidisciplinary study of archaeological grape seeds - Enrico Cappellini; M. Thomas P. Gilbert; Filippo Geuna; Girolamo Fiorentino; Allan Hall; Jane Thomas-Oates; Peter D. Ashton; David A. Ashford; Paul Arthur; Paula F. Campos; Johan Kool; Eske Willerslev; et al. (The Science of Nature, 2010)

Pervasive interactions between ungulate browsers and disturbance regimes promote temperate forest herbaceous diversity - Alejandro A. Royo; Rachel Collins; Mary Beth Adams; Chad Kirschbaum; Walter P. Carson (Ecology, 2010)
Disruptions to historic disturbance and herbivory regimes have altered plant assemblages in forests worldwide. An emerging consensus suggests that these disruptions often result in impoverished forest biotas. This is particularly true for eastern U.S. deciduous forests where large gaps and understory fires were once relatively common and browsers were far less abundant. Although much research has focused on how disturbance and browsers affect tree diversity, far less attention has been devoted to forest understories where the vast majority (>75%) of the vascular species reside. Here we test the hypothesis that the reintroduction of disturbances resembling historic disturbance regimes and moderate levels of ungulate browsing enhance plant diversity. We explore whether once‐common disturbances and their interaction with the top‐down influence of browsers can create conditions favorable for the maintenance of a rich herbaceous layer in a region recognized as a temperate biodiversity hotspot in West Virginia, USA. We tested this hypothesis via a factorial experiment whereby we manipulated canopy gaps (presence/absence) of a size typically found in old‐growth stands, low‐intensity understory fire (burned/unburned), and deer browsing (fenced/unfenced). We tracked the abundance and diversity of more than 140 herb species for six years. Interactions among our treatments were pervasive. The combination of canopy gaps and understory fire increased herbaceous layer richness, cover, and diversity well beyond either disturbance alone. Furthermore, we documented evidence that deer at moderate levels of abundance promote herbaceous richness and abundance by preferentially browsing fast‐growing pioneer species that thrive following co‐occurring disturbances (i.e., fire and gaps). This finding sharply contrasts with the negative impact browsers have when their populations reach levels well beyond those that occurred for centuries. Although speculative, our results suggest that interactions among fire, canopy gaps, and browsing provided a variable set of habitats and conditions across the landscape that was potentially capable of maintaining much of the plant diversity found in temperate forests.

The biology of extinct and extant sawfish (Batoidea: Sclerorhynchidae and Pristidae) - Barbara E. Wueringer; Lyle Squire; Shaun P. Collin (Reviews in Fish Biology and Fisheries, 2009)

Reduced TFAP2A function causes variable optic fissure closure and retinal defects and sensitizes eye development to mutations in other morphogenetic regulators - Gaia Gestri; Robert J. Osborne; Alexander W. Wyatt; Dianne Gerrelli; Susan Gribble; Helen Stewart; Alan Fryer; David J. Bunyan; Katrina Prescott; J. Richard O. Collin; Tomas Fitzgerald; David Robinson; et al. (Human Genetics, 2009)

Lithostratigraphy, magnetostratigraphy, and radiometric dating of the Stanislaus Group, CA, and age of the Little Walker Caldera - Christopher J. Pluhar; Alan L. Deino; Nathan M. King; Cathy Busby; Brian P. Hausback; Tracy Wright; Collin Fischer (International Geology Review, 2009)

Controls of Aboveground Net Primary Production in Mesic Savanna Grasslands: An Inter-Hemispheric Comparison - Greg M. Buis; John M. Blair; Deron E. Burkepile; Catherine E. Burns; Annikki J. Chamberlain; Phillip L. Chapman; Scott L. Collins; Richard W. S. Fynn; Navashni Govender; Kevin P. Kirkman; Melinda D. Smith; Alan K. Knapp (Ecosystems, 2009)

Ostracods (Crustacea) and water oxygenation in the earliest Triassic of South China: implications for oceanic events at the end-Permian mass extinction - M-B. Forel; S. Crasquin; S. Kershaw; Q. L. Feng; P-Y. Collin (Australian Journal of Earth Sciences, 2009)

Microbialites as disaster forms in anachronistic facies following the end-Permian mass extinction: a discussion - S. Kershaw; S. Crasquin; P-Y. Collin; Y. Li; Q. Feng; M-B. Forel (Australian Journal of Earth Sciences, 2009)

Physical analysis of the complex rye (Secale cereale L.) Alt4 aluminium (aluminum) tolerance locus using a whole-genome BAC library of rye cv. Blanco - B.-J. Shi; J. P. Gustafson; J. Button; J. Miyazaki; M. Pallotta; N. Gustafson; H. Zhou; P. Langridge; N. C. Collins (Theoretical and Applied Genetics, 2009)

How many Eurasian badgers Meles meles L. are there in the Republic of Ireland? - D. P. Sleeman; J. Davenport; S. J. More; T. A. Clegg; J. D. Collins; S. W. Martin; D. H. Williams; J. M. Griffin; I. O’Boyle (European Journal of Wildlife Research, 2009)

Lutetian arc-type magmatism along the southern Eurasian margin: New U-Pb LA-ICPMS and whole-rock geochemical data from Marmara Island, NW Turkey - P. Ayda Ustaömer; Timur Ustaömer; Alan S. Collins; Jörg Reischpeitsch (Mineralogy and Petrology, 2009)

Validation of a wetland Rapid Assessment Method: Use of EPA’s level 1-2-3 framework for method testing and refinement - Eric D. Stein; A. Elizabeth Fetscher; Ross P. Clark; Adam Wiskind; J. Letitia Grenier; Martha Sutula; Joshua N. Collins; Cristina Grosso (Wetlands, 2009)

Effects of yohimbine and hydrocortisone on panic symptoms, autonomic responses, and attention to threat in healthy adults - Roma A. Vasa; Daniel S. Pine; Carrie L. Masten; Meena Vythilingam; Carlos Collin; Dennis S. Charney; Alexander Neumeister; Karin Mogg; Brendan P. Bradley; Maggie Bruck; Christopher S. Monk (Psychopharmacology, 2009)

A Mass Balance Mercury Budget for a Mine-Dominated Lake: Clear Lake, California - Thomas H. Suchanek; Janis Cooke; Kaylene Keller; Salvador Jorgensen; Peter J. Richerson; Collin A. Eagles-Smith; E. James Harner; David P. Adam (Water, Air, & Soil Pollution, 2009)

Amphibian Commerce as a Likely Source of Pathogen Pollution - ANGELA M. PICCO; JAMES P. COLLINS (Conservation Biology, 2008)
The commercial trade of wildlife occurs on a global scale. In addition to removing animals from their native populations, this trade may lead to the release and subsequent introduction of nonindigenous species and the pathogens they carry. Emerging infectious diseases, such as chytridiomycosis caused by the chytrid fungus Batrachochytrium dendrobatidis (Bd), and ranaviral disease have spread with global trade in amphibians and are linked to amphibian declines and die‐offs worldwide, which suggests that the commercial trade in amphibians may be a source of pathogen pollution. We screened tiger salamanders involved in the bait trade in the western United States for both ranaviruses and Bd with polymerase chain reaction and used oral reports from bait shops and ranavirus DNA sequences from infected bait salamanders to determine how these animals and their pathogens are moved geographically by commerce. In addition, we conducted 2 surveys of anglers to determine how often tiger salamanders are used as bait and how often they are released into fishing waters by anglers, and organized bait‐shop surveys to determine whether tiger salamanders are released back into the wild after being housed in bait shops. Ranaviruses were detected in the tiger salamander bait trade in Arizona, Colorado, and New Mexico, and Bd was detected in Arizona bait shops. Ranaviruses were spread geographically through the bait trade. All tiger salamanders in the bait trade were collected from the wild, and in general they moved east to west and north to south, bringing with them their multiple ranavirus strains. Finally, 26–73% of anglers used tiger salamanders as fishing bait, 26–67% of anglers released tiger salamanders bought as bait into fishing waters, and 4% of bait shops released tiger salamanders back into the wild after they were housed in shops with infected animals. The tiger salamander bait trade in the western United States is a useful model for understanding the consequences of the unregulated anthropogenic movement of amphibians and their pathogens through trade.

Northern hemisphere winter atmospheric climate: modes of natural variability and climate change - Sarah P. E. Keeley; Matthew Collins; Alan J. Thorpe (Climate Dynamics, 2008)

Seasonal variation in the white muscle biochemical composition of deep-sea macrourids in the North-east Atlantic - K. M. Kemp; K. P. P. Fraser; M. A. Collins; I. G. Priede (Marine Biology, 2008)

Female reproductive biology of two sympatric incirrate octopod species, Adelieledone polymorpha (Robson 1930) and Pareledone turqueti (Joubin 1905) (Cephalopoda: Octopodidae), from South Georgia - I. M. Barratt; M. P. Johnson; M. A. Collins; A. L. Allcock (Polar Biology, 2008)

Single cell adhesion measuring apparatus (SCAMA): application to cancer cell lines of different metastatic potential and voltage-gated Na+ channel expression - Christopher P. Palmer; Maria E. Mycielska; Hakan Burcu; Kareem Osman; Timothy Collins; Rachel Beckerman; Rebecca Perrett; Helen Johnson; Ebru Aydar; Mustafa B. A. Djamgoz (European Biophysics Journal, 2008)

Shrub encroachment in North American grasslands: shifts in growth form dominance rapidly alters control of ecosystem carbon inputs - ALAN K. KNAPP; JOHN M. BRIGGS; SCOTT L. COLLINS; STEVEN R. ARCHER; M. SYNDONIA BRET‐HARTE; BRENT E. EWERS; DEBRA P. PETERS; DONALD R. YOUNG; GAIUS R. SHAVER; ELISE PENDALL; MEAGAN B. CLEARY (Global Change Biology, 2008)
Shrub encroachment into grass‐dominated biomes is occurring globally due to a variety of anthropogenic activities, but the consequences for carbon (C) inputs, storage and cycling remain unclear. We studied eight North American graminoid‐dominated ecosystems invaded by shrubs, from arctic tundra to Atlantic coastal dunes, to quantify patterns and controls of C inputs via aboveground net primary production (ANPP). Across a fourfold range in mean annual precipitation (MAP), a key regulator of ecosystem C input at the continental scale, shrub invasion decreased ANPP in xeric sites, but dramatically increased ANPP (>1000 g m −2 ) at high MAP, where shrub patches maintained extraordinarily high leaf area. Concurrently, the relationship between MAP and ANPP shifted from being nonlinear in grasslands to linear in shrublands. Thus, relatively abrupt (

Phylogenetic concordance analysis shows an emerging pathogen is novel and endemic - Andrew Storfer; Michael E. Alfaro; Benjamin J. Ridenhour; James K. Jancovich; Stephen G. Mech; Matthew J. Parris; James P. Collins (Ecology Letters, 2007)
Distinguishing whether pathogens are novel or endemic is critical for controlling emerging infectious diseases, an increasing threat to wildlife and human health. To test the endemic vs. novel pathogen hypothesis, we present a unique analysis of intraspecific host‐pathogen phylogenetic concordance of tiger salamanders and an emerging Ranavirus throughout Western North America. There is significant non‐concordance of host and virus gene trees, suggesting pathogen novelty. However, non‐concordance has likely resulted from virus introductions by human movement of infected salamanders. When human‐associated viral introductions are excluded, host and virus gene trees are identical, strongly supporting coevolution and endemism. A laboratory experiment showed an introduced virus strain is significantly more virulent than endemic strains, likely due to artificial selection for high virulence. Thus, our analysis of intraspecific phylogenetic concordance revealed that human introduction of viruses is the mechanism underlying tree non‐concordance and possibly disease emergence via artificial selection.

Determination of Iodine in Low Mass Human Hair Samples by Inductively Coupled Plasma Mass Spectrometry - K. E. Levine; A. S. Essader; F. X. Weber; J. M. Perlmutter; L. S. Milstein; R. A. Fernando; M. A. Levine; B. J. Collins; J. B. Adams; P. M. Grohse (Bulletin of Environmental Contamination and Toxicology, 2007)

Survival and Growth of Palaemonetes argentinus (Decapoda; Caridea) Exposed to Insecticides with Chlorpyrifos and Endosulfan as Active Element - M. C. Montagna; P. A. Collins (Archives of Environmental Contamination and Toxicology, 2007)

Residence and movement patterns of cownose rays Rhinoptera bonasus within a south‐west Florida estuary - A. B. Collins; M. R. Heupel; P. J. Motta (Journal of Fish Biology, 2007)
Between July 2003 and November 2004, 21 cownose rays Rhinoptera bonasus were tagged and tracked within Pine Island Sound estuary, Florida, using passive acoustic telemetry. Residence time of individuals ranged between 1 and 102 days. No relationship was detected between ray activity and tidal stage or time of day. Minimum convex polygons (MCP) and kernel utilization distributions (KUD) were calculated over several time frames to demonstrate the extent of an animal’s home range and core areas of use. Total MCPs ranged between 0·81 and 71·78 km 2 (mean = 22·01 km 2 ), with daily MCPs as large as 25·8 km 2 . Total 95% KUDs ranged between 0·18 and 62·44 km 2 (mean = 22·63 km 2 ), while total 50% KUDs were smaller, ranging from 0·09 to 9·68 km 2 (mean = 3·33 km 2 ). Both MCP and KUD areas exhibited a positive relationship with residence time and R. bonasus size. As mobile, pelagic swimmers capable of traversing large distances, these data show that cownose rays travel extensively throughout this estuary, yet may remain within very small areas for extended periods.

Captive breeding and embryonic development of Chiloscyllium punctatum Muller & Henle, 1838 (Elasmobranchii: Hemiscyllidae) - B. K. Harahush; A. B. P. Fischer; S. P. Collin (Journal of Fish Biology, 2007)
The fecundity, embryonic development, growth and viability of captive Chiloscyllium punctatum were investigated over two breeding and laying seasons. Chiloscyllium punctatum is an oviparous species, which lays rectangular eggs from late July to February. The six adult female C. punctatum in the open ocean display tank at UnderWater World, Mooloolaba, Australia laid a total of 692 eggs between July 2004 and February 2006, with 228 of those being viable. This equates to each female laying 115·3 eggs over the two seasons, with 38 viable. The embryos are first visible to the naked eye at c . 18 days post deposition (dpd), while pre‐hatching is first seen c . 35 dpd, and the embryos hatch at an average of 153 dpd (temperature 21–25° C). Embryonic growth is most rapid from 99 dpd until hatching. An average of 21·4% of the eggs hatched over the two seasons.

A derivation of roughness correlation length for parameterizing radar backscatter models - M. M. Rahman; M. S. Moran; D. P. Thoma; R. Bryant; E. E. Sano; C. D. Holifield Collins; S. Skirvin; C. Kershner; B. J. Orr (International Journal of Remote Sensing, 2007)

A computational fluid dynamics study of inspiratory flow in orotracheal geometries - T. P. Collins; G. R. Tabor; P. G. Young (Medical & Biological Engineering & Computing, 2007)

Fine mapping and targeted SNP survey using rice-wheat gene colinearity in the region of the Bo1 boron toxicity tolerance locus of bread wheat - Thorsten Schnurbusch; Nicholas C. Collins; Russell F. Eastwood; Tim Sutton; Steven P. Jefferies; Peter Langridge (Theoretical and Applied Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Elton’s hypothesis revisited: an experimental test using cogongrass - A. R. Collins; S. Jose; P. Daneshgar; C. L. Ramsey (Biological Invasions, 2007)

Levels of intra-host and temporal sequence variation in a large CO1 sub-units from Anisakis simplex sensu stricto (Rudolphi 1809) (Nematoda: Anisakisdae): implications for fisheries management - M. A. Cross; C. Collins; N. Campbell; P. C. Watts; J. C. Chubb; C. O. Cunningham; E. M. C. Hatfield; K. MacKenzie (Marine Biology, 2007)

Deep sea benthic bioluminescence at artificial food falls, 1,000–4,800 m depth, in the Porcupine Seabight and Abyssal Plain, North East Atlantic Ocean - E. J. V. Gillibrand; P. Bagley; A. Jamieson; P. J. Herring; J. C. Partridge; M. A. Collins; R. Milne; I. G. Priede (Marine Biology, 2007)

Soil carbon pools and fluxes after land conversion in a semiarid shrub-steppe ecosystem - R. L. Cochran; H. P. Collins; A. Kennedy; D. F. Bezdicek (Biology and Fertility of Soils, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Colour vision and visual ecology of the blue-spotted maskray, Dasyatis kuhlii Müller & Henle, 1814 - Susan M. Theiss; Thomas J. Lisney; Shaun P. Collin; Nathan S. Hart (Journal of Comparative Physiology A, 2007)

Selectivity at a three-base bulge site in the DNA binding of ΔΔ-[{Ru(phen)2}2(μ-dppm)]4+ [dppm is 4,6-bis(2-pyridyl)pyrimidine; phen is 1,10-phenanthroline] - Joy L. Morgan; Damian P. Buck; Adam G. Turley; J. Grant Collins; F. Richard Keene (JBIC Journal of Biological Inorganic Chemistry, 2006)

Response to Rominger - Ben A. Minteer; James P. Collins (Conservation Biology, 2006)

Cypermethrin Toxicity to Aquatic Life: Bioassays for the Freshwater Prawn Palaemonetes argentinus - P. Collins; S. Cappello (Archives of Environmental Contamination and Toxicology, 2006)

Mapping diabetes QTL in an intercross derived from a congenic strain of the Brown Norway and Goto-Kakizaki rats - Stephan C. Collins; Robert H. Wallis; Steven P. Wilder; Karin J. Wallace; Karène Argoud; Pamela J. Kaisaki; Marie-Thérèse Bihoreau; Dominique Gauguier (Mammalian Genome, 2006)

Residency and movement patterns of bonnethead sharks, Sphyrna tiburo, in a large Florida estuary - Michelle R. Heupel; Colin A. Simpfendorfer; Angela B. Collins; John P. Tyminski (Environmental Biology of Fishes, 2006)

Micropropagation of juvenile tissue of Eucalyptus erythronema × eucalyptus stricklandii cv. ‘urrbrae gem’ - P. Glocke; K. Delaporte; G. Collins; M. Sedgley (In Vitro Cellular & Developmental Biology - Plant, 2006)

Soil microbial, fungal, and nematode responses to soil fumigation and cover crops under potato production - H. P. Collins; A. Alva; R. A. Boydston; R. L. Cochran; P. B. Hamm; A. McGuire; E. Riga (Biology and Fertility of Soils, 2006)

Brain morphology in large pelagic fishes: a comparison between sharks and teleosts - T. J. Lisney; S. P. Collin (Journal of Fish Biology, 2006)
A quantitative comparison was made of both relative brain size (encephalization) and the relative development of five brain area of pelagic sharks and teleosts. Two integration areas (the telencephalon and the corpus cerebellum) and three sensory brain areas (the olfactory bulbs, optic tectum and octavolateralis area, which receive primary projections from the olfactory epithelium, eye and octavolateralis senses, respectively), in four species of pelagic shark and six species of pelagic teleost were investigated. The relative proportions of the three sensory brain areas were assessed as a proportion of the total ‘sensory brain’, while the two integration areas were assessed relative to the sensory brain. The allometric analysis of relative brain size revealed that pelagic sharks had larger brains than pelagic teleosts. The volume of the telencephalon was significantly larger in the sharks, while the corpus cerebellum was also larger and more heavily foliated in these animals. There were also significant differences in the relative development of the sensory brain areas between the two groups, with the sharks having larger olfactory bulbs and octavolateralis areas, whilst the teleosts had larger optic tecta. Cluster analysis performed on the sensory brain areas data confirmed the differences in the composition of the sensory brain in sharks and teleosts and indicated that these two groups of pelagic fishes had evolved different sensory strategies to cope with the demands of life in the open ocean.

Preliminary evidence for medication effects on functional abnormalities in the amygdala and anterior cingulate in bipolar disorder - Hilary P. Blumberg; Nelson H. Donegan; Charles A. Sanislow; Susan Collins; Cheryl Lacadie; Pawel Skudlarski; Ralitza Gueorguieva; Robert K. Fulbright; Thomas H. McGlashan; John C. Gore; John H. Krystal (Psychopharmacology, 2005)

Ecological Ethics: Building a New Tool Kit for Ecologists and Biodiversity Managers - BEN A. MINTEER; JAMES P. COLLINS (Conservation Biology, 2005)
Ecological research and biodiversity management often raise ethical questions in areas that include responsibilities and duties to the scientific community, public welfare, research animals, species, and ecosystems. Answering these questions is challenging because ecologists and biodiversity managers do not have the equivalent of bioethics, an established field with a support network focused mainly on biomedicine, to guide them in making decisions. Environmental ethics provides some insight into environmental values and the duties these may impose on humans. But for the most part those in the field have not considered many of the common responsibilities and obligations that ecologists and managers have to the scientific profession or to public welfare. There is a need to bring ethicists, scientists, and biodiversity managers together in a collaborative effort to study and inform the methods of ethical analysis and problem solving in ecological research and biodiversity management. We present a series of cases that illustrate the kinds of ethical questions faced by researchers and biodiversity managers in practice. We argue for the creation of an extensive case database and a pluralistic and integrated ethical framework, one that draws from the theoretical (normative), research, animal, and environmental ethics traditions. These tools form the foundations of a new area of inquiry and practical ethical problem solving, that we call “ecological ethics.”

High-resolution array-CGH profiling of germline and tumor-specific copy number alterations on chromosome 22 in patients affected with schwannomas - Teresita Díaz de Ståhl; Caisa M. Hansson; Cecilia de Bustos; Kiran K. Mantripragada; Arkadiusz Piotrowski; Magdalena Benetkiewicz; Caroline Jarbo; Leif Wiklund; Tiit Mathiesen; Gunnar Nyberg; V. Peter Collins; D. Gareth Evans; et al. (Human Genetics, 2005)

The Novel and Endemic Pathogen Hypotheses: Competing Explanations for the Origin of Emerging Infectious Diseases of Wildlife - LARA J. RACHOWICZ; JEAN‐MARC HERO; ROSS A. ALFORD; JOHN W. TAYLOR; JESS A.T. MORGAN; VANCE T. VREDENBURG; JAMES P. COLLINS; CHERYL J. BRIGGS (Conservation Biology, 2005)
Chytridiomycosis, caused by the fungal pathogen Batrachochytrium dendrobatidis , is an emerging infectious disease implicated in declines of amphibian populations around the globe. An emerging infectious disease is one that has recently been discovered; has recently increased in incidence, geography, or host range; or is newly evolved. For any given outbreak of an emerging disease, it is therefore possible to state two hypotheses regarding its origin. The novel pathogen hypothesis states that the disease has recently spread into new geographic areas, whereas the endemic pathogen hypothesis suggests that it has been present in the environment but recently has increased in host range or pathogenicity. Distinguishing between these hypotheses is important, because the conservation measures needed to slow or stop the spread of a novel pathogen are likely to differ from those needed to prevent outbreaks of an endemic pathogen. Population genetics may help discriminate among the possible origins of an emerging disease. Current evidence suggests chytridiomycosis may be a novel pathogen being spread worldwide by carriers; until we know how much genetic variation to expect in an endemic strain, however, we cannot yet conclude that B. dendrobatidis is a novel pathogen.

Human movement coordination implicates relative direction as the information for relative phase - Andrew D. Wilson; David R. Collins; Geoffrey P. Bingham (Experimental Brain Research, 2005)

Perceptual coupling in rhythmic movement coordination: stable perception leads to stable action - Andrew D. Wilson; David R. Collins; Geoffrey P. Bingham (Experimental Brain Research, 2005)

Life in a warm deep sea: routine activity and burst swimming performance of the shrimp Acanthephyra eximia in the abyssal Mediterranean - D. M. Bailey; P. M. Bagley; A. J. Jamieson; A. Cromarty; M. A. Collins; A. Tselepidis; I. G. Priede (Marine Biology, 2005)

Completion of the Sequence of a Cetacean Morbillivirus and Comparative Analysis of the Complete Genome Sequences of Four Morbilliviruses - B. K. Rima; A. M. J. Collin; J. A. P. Earle (Virus Genes, 2005)

Evidence for emergence of an amphibian iridoviral disease because of human‐enhanced spread - J. K. JANCOVICH; E. W. DAVIDSON; N. PARAMESWARAN; J. MAO; V. G. CHINCHAR; J. P. COLLINS; B. L. JACOBS; A. STORFER (Molecular Ecology, 2005)
Our understanding of origins and spread of emerging infectious diseases has increased dramatically because of recent applications of phylogenetic theory. Iridoviruses are emerging pathogens that cause global amphibian epizootics, including tiger salamander ( Ambystoma tigrinum ) die‐offs throughout western North America. To explain phylogeographical relationships and potential causes for emergence of western North American salamander iridovirus strains, we sequenced major capsid protein and DNA methyltransferase genes, as well as two noncoding regions from 18 geographically widespread isolates. Phylogenetic analyses of sequence data from the capsid protein gene showed shallow genetic divergence ( Ranavirus , suggesting a single introduction and radiation. Analysis of capsid protein sequences also provided support for a closer relationship of tiger salamander virus strains to those isolated from sport fish (e.g. rainbow trout) than other amphibian isolates. Despite monophyly based on capsid protein sequences, there was low genetic divergence among all strains ( Ambystoma mexicanum ) colony. Human enhancement of viral movement is a mechanism consistent with these results. These findings suggest North American salamander ranaviruses cause emerging disease, as evidenced by apparent recent spread over a broad geographical area.

Homozygous loss of menin is well tolerated in liver, a tissue not affected in MEN1 - Peter C. Scacheri; Judy S. Crabtree; Alyssa L. Kennedy; Gary P. Swain; Jerrold M. Ward; Stephen J. Marx; Allen M. Spiegel; Francis S. Collins (Mammalian Genome, 2004)

Quantifying the water vapour feedback associated with post-Pinatubo global cooling - P. M. de F. Forster; M. Collins (Climate Dynamics, 2004)

The role of ecosystem-atmosphere interactions in simulated Amazonian precipitation decrease and forest dieback under global climate warming - R. A. Betts; P. M. Cox; M. Collins; P. P. Harris; C. Huntingford; C. D. Jones (Theoretical and Applied Climatology, 2004)

Amazonian forest dieback under climate-carbon cycle projections for the 21st century - P. M. Cox; R. A. Betts; M. Collins; P. P. Harris; C. Huntingford; C. D. Jones (Theoretical and Applied Climatology, 2004)

Alkalimonas amylolytica gen. nov., sp. nov., and Alkalimonas delamerensis gen. nov., sp. nov., novel alkaliphilic bacteria from soda lakes in China and East Africa - Yanhe Ma; Yanfen Xue; William D. Grant; Nadine C. Collins; Andrew W. Duckworth; Robert P. van Steenbergen; Brian E. Jones (Extremophiles, 2004)

Carbohydrate Distribution in Stalks and Ears of Sweet Maize with Different Endosperm Genotypes - V. M. Russo; J. K. Collins; P. Perkins-Veazie; T. Smith (Cereal Research Communications, 2004)

The role of the defective interfering particle DI9c in mucosal disease in cattle - M. Stokstad; M. Collins; R. Srby; P. Barboni; G. Meyers; T. Lken; J. Brownlie (Archives of Virology, 2004)

To what extent does upright sessile epifauna affect benthic biodiversity and community composition? - C. Bradshaw; P. Collins; A. R. Brand (Marine Biology, 2003)

Effects of Cypermethrin on the Freshwater Crab Trichodactylus borellianus (Crustacea: Decapoda: Braquiura) - W. Vernica; P. A. Collins (Bulletin of Environmental Contamination and Toxicology, 2003)

Integration of soil solarization with chemical, biological and cultural control for the management of soilborne diseases of vegetables - C. Stevens; V. A. Khan; R. Rodriguez-Kabana; L. D. Ploper; P. A. Backman; D. J. Collins; J. E. Brown; M. A. Wilson; E. C. K. Igwegbe (Plant and Soil, 2003)

Barley disease resistance gene analogs of the NBS-LRR class: identification and mapping - L. H. Madsen; N. C. Collins; M. Rakwalska; G. Backes; N. Sandal; L. Krusell; J. Jensen; E. H. Waterman; A. Jahoor; M. Ayliffe; A. J. Pryor; P. Langridge; et al. (Molecular Genetics and Genomics, 2003)

Larval Development of Silver Sea Bream ( Sparus sarba ): Ontogeny of RNA-DNA Ratio, GH, IGF-I, and Na + -K + -ATPase - E. E. Deane; S. P. Kelly; P. M. Collins; N. Y. S. Woo (Marine Biotechnology, 2003)

Sequence Analysis of the Washington/1964 strain of Human Parainfluenza Virus Type 1 (HPIV1) and Recovery and Characterization of Wild Type Recombinant HPIV1 Produced by Reverse Genetics - J. T. Newman; S. R. Surman; J. M. Riggs; Chris T. Hansen; P. L. Collins; B. R. Murphy; M.H. Skiadopoulos (Virus Genes, 2003)

Remote assessment of benthic substrate composition in shallow waters using multispectral reflectance - P. Jeremy Werdell; Collin S. Roesler (Limnology and Oceanography, 2003)
We investigated the utility of quantifying percent coverage of benthic substrate constituents from surface multispectral reflectance measurements. Six substrates were considered: kelp, eelgrass, clay, silt, mineralic sand from a temperate environment, and turtlegrass and carbonate sand from a tropical environment. Each had a unique albedo spectrum that contributes differently to the upward light field in an optically shallow environment. Simplifications to the radiative transfer equation yield an analytic solution for surface reflectance in optically shallow environments. The objectives were to test the inverse model to predict bottom albedo from measurements of surface reflectance, diffuse attenuation, and water depth in the turbid water of eastern Long Island Sound, Connecticut, and clear waters off Exuma, Bahamas. A linear mixing model was used to deconvolve the derived albedo spectra into contributions by the six constituents. The inverse and deconvolution models accurately identified the dominant substrate in the six homogeneous habitats (single point determinations) and predicted the gradient in substrate composition along transects. This approach has applications to benthic survey mapping, habitat assessment, and habitat monitoring.

Evaluation of the Vitek 2 System for Rapid Identification of Clinical Isolates of Gram-Negative Bacilli and Members of the Family Streptococcaceae - P. J. Gavin; J. R. Warren; A. A. Obias; S. M. Collins; L. R. Peterson (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Recent introduction of the dominant tunicate, Pyura praeputialis (Urochordata, Pyuridae) to Antofagasta, Chile - J. C. Castilla; A. G. Collins; C. P. Meyer; R. Guiñez; D. R. Lindberg (Molecular Ecology, 2002)
The large sessile tunicate Pyura stolonifera (Pleurogona: Stolibranchiata: Pyuridae), has been regarded as a complex taxon with disjointed distributions, including Australia ( Pyura stolonifera praeputialis ), South Africa ( Pyura stolonifera stolonifera ) and South America (Chile, Antofagasta: Pyura sp., the ‘piure de Antofagasta’), and has been cited under at least five taxonomic combinations. The ‘piure de Antofagasta’ is a competitively dominant species in rocky intertidal habitats and shows a limited geographical range (60–70 km) exclusively inside the Bay of Antofagasta. Using cytochrome oxidase I (COI) mitochondrial sequence data from Pyura specimens of the three taxa we tested whether the Chilean taxon represents: (i) a Gondwana relict; (ii) a more recently divergent species; or (iii) a recently introduced species. The results suggest that the Chilean taxon is a recent introduction to Chile from Australian populations and that Pyura stolonifera praeputialis , from Australia, and the ‘piure de Antofagasta’ are geographical populations of a single species: Pyura praeputialis ; whereas the South African taxon represents a second species: Pyura stolonifera .

Natural enemies and sex: how seed predators and pathogens contribute to sex-differential reproductive success in a gynodioecious plant - C. Collin; P. Pennings; C. Rueffler; A. Widmer; J. Shykoff (Oecologia, 2002)

Distribution, production, and ecophysiology of Picocystis strain ML in Mono Lake, California - Collin S. Roesler; Charles W. Culbertson; Stacey M. Etheridge; Ralf Goericke; Ronald P. Kiene; Laurence G. Miller; Ronald S. Oremland (Limnology and Oceanography, 2002)
A recently described unicellular chlorophytic alga isolated from meromictic Mono Lake, California, occupies a niche that spans two environments: the upper oxic mixolimnion and the deeper anoxic and highly reducing monimolimnion. This organism, Picocystis sp. strain ML, accounts for nearly 25% of the primary production during the winter bloom and more than 50% at other times of the year. In incubations, it is heavily grazed by the brine shrimp, Artemia monica . We assessed growth and photosynthetic parameters over broad ranges of irradiance, salinity, and pH and under oxic and anoxic conditions. Picocystis appears to be particularly adapted to low irradiance; we observed an order of magnitude increase in the cellular pigment concentrations, as well as marked increases in cellspecific photosynthetic parameters for cells acclimated to low‐growth irradiance. Growth rates of 0.3–1.5 d −1 were observed over a salinity range of 0–260‰ and a pH range of 4–12, with maximal growth at ~50 mmol photons m −2 s −1 , 40‰, and pH 6–10. Growth and oxygenic photosynthesis were observed under anoxic conditions at rates comparable to those measured under oxic conditions. The ability of the organism to acclimate and grow under such a broad range of environmental conditions makes it an important component of the Mono Lake ecosystem and likely contributes to its dominance of the monimolimnion/mixolimnion interface.

Variation in cold tolerance and spring growth among Italian white clover populations - Paolo Annicchiarico; Rosemary P. Collins; Flavio Fornasier; Ian Rhodes (Euphytica, 2001)

Analysis of lymphoedema-distichiasis families forFOXC2 mutations reveals small insertions and deletions throughout the gene - R. Bell; G. Brice; A. Child; V. Murday; S. Mansour; C. Sandy; J. Collin; A. Brady; D. Callen; K. Burnand; P. Mortimer; S. Jeffery (Human Genetics, 2001)

Trends in extreme daily rainfall and temperature in Southeast Asia and the South Pacific: 1961–1998 - M.J. Manton; P.M. Della‐Marta; M.R. Haylock; K.J. Hennessy; N. Nicholls; L.E. Chambers; D.A. Collins; G. Daw; A. Finet; D. Gunawan; K. Inape; H. Isobe; et al. (International Journal of Climatology, 2001)
Trends in extreme daily temperature and rainfall have been analysed from 1961 to 1998 for Southeast Asia and the South Pacific. This 38‐year period was chosen to optimize data availability across the region. Using high‐quality data from 91 stations in 15 countries, significant increases were detected in the annual number of hot days and warm nights, with significant decreases in the annual number of cool days and cold nights. These trends in extreme temperatures showed considerable consistency across the region. Extreme rainfall trends were generally less spatially coherent than were those for extreme temperature. The number of rain days (with at least 2 mm of rain) has decreased significantly throughout Southeast Asia and the western and central South Pacific, but increased in the north of French Polynesia, in Fiji, and at some stations in Australia. The proportion of annual rainfall from extreme events has increased at a majority of stations. The frequency of extreme rainfall events has declined at most stations (but not significantly), although significant increases were detected in French Polynesia. Trends in the average intensity of the wettest rainfall events each year were generally weak and not significant. Copyright © 2001 Royal Meteorological Society

The effect of frequency on the visual perception of relative phase and phase variability of two oscillating objects - Geoffrey P. Bingham; Frank T.J.M. Zaal; J. Alexander Shull; David R. Collins (Experimental Brain Research, 2001)

Application methodology of ca and/or fumigation including use of carbon dioxide under increased pressure - C. J. Waterford; P. P. Asher; M. G. Andrada; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; P. V. Herrera; M. G. Andrada; Ma. Elvira M. Martinez; R. P. Estigoy; P. Williams; R. Ryan; R. Cavasin; et al. (Phytoparasitica, 2001)

Potential threats to conventional ca and/or fumigation (regulatory, insect resistance) - K. A. Mills; PJ. Collins; G. J. Daglish; M. K. Nayak; P. J. Collins; Cao Yang; Wang Dianxuan; T. A. Lambkin (Phytoparasitica, 2001)

Embryogenic response of multiple soybean [Glycine max (L.) merr.] cultivars across three locations - C. A. Meurer; R. D. Dinkins; C. T. Redmond; K. P. McAllister; D. T. Tucker; D. R. Walker; W. A. Parrott; H. N. Trick; J. S. Essig; H. M. Frantz; J. J. Finer; G. B. Collins (In Vitro Cellular & Developmental Biology - Plant, 2001)

Characterisation of marine and lacustrine sediments in a drowned thermokarst embayment, Richards Island, Beaufort Sea, Canada - S. Solomon; P. J. Mudie; R. Cranston; T. Hamilton; S. A. Thibaudeau; E. S. Collins (International Journal of Earth Sciences, 2000)

Factors Affecting Population Assessments of Desert Tortoises - Jerome E. Freilich; Kenneth P. Burnham; Christopher M. Collins; C. Ann Garry (Conservation Biology, 2000)
Desert tortoises have been a subject of controversy since their listing as threatened in 1990. With a wide geographic range and more living individuals than any other listed land animal, biologists have needed to detect population trends against a “noisy” background of strong annual changes. We obtained annual population estimates of desert tortoises over 6 consecutive years at a 2.59‐km 2 plot in Joshua Tree National Park, California. Our estimates, based on weekly spring surveys, varied substantially, particularly between wet and dry years. Concurrently, we followed 10 radiotagged animals for 3 years to corroborate the surveys. Population density was determined separately for each year and for all years combined. Our best population estimate was an average of 67 adult tortoises, three times more than the density reported in a 1978 survey of the same site. Annual mortality was low (

Foraging under the risk of cannibalism leads to divergence in body size among tiger salamander larvae - R. E. Ziemba; M. T. Myers; J. P. Collins (Oecologia, 2000)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Isolation of polymorphic microsatellite loci from the malaria vector Anopheles funestus - S. P. Sinkins; B. J. Hackett; C. Costantini; J. Vulule; Y‐Y. Ling; F. H. Collins; N. J. Besansky (Molecular Ecology, 2000)

Prey capture and accommodation in the sandlance, Limnichthyes fasciatus (Creediidae; Teleostei) - J. D. Pettigrew; S. P. Collin; K. Fritsches (Journal of Comparative Physiology A, 2000)

Rescue of a bovine respiratory syncytial virus genomic RNA analog by bovine, human and ovine respiratory syncytial viruses confirms the “functional integrity” and “cross-recognition” of BRSV cis-acting elements by HRSV and ORSV - A. S. Yunus; S. Krishnamurthy; M. K. Pastey; Z. Huang; S. K. Khattar; P. L. Collins; S. K. Samal (Archives of Virology, 1999)

Development of size structure in tiger salamanders: the role of intraspecific interference - Robert E. Ziemba; James P. Collins (Oecologia, 1999)

Surface Water Transport of Lead at a Shooting Range - J. R. Craig; J. D. Rimstidt; C. A. Bonnaffon; T. K. Collins; P. F. Scanlon (Bulletin of Environmental Contamination and Toxicology, 1999)

Low levels of DNA sequence variation among adapted genotypes of hexaploid wheat - G. J. Bryan; P. Stephenson; A. Collins; J. Kirby; J. B. Smith; M. D. Gale (Theoretical and Applied Genetics, 1999)

A group of schwannomas with interstitial deletions on 22q located outside the NF2 locus shows no detectable mutations in the NF2 gene - Carl E. G. Bruder; Koichi Ichimura; O. Tingby; Kimiyoshi Hirakawa; Atsushi Komatsuzaki; Akira Tamura; Yasuhito Yuasa; V. Peter Collins; J. P. Dumanski (Human Genetics, 1999)

Age structure and diel activity of pouting on the Poole Bay artificial reef - A. J. Fowler; A. C. Jensen; K. J. Collins; I. P. Smith (Journal of Fish Biology, 1999)
Predominantly (86·6%) juvenile ( Trisopterus luscus formed inactive, nonfeeding schools around artificial reef units in Poole Bay, Dorset, during daylight hours and the position of the schools was related to differing tidal conditions. At current speeds >0·3 m s −1 , the pouting congregated close to the reef units, remained low in the water column and maintained position. At current speeds −1 , the schools were more dispersed, further away from reef units and higher in the water column. This tidally‐related behaviour is thought to be related to energy conservation during the daylight hours, when the pouting utilize the lee of reef units during strong tidal currents. Between 15 and 30 min after dusk the majority of pouting left the artificial reef, and returned 45–60 min before dawn. A brief mark‐recapture programme, using 0‐ to 1‐group pouting, confirmed that a proportion of the pouting tagged were present on the artificial reef up to 5 days after marking, suggesting that the site was being used to some extent as a home reef. The nocturnal foraging pattern may be related to the availability of prey species.

Gangliosides and neutral glycolipids in ependymal, neuronal and primitive neuroectodermal tumors - Allan J. Yates; Teresa K. Franklin; Paula McKinney; Raymond Collins; Theodore Comas; Carl P. Boesel; Dennis K. Pearl (Journal of Molecular Neuroscience, 1999)

Muscle parvalbumin isoforms of Clarias gariepinus, Heterobranchus longifilis and Chrysichthys auratus : isolation, characterization and expression during development - B. Focant; F. Mélot; S. Collin; A. Chikou; P. Vandewalle; F. Huriaux (Journal of Fish Biology, 1999)
The white‐muscle parvalbumin isoforms of Clarias gariepinus, Heterobranchus longifilis and Chrysichthys auratus were purified and their physicochemical parameters determined. The three catfish isoforms are distinct but those of C. gariepinus and H. longifilis are more similar. In the course of development, the successive appearance of larval and adult parvalbumins was observed. Larval isoforms (PA I, PA IIa, PA IIb) displayed a lower isoelectric point (pI) and molecular mass than adult ones (PA IIc, PA IIIa, PA IIIb, PA III, PA IV). The PA IIa isoform appeared as an omnipresent typical larval isoform. PA IIb appeared mostly larval, being insignificant in adult specimens; its physicochemical features were the same in the three catfish species. In Chrysichthys auratus , there were three PA II isoforms, one appearing as an adult isoform (PA IIc). The fact that the two types of parvalbumin isoforms appear at different times should reflect specific physiological needs (mobility, feeding) of different developmental stages.

Movement and activity patterns of the European lobster, Homarus gammarus , revealed by electromagnetic telemetry - I. P. Smith; K. J. Collins; A. C. Jensen (Marine Biology, 1998)

Fifty new microsatellite loci for the wheat genetic map - P. Stephenson; G. Bryan; J. Kirby; A. Collins; K. Devos; C. Busso; M. Gale (Theoretical and Applied Genetics, 1998)

Spatial and Temporal Trends in Organochlorine Contamination and Bill Deformities in Double-Crested Cormorants (Phalacrocorax Auritus) from the Canadian Great Lakes - D.P. Ryckman; D.V. Weseloh; P. Hamr; G.A. Fox; B. Collins; P.J. Ewins; R.J. Norstrom (Environmental Monitoring and Assessment, 1998)

Characterization of the human synaptogyrin gene family - Darek Kedra; Hua-Qin Pan; Eyal Seroussi; Ingegerd Fransson; Cecile Guilbaud; John E. Collins; Ian Dunham; Elisabeth Blennow; Bruce A. Roe; Fredrik Piehl; J. P. Dumanski (Human Genetics, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Microbial Degradation of Dimethylsilanediol in Soil - R. G. Lehmann; J. R. Miller; H. P. Collins (Water, Air, & Soil Pollution, 1998)

Acoustic tracking of the dispersal of organic matter by scavenging fishes in the deep-sea - M. A. Collins; I. G. Priede; S. Addison; A. Smith; P. M. Bagley (Hydrobiologia, 1998)

Electromagnetic telemetry of lobster (Homarus gammarus (L.)) movements and activity: preliminary results - I. P. Smith; K. J. Collins; A. C. Jensen (Hydrobiologia, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Isolation and characterisation of microsatellites from hexaploid bread wheat - G. J. Bryan; A. J. Collins; P. Stephenson; A. Orry; J. B. Smith; M. D. Gale (Theoretical and Applied Genetics, 1997)

Characterization of parvalbumin isotypes in white muscle from the barbel and expression during development - F. Huriaux; S. Collin; P. Vandewalle; J. C. Philippart; B. Focant (Journal of Fish Biology, 1997)
Parvalbumin isotypes PA II, PA III, PA IVa, and PA IVb were isolated by chromatography from trunk white muscle of barbel and physicochemically characterized. Electrospray ionization mass spectroscopy revealed that PA II has a lower molecular weight than the other isotypes and that PA IVa and PA IVb each consist of two subforms. Isotype distribution was studied by polyacrylamide gel electrophoresis. In adult fish, the total parvalbumin titre decreased and the isotype distribution varied from the anterior to the posterior myotomes. In the course of barbel development, the total parvalbumin titre increased rapidly as fish standard length increased from 1·3 to 5 cm; then sloped down gently as the length increased to 60 cm. At least six parvalbumin isotypes were identified, three of which are different forms (a, b, and c) of PA II. These three forms were present together at the larval stage, but PA IIc and chiefly PA IIb appeared as early isotypes, contrary to PA IIa which was present until the adult period. Later PA IVb accounted for up to 90% of the total parvalbumin content; PA III and PA IVa are minor adult isotypes. Temporal and spatial variations in the total parvalbumin titre and in the differential expression of barbel parvalbumin isotypes very likely reflected the functional requirements of the fish axial musculature according to fish size and myotome location. Physiologically, the larval isotypes could promote faster relaxation of fast fibres than the adult isotypes, and hence favour shorter contraction times.

A medium-density genetic linkage map of the bovine genome - W. Barendse; D. Vaiman; S. J. Kemp; Y. Sugimoto; S. M. Armitage; J. L. Williams; H. S. Sun; A. Eggen; M. Agaba; S. A. Aleyasin; M. Band; M. D. Bishop; et al. (Mammalian Genome, 1997)

Genetic interrelationships of proteolyticClostridium botulinum types A, B, and F and other members of theClostridium botulinum complex as revealed by small-subunit rRNA gene sequences - R. A. Hutson; D. E. Thompson; P. A. Lawson; R. P. Schocken-Itturino; E. C. Bttger; M. D. Collins (Antonie van Leeuwenhoek, 1994)

Evaluation of mouse monoclonal antibodies raised against an isolate of the variant avian paramyxovirus type 1 responsible for the current panzootic in pigeons - M. S. Collins; D. J. Alexander; S. Brockman; P. A. Kemp; R. J. Manvell (Archives of Virology, 1989)

Isolation and structural determination of a novel coenzyme from a methane-oxidizing bacterium - M. D. Collins; O. W. Howarth; P. N. Green (Archives of Microbiology, 1986)

Infection of gnotobiotic calves with a bovine and human isolate of respiratory syncytial virus. Modification of the response by dexamethasone - L. H. Thomas; E. J. Stott; A. P. Collins; Susan Crouch; Jean Jebbett (Archives of Virology, 1984)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

A study in test reproducibility between laboratories: Report of a Pseudomonas Working Party - P. H. A. Sneath; Vera G. Collins (Antonie van Leeuwenhoek, 1974)

The mouse liver aldehyde oxidase locus (Aox) - J. G. Watson; T. J. Higgins; P. B. Collins; S. Chaykin (Biochemical Genetics, 1972)